Species and geographical origin discrimination of cinnamon using UV-Vis spectroscopy combined with chemometrics - Xiao-Dong Sun; Zhu Pan; Yan-Yan Tang; Qi Zuo; Min Zhang; Huan Liang; Peng-Jiao Wang; Xiu-Li Gao (Food Control, 2027)

Advancements and challenges of partial denitrification/anammox technology: Implementation strategies for plug-flow municipal wastewater treatment - Yufei Wu; Jianwei Li; Ruitao Gao; Qiyu Liu; Qi Zhao; Shunjie Zhang; Xinyu Chen; Jingyu Zhang; Shujun Zhang; Liang Zhang; Yongzhen Peng (Bioresource Technology, 2027)

Magnet-absorbed detrital magnetite from the western Qaidam Basin: Implications to Mars sample return missions - Qi-Tao Hu; Wen-Ping Liu; Qi-Zhi Yao; Shao-Bing Zhang; Wan-Cai Li; Sheng-Quan Fu; Yi-Liang Li; Gen-Tao Zhou (Icarus, 2026)

Room-temperature synthesis of self-supported NiS-Ni2P heterojunctions via a mild plasma strategy for efficient bifunctional water splitting - Mingyang Song; Fan Yang; Yaotian Yan; Jiping Chen; Yangshuo Liu; Yu Liang; Liwu Liu; Jian Cao; Peixin Li; Kai Bao; Junlei Qi (Fuel, 2026)

A novel model for precise segmentation and disease diagnosis of economic forest images in complicated backgrounds - Liang Qi; Chi Zhou; Maocheng Zhao; Bin Wu; Qiaolin Ye; Mingguang Li; Weijun Xie; Shuaishuai Zhao; Kai Zhang (Computers and Electronics in Agriculture, 2026)

Insulin-like peptide 3 facilitates sheep oocytes in vitro maturation and subsequent early embryo development - Qi Yang; Rui-Feng Zhang; Zhao-Yu Jiang; Dui Sun; Rui-Hao Tang; Xiao-Yi Zhang; Yi-Tong Li; Wen-Ying Li; Ao Liu; Chun-Lan Zhang; Zhi-Wen Jia; Meng-Lei Feng; et al. (Theriogenology, 2026)

Organic amendments induce crop-specific soil biotic homogenization associated with SOC sequestration: Evidence from a 35-year intercropping experiment - Guizong Zhang; Jiudong Zhang; Rui-Peng Yu; Hao Yang; Xingguo Bao; Wenju Liang; Qi Li; Long Li (Soil and Tillage Research, 2026)

Toward accurate disease diagnosis of fruit trees: Integrating a novel dual-angle vegetation index with canopy vertical distribution knowledge - Wenjie Zhang; Guijun Yang; Xinlian Liang; Xiaohong Liu; Jianbo Qi; Hao Yang; Haikuan Feng; Bo Li; Changyuan Zhai; Baoguo Wu; Xiaohui Su; Liping Chen; et al. (Remote Sensing of Environment, 2026)

Sample-level PRRSV RT-PCR prevalence in pigs in mainland China (2004–2025): A systematic review and meta-analysis - Mengke Si; Yiwei Wang; Xiang Li; Junxue Qiu; Xiaoyu Chong; Baolei Yang; Mingfeng Chu; Yuchen Liang; Wei Cheng; Jingyan Zhang; Xuelong Chen; Yanping Qi (Preventive Veterinary Medicine, 2026)

Impact of barrier lake collapse on hydrological characteristics and fish habitats: A case study in the Qinghai-Tibetan Plateau - Yunong Qin; Qi Tang; Yuanming Wang; Kefeng Li; Ruifeng Liang (Ecological Modelling, 2026)

Urbanization drives rapid convergence of riverine greenhouse gas levels in the urban agglomeration, North China - Ling Wen; Zhengkui Ge; Yulin Qi; Dietrich A. Volmer; Chao Ma; Chunmei Chen; Zhifeng Yan; Pingqing Fu; Si-Liang Li (Agriculture, Ecosystems & Environment, 2026)

CAZyme-resolved substrate routing explains limited soil organic carbon gains under no-tillage in paddy soils - Qi Liu; Xiang-Bin Yao; Yong-Yu Liang; Chun-Yan Li; Xing Wang; Jian-Ying Qi (Agriculture, Ecosystems & Environment, 2026)

Genetic analysis of reciprocal allotetraploid hybrids between Crassostrea gigas and C. angulata: Heterosis, heritability, and genotype-by-environment interaction of growth and survival traits - Xianchao Bai; Yuanxin Liang; Jianmin Zhou; Qi Li (Aquaculture, 2026)

Fe(II)-driven abiotic-biotic relay alleviates denitrification bottleneck via chemical nitrite reduction and intracellular carbon - Na Hu; Qi Feng; Chenxi Li; Yuanyuan Liu; Baoli Zhu; Tianci Guo; Lei Tong; Jianbo Shi; Robert A. Sanford; Shuyi Li; Yu He; Yidan Hu; et al. (Water Research, 2026)

The role of energy metabolism homeostasis in exogenous trisodium phosphate-delayed browning and quality maintenance of longan fruit - Liang Shuai; Jiwei Pang; Yuan Cheng; Qi Cao; Qian Li; Lingyan Liao; Meiying He; Yunfen Liu; Feilong Yin (Postharvest Biology and Technology, 2026)

High-surface-area g-C3N4/ZIF-8 heterojunction for synergistic radical and non-radical photocatalytic peroxymonosulfate activation toward antibiotic degradation: Mechanistic insight and membrane application - Ying-Ying Zhang; Si-Han Guo; Wu-He Ji Pi; Qing-Tong Dong; Qi Huang; Jing Bu; Li-Xuan Kou; Chun Li; Quan-Liang Chen (Journal of Environmental Chemical Engineering, 2026)

Marine air promotes structural compaction and coating growth of soot aerosols after long-range transport from East Asia - Liang Xu; Qi Yuan; Xiyao Chen; Xiaohuan Liu; Huiwang Gao; Xiaohong Yao; Yuanyuan Wang; Mingzhou Yu; Hanjin Yoo; Ki-Joon Jeon; Keliang Li; Weijun Li (Journal of Environmental Sciences, 2026)

Stereoisomer-specific allosteric activation of xanthine oxidoreductase by shikonin and alkannin: mechanistic insights and hyperuricemia risk assessment - Li Liu; Huizhi Zhan; Yonglan Chen; Jing Long; Yuxin Lan; Huan Liu; Gan Qiao; Maolin Chen; Shi Zhen; Bing He; Liangliang Zhu; Xiaoyi Qi; et al. (Food Chemistry, 2026)

Enhanced phenanthrene degradation in microalgae-bacteria systems: Mechanistic roles of exogenous and indigenous degraders - Mengying Wang; Han Wang; Xuetao Liang; Jingran Li; Chen Wang; Longyan Cui; Shuo Yang; Jiaxuan Lin; Qi Yang; Zhilin Yang (Bioresource Technology, 2026)

Fe-modified hydroxyapatite with regulated surface properties for enhanced Mn2+ adsorption: Structural evolution and adsorption mechanism - Yike Liu; Qi Zhou; Siwen Lao; Saibo Wang; Feilong Liang; Zhiling Li; Anning Song; Zhen Chen; Wei Ma (Chemosphere, 2026)

Bisphenol A induces osteoporosis by targeting LAMA4 and OLR1: Novel insights into environmental bone toxicity - Zhenyang Wang; Yongqin Chen; Jiling Ma; Yuxuan Yang; Ke Li; Xiejia Jiao; Biteng Xu; Guidong Shi; Liang Wang; Lei Qi (Toxicology, 2026)

Flocculation performance of a red soil-based inorganic coagulant enhanced by Fe3O4 magnetic loading - Yixuan Huang; Qi Li; Ruimin Zhao; Ruyan Luo; Shaman Zhou; Yuanliang Zhang; Jingbao He; Wanqing Yang; Zhifei Yu; Jiahao Yang; Liang He; Xuyuan Zhao; et al. (Process Safety and Environmental Protection, 2026)

Involvement of sucrose transporter SUT4 in regulating tomato yield and fruit quality - Yufei Liang; Zhaoyuan Lian; Wenjing Dong; Shuyu Qi; Jingyi Zhao; Wanxing Hu; Ning Li; Haijun Gong (Plant Science, 2026)

Chondroitin sulfate: an environmentally friendly immune inducer enhanceing plant resistance to potato virus X and tobacco mosaic virus - Cui-Hong Hao; Wei Xu; Tian-Qi Liang; Yun-Mei Li; Yi-Lin Guan; Ru-Xin Li; Dan-Ya Ju; Chun-E Peng; Li-Zeng Peng; Qing-Bin Wang (Physiological and Molecular Plant Pathology, 2026)

Genomic insights into the transition from saprophytic to parasitic lifestyles in Hymenochaetales - Ji-Hang Jiang; Xue-Wei Wang; Zi-Qi Shen; Qiu-Shi Li; Shi-Liang Liu; Li-Wei Zhou (Molecular Phylogenetics and Evolution, 2026)

Exogenous dust-induced snow albedo reduction and radiative forcing over the Third Pole - Liang Li; Keqin Duan; Ting Yang; Yuhan Qi; Rong Chen; Peihong Shi (Journal of Hydrology, 2026)

Occurrence of microplastics in farmland around non-ferrous metals sulfide mining areas: Characteristics changes caused by sulfide minerals - Qi Jin; Xinru Li; Lin Bai; Yisheng Liu; Liang Wang; Yanrong Lu; Yingbo Dong; Hai Lin; Yinhai He (Journal of Environmental Sciences, 2026)

Insights into the fate and dynamics of antibiotic resistance in multidrug-resistant Bacillus cereus during in vitro simulated gastrointestinal digestion - Wen-Li Shi; Juan Zhang; Rui Huang; Yan Qi; Juan Wang; Yu Ding; Jia-Jun Yan; Quan Zhou; Zi-Hui Chen; Zhi-Hang Chen; Ai-Min Jiang; Ling Chen; et al. (Food Research International, 2026)

Cod protein modifications induced by lipid oxidation-derived aldehydes: Insights into multi-aldehydes environment - Ting-qi Yang; Shenghai Liu; Kaiyu Jiang; Juncai Tu; Menghui Wang; Yuxuan Liang; Jinjin Li; Beiwei Zhu; Wei Gong (Food Chemistry, 2026)

The priming effect of biodegradable microplastics in paddy soil and its various aggregates - Kaitao Jia; Yujiao Song; Chufan Mo; Qi Liang; Xinle Li; Kaijia Xue; Yuting Zhang; Chunying Li; Chunjian Zhao (European Journal of Soil Biology, 2026)

Carboxymethyl cellulose content optimization in an electro-responsive hydrogel for efficient swelling and superior forward osmosis draw agent performance - Xing Ji; Bo Zhang; Yuan Liang; Yu Zhang; Feng Wang; Zonghe Huang; Haoyu Zhang; Yonggang Wang; Qi Li (Desalination, 2026)

Engineered probiotic carriers enregulate coordinated cuproptosis and ferroptosis with immune activation against bladder cancer - Anguo Zhao; Rongkang Li; Rui Liang; Qi Zhuang; Yang Liu; Dashi Deng; Peng Yu; Lei Peng; Hongbo Xu; Jun Zhang; Zhangxin He; Xin Chen; et al. (Chemical Engineering Journal, 2026)

Three-armed biodegradable polyesters with ionization-mimicking cationic lipid properties for VEGF mRNA delivery in critical limb ischemia - Changduo Wang; Yaming Guo; Xiaoyu Liang; Yujie Zhang; Kaijing Liu; Gen Li; Ni Zhu; Chunxiao Qi; Jiajia Shi; Chao Liu; Jianwu Dai; Jing Yang (Chemical Engineering Journal, 2026)

Dendritic cell membrane enhanced chemo-sonodynamic therapy to synergistically promote anti-tumor immunity in ovarian cancer - Hui Zhang; Huanzhi Zhang; Xuan Gu; Qi Wang; Wanrui Shi; Xinxin Xie; Shuyu Xu; Peng Zuo; Xiuli Sun; Jianliu Wang; Xiaolong Liang; Xiaoping Li (Chemical Engineering Journal, 2026)

Ultrasensitive terahertz biosensing of D-aspartic acid via graphene oxide/gold nanoparticles functionalized quasi-BIC metasurfaces: Targeted adsorption and field enhancement - Xin Yan; Ji Qi; Pibin Bing; Lanju Liang; Zhenhua Li; Haiyun Yao; Ziqun Wang; Xiaofei Hu; Zhongyang Li; Jianquan Yao (Chemical Engineering Journal, 2026)

An injectable thiolated alginate/oxidized dextran hydrogel with curcumin-copper nanoparticles for corneal neovascularization after alkali burn - Zhongwu Bei; Lin Ye; Shiyu Liang; Qi Tong; Xicheng Li; Jianan Li; Xiaorui Yu; Yujia Wei; Xuyue Liang; Tingyu Yang; Yun Yang; Longqian Liu; et al. (Carbohydrate Polymers, 2026)

Kit Ligand enhances in vitro oocyte maturation and early embryonic development in sheep - Qi Yang; Dui Sun; Zhao-Yu Jiang; Rui-Hao Tang; Rui-Feng Zhang; Xiao-Yi Zhang; Wen-Ying Li; Yi-Tong Li; Ao Liu; Chun-Lan Zhang; Zhi-Wen Jia; Meng-Lei Feng; et al. (Animal Reproduction Science, 2026)

Optimized fast desensitized Kalman filter - Tai-shan Lou; Liang Ma; Li-ying Jiang; Yu-zhao Jiao; Liang-Yu Zhao; Ren-long Qi (Advances in Space Research, 2026)

Species Divergence in Oxytocin-Dependent Yawning on a Conserved Glutamatergic Erection Circuit - Yan-Chu-Fei Zhang; Qing-Wu Zheng; Yang Lu; Hao-Yuan Wang; Jiao Cang; Xin-Rui Wu; Lin-Yao Fan; Liang Li; Ni-Na Zhang; Xiao-Yang Zhang; Jing-Ning Zhu; Jian Jing; et al. (Neuroscience Bulletin, 2026)
Yawning coupled with penile erection is a conserved neurobehavioral syndrome mediated by the paraventricular hypothalamus (PVH). However, the distinct roles of oxytocin and its co-transmitters remain unresolved. Using chemogenetics, we showed that activation of PVH oxytocin neurons was sufficient to elicit both responses, whereas silencing these neurons abolished them. Viral tracing revealed that these neurons project collaterally to the brainstem reticular nucleus and spinal cord to spatially coordinate autonomic and somatic motor outputs. By dissecting the molecular mechanisms using CRISPR-Cas9, we found that vesicular glutamate transporter 2 (VGLUT2)-dependent glutamatergic transmission provides the primary drive for both behaviors, whereas the oxytocin peptide is selectively required for yawning but dispensable for erection. Comparative analyses across rats, hamsters, and mice demonstrated that while the glutamatergic erectile circuit was conserved, mice lacked spontaneous yawning and were resistant to apomorphine-induced yawning. These findings suggest a hierarchical co-transmission framework in which fast glutamatergic signaling provides the core drive, while oxytocin confers behavioral specificity.

Genetic Parameters and the Influence of Genotype by Environment Interactions on Growth Traits in Crassostrea gigas - Geng Cheng; Zhenzong Pan; Shulei Jin; Yuanxin Liang; Wenlong Bi; Chengxun Xu; Haijun Liu; Qi Li (Journal of Ocean University of China, 2026)

Retraction notice to “Environmental effect and spatiotemporal pattern of stable isotopes in precipitation on the transition zone between the Tibetan Plateau and arid region” [Sci. Total Environ. 749 (2020) 141559] - Gui Juan; Zongxing Li; Feng Qi; Yuan Ruifeng; Ning Tingting; Zhang Baijuan; Xue Jian; Gao Wende; Nan Fusen; Ding Weixuan; Yang Anle; Liang Pengfei (Science of The Total Environment, 2026)

Solvent-resistant gelatin-calcium alginate dual-network gel membranes for separation in organic solvents - Xiaolei Wang; Zifei Qi; Haomiao Liang; Lei Wang; Chan Huang; Haike Li; Huan Zhang; Zhiyun Kong; Huicai Wang (Journal of Water Process Engineering, 2026)

SlCOMT1-dependent melatonin biosynthesis is required for auxin-mediated alleviation of cadmium toxicity in tomato - Zi-Qi Pei; Cheng Ma; Peng Xing; Liang-Hao Li; Xin-Xin Mou; Tong Guo; Lu Wang; Juan Wang; Sheng Zheng; Teng-Guo Zhang (Journal of Plant Physiology, 2026)

The hidden buffering: How carbonate geology and sediments suppress CO2 emissions from reservoirs - Xuan Hu; Wanfa Wang; Xixi Lu; Hongkai Qi; Amit Kumar; Dengming He; Shijun Tu; Yufei Bao; Jie Zeng; Qixin Wu; Hao Xia; Yuchun Wang; et al. (Journal of Hydrology, 2026)

Biodegradable plastic mulches: Distinct effects on microbial communities but no impact on soil multifunctionality during cabbage production - Rong Liang; Lei Mei; Jina Ding; Li Wang; Mouliang Xiao; Yongfu Li; Xiao Liu; Changlong Shao; David R. Chadwick; Davey Jones; Fan Ding; Can Hu; et al. (Journal of Hazardous Materials, 2026)

Particulate matter-bound metals and chlorinated paraffins co-exposure: A population-based study on attention-deficit/hyperactivity disorder in Chinese youth - Ya-Qin Zhang; Qi Yang; Hai-Xin Tu; Haseeb Tufail Moryani; Wan-Ting He; Jing-Wen Huang; Dan-Yao Zhou; Yun-Ting Zhang; Li-Xia Liang; Yang Zhou; Li-Zi Lin; Wen-Wen Bao; et al. (Journal of Hazardous Materials, 2026)

Dual-defect engineering in a supported heterostructure for efficient photocatalytic degradation of polylactic acid microplastics and organic pollutants - Liang Li; Yujiang Zhong; Weitao Han; Liuxin Xiao; Yahong Xie; Yunlong Zhao; Ying Qi (Journal of Environmental Chemical Engineering, 2026)

Non-monotonic evolution of reservoir permeability during water flooding: Impact of development history of depleted hydrocarbon reservoirs on hydrogen recovery efficiency - Xufeng Liang; Yongfei Yang; Tonghui Liu; Ruixu Wan; Haoyun Li; Qi Zhang; Weichen Sun; Yingwen Li; Hai Sun; Lei Zhang; Junjie Zhong; Kai Zhang; et al. (Gas Science and Engineering, 2026)

Quantitative analysis of spray morphology and shock wave structures in supercritical methanol spray - Xiaojie Li; Liang Wang; Yi Hu; Lin Xiang; Ruiqi Wang; Qi Xiao; Zhaowen Wang (Fuel, 2026)

Effective photodynamic inactivation of curcumin in combination with ethylenediaminetetraacetic acid against Burkholderia gladioli pathovar cocovenenans - Xiu-Xia Tian; Jia-Jun Yan; Rui Huang; Quan Zhou; Qi-Ying Zeng; Yu-Ming Jiang; Zi-Hui Chen; Hai-Yan Wang; Bai-Sheng Li; Yong-Ning Wu; Wei-Liang Wu (Food Research International, 2026)

Smartphone-integrated cascade immunosensing platform based on antibody-enzyme-inorganic hybrid nanoflowers for highly sensitive detection of zearalenone - Huan Liang; Xiao-Dong Sun; Peng-Jiao Wang; Jia-Qi Wang; Shuo Zhang; Min Zhang; Xiu-Li Gao (Food Research International, 2026)

Fenugreek gum/casein edible gel film based on polycarboxylic acid cross-linking: Performance characterization, cross-linking mechanism and application - Shengnan Liang; Jia Song; Tianhang Zheng; Guofang Zhang; Chun Li; Libo Liu; Peng Du; Xiaoxi Qi; Zhicheng Chen; Quan Su; Jiazhou Wei (Food Chemistry, 2026)

Mg hydrogen generator based intelligent responsive stent for in situ therapy of reflux esophagitis - Guokai Zeng; Junjie Liang; Yuxuan Zhang; Guofeng Zeng; Xiaoying Li; Qiansha Luo; Bingjun Wu; Yuxin Tang; Jiazheng Chen; Shuhan Zhou; Fang Qin; Qi He; et al. (Chemical Engineering Journal, 2026)

Elevation-dependent factors of soil organic carbon in food legume-based agroecosystems - Qi Liu; Xuebin Xu; Shuang Wang; Liang Wei; Yongfu Li; Wenli Ling; Xiang Wan; Wu Xiang; Zhenke Zhu; Yakov Kuzyakov; Qiong Liu; Tida Ge (Plant and Soil, 2026)

Dynamic Early Warning Model for Coal Spontaneous Combustion Based on Machine Learning - Gang Bai; Ran Liang; Wei Wang; Yun Qi; Xiaowen Zhang; Xueming Li; Xun Zhang (Natural Resources Research, 2026)

Biochemical and multi-omics analyses reveal skeletal muscle adaptation to chronic low-salinity stress of marine medaka (Oryzias melastigma) - Tian-Hong Chen; Qing-Hao Zhan; Xiao-Yu Zeng; Ning-Ning Ma; Qi-Liang Li; Run-Jie Jin; Jia-Lang Zheng; Qing-Ling Zhu (Fish Physiology and Biochemistry, 2026)

The unique effect of Atlantic forcing on Central Pacific El Niño - Qi Tian; Jiawei Tang; Ruiqiang Ding; Jianping Li; Liang Shi (Climate Dynamics, 2026)

Soil animal ecology in China: Two decades of progress and future prospects - Xin Sun; Zhihong Qiao; Weixin Zhang; Qi Li; Yuanhu Shao; Haifeng Yao; Jihua Wu; Manqiang Liu; Donghui Wu; Wenju Liang; Feng Hu; Stefan Scheu; et al. (Soil Ecology Letters, 2026)

Polyphase of uranium mineralization in granite-related deposits: Insights from the geochronology and geochemistry of pitchblende and coffinite in the Xiwang uranium deposit, South China - Bin Liu; Weifeng Chen; Haidong Li; Jiaming Qi; Liang Qiu; Hongfei Ling (Applied Geochemistry, 2026)

The gut microbiota mediates the antidepressant effects of imipramine: Evidence from fecal microbiota transplantation and prebiotic inulin intervention - Yonglan Chen; Yuxin Lan; Jingyan Yi; Xiaoyi Qi; Li Liu; Sha Liu; Xinxin Xu; Huan Liu; Yufeng He; Bing He; Xiaochi Ma; Muhan Lü; et al. (Psychopharmacology, 2026)

New ecdysteroids with anticomplementary activity from roots of Leuzea uniflora (L.) holub - Wen-qing Du; Can Liu; Ruo-mei Li; Ning-ning Shi; Yan-nan Ji; Jin-long Qi; Yu-cheng Gu; Chun-hui Liang; Man-li Zhang (Natural Product Research, 2026)

Examination of growth, survival, physiological parameters, and gonad development in Pacific oysters of different ploidy under varying temperature and salinity levels - Geng Cheng; Hong Hu; Yuanxin Liang; Chengxun Xu; Qi Li (Aquaculture International, 2026)

Tolypaxillines A–J: indole diterpenoids with neuroprotective activities from a soil-derived fungus Tolypocladium album DWS131 - Yu-Fen Tan; Xing-Yi Chen; Chao Wang; Ai-Lin Liang; Wen-Yu Lu; Le-Meng Feng; Qi Huang; Yue-Ping Jiang; Shao Liu; Xiao-Bo Xia; Jing Li; Wen-Xuan Wang (Phytochemistry, 2026)

Genome-wide interactions with cadmium exposure in dysglycemia: populational effects and molecular insights - Qi Jiang; Bin Li; Yunfei Ma; Wanying Shi; Liang Ding; Naifan Hu; Yunhao Zhao; Yingli Qu; Zheng Li; Peijie Sun; Yifu Lu; Donghui Zhang; et al. (Journal of Hazardous Materials, 2026)

Carbohydrate conversion and microbial community restructuring following Saccharomyces cerevisiae inoculation during Pu-erh tea fermentation - Ruoyu Li; Teng Wang; Qiuyue Chen; Yanhui Guan; Nianguo Bo; Qi Wang; Yiqing Guan; Dihan Yang; Ping Liang; Yan Ma; Tiejun Ling; Ming Zhao (International Journal of Food Microbiology, 2026)

Effect of Ohmic heating combined with glycation on the structure and immunoreactivity of tropomyosin from Litopenaeus vannamei - Qi Fang; Ashily Liang Wang; Yunzi Jiang; Weiqiang Qiu; Li Li; Yuhui Feng; Yingshan Jin; Chancong Jiang; Yinzhe Jin (Innovative Food Science & Emerging Technologies, 2026)

L-xylulose, a new versatile rare sugar: recent biosynthetic advances and challenges - Xiaolan Li; Yating Liang; Guoyan Zhang; Jingqiong Wan; Yifan Yu; Zhongyi Hua; Zhi-Hong Zhang; Xianghui Qi; Zhen Ouyang (Food Research International, 2026)

EEG signal recognition of flavor perception in rapeseed oil from different processing techniques - Lanhang Yao; Di Liang; Yini Yang; Wenlin Li; Mingquan Huang; Qi Zhou (Food Chemistry, 2026)

Engineering over-oxidized cu on CNTs for sensitive non-enzymatic glucose sensing and energy applications - Songxin Zhong; Rida Li; Hui Chen; Chao Xiao; Yining Lan; Qi-an Chen; Jian Li; Changqiang Feng; Shizhan Li; Hengchan Qi; Chi Gong; Zukun He; et al. (Chemical Engineering Journal, 2026)

Bio-inspired functionalization of PA1012 into piezoelectric ionomers via molecular asymmetry and ion-cluster polarization - Guangmou Cao; Rong Li; Qi Liang; Jingwen Liu; Pengyuan Luo; Haomeng Ma; Yang Yu; Linyi Cui; Le Xu; Jingjing Ma; Tong Lin; Liuchun Zheng (Chemical Engineering Journal, 2026)

Differential analysis of lipid profiles in natural Calculus Bovis and Bovis Calculus Sativus by UHPLC-MS/MS - Qiang Mao; Huan Zhong; Wan-Li Liang; Jin Dai; Rui-Ting Huang; Yi-Di Wang; Di-Yang Sun; Kai Tang; Long-Fei Xia; Hai-Biao Gong; Yi-Fang Li; Wan-Yang Sun; et al. (Journal of Natural Medicines, 2026)

Gastrodin Ameliorates Blood Pressure by Targeting the PPAR-γ/NF-κB/NLRP3 Signaling Axis in the Hypothalamic Paraventricular Nucleus - Yu Yang; Xiao-Jing Yu; Li-Yan Fu; Jie Qi; Kai-Li Liu; Xiu-Yue Jia; Wei Cui; Qing Su; Ting Huang; Yan-Feng Liang; Hua Tian; Huan Liu; et al. (Cardiovascular Toxicology, 2026)

CRKL amplification synergizes with mechanical stress-induced signaling to dually activate YAP oncogenic pathways, driving plantar melanoma progression - Jiashe Chen; Liang Li; Ruoqi Wang; Fei Wu; Nanhui Wu; Yongyi Xie; Wei Tan; Yun Bai; Shuyi Liu; Qi Yu; Yueyi Zhu; Mingyuan Xu; et al. (Apoptosis, 2026)

RNA regulation in plants - Yijun Qi; Yueqin Chen; Hongwei Guo; Huishan Guo; Runlai Hang; Guifang Jia; Yan Li; Beixin Mo; Zhen Wang; Liang Wu; Yiji Xia; Xiaofei Yang; et al. (Science China Life Sciences, 2026)

Establishment and comprehensive performance evaluation of auto- and allo-tetraploids derived from Crassostrea gigas and C. angulata - Xianchao Bai; Yuanxin Liang; Geng Cheng; Jianmin Zhou; Rui Xu; Qi Li (Aquaculture International, 2026)

Treatment of waste activated sludge and the enhancement mechanism for electron transfer in an osmotic microbial fuel cell - Shilong Li; Lin Qi; Qiusheng Gao; Yanyan Jia; Hengliang Zhang; Liang Duan; Bruce E. Rittmann (Water Research, 2026)

Cascade dams amplify molecular transformation and compositional homogenization of dissolved organic matter on the Eastern Tibetan Plateau - Dengming He; Wanfa Wang; Philipp Maurischat; Yuanbi Yi; Yulin Qi; Xuan Hu; Shijun Tu; Shengde Yu; Jie Zeng; Qixin Wu; Hao Xia; Ding He; et al. (Water Research, 2026)

Mapping global floodplain development disparities highlights drivers behind intensifying flood losses - Zhiyang Lan; Wenbin Liu; Rafael Jan Pablo Schmitt; Chaoyang Wu; Yingjie Li; Deliang Chen; Peirong Lin; Kailiang Yu; Xinli Bai; Kaihao Zheng; Tingting Wang; Hong Wang; et al. (Science Bulletin, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Synthesis, characterization, and antimicrobial properties of 8-Hydroxyquinoline-based group 4 metal complexes for plant pathogen control - Tiankun Zhao; Baoqing Lv; Yinan Ding; Dongyu Mei; Jing Ma; Qi Zhang; Li Zhang; Qipin Qin; Zhongduo Yang; Shanjia Li; Isabel Correia; Hong Liang; et al. (Pesticide Biochemistry and Physiology, 2026)

Green synthesis of magnetite tailings derived Fe3O4@CaSiO3 core-shell magnetic adsorbents with a highly-efficient removal of Cu(II) in aqueous - Mingyang Qi; Xianku Wang; Pengfei Zhou; Hairui Yao; Zhongwen Li; Pengjia Wang; Guanling Yang; Jinsheng Liang; Fei Wang (Journal of Environmental Chemical Engineering, 2026)

A dual-responsive silica-based molecularly imprinted polymer for sustainable and specific adsorption of γ-aminobutyric acid from Moringa oleifera seeds - Jiabo Cheng; Jirui Sui; Xuanyi Yu; Kungang Li; Qi Liang; Chuancheng Lin; Mingxing Li; Chunying Li; Chunjian Zhao (Food Research International, 2026)

Different land use types around megacities contribute contrasting heavy metal pollution and health risks in soil-leaf vegetable systems - Ling Huang; Wen-Fei Chen; Yue-E Guan; Yan-Ping Pang; Sheng-Gong Yu; Lin Li; Qi Zou; Meng-Qiang Sun; Hang Wei; Zhi-Liang Chen (Environmental Research, 2026)

From air to adipose: Investigating PM2.5-bound chlorinated paraffins and overweight/obesity in Chinese children and adolescents - Qi Yang; Hai-Xin Tu; Yu He; Ya-Qin Zhang; Muhammad Amjad; Jing-Fu Lai; Jing-Wen Huang; Yun-Ting Zhang; Wan-Ting He; Li-Xia Liang; Wen-Wen Bao; Yang Zhou; et al. (Environmental Research, 2026)

CdS incorporation induced gate-opening in UiO-66-NH2 for photocatalysis - Qi Li; Bryan Kit Yue Ng; Zhao-Xue Luan; Ping-Luen Baron Ho; Daniel Woodside; Xiyu Zhang; Christopher Foo; Pu Zhao; Tai-Sing Wu; Yun-Liang Soo; Mingjie Li; Xin-Ping Wu; et al. (Chemical Engineering Journal, 2026)

Morphology and mixing state of multi-core soot over the eastern China seas - Mengze Li; Qi Yuan; Xiyao Chen; Liang Xu; Yuanyuan Wang; Jian Zhang; Jun Liu; Xiaohong Yao; Huiwang Gao (Atmospheric Environment, 2026)

Enhancing Topographic Mapping Using Relief Shading: A Case Study of the Larsemann Hills, East Antarctica - Yibo Li; Teng Li; Xiang Zhang; Tiancheng Zhao; Baogang Zhang; Lei Zheng; Shuhang Zhang; Qi Liang; Xiao Cheng (Journal of Geovisualization and Spatial Analysis, 2026)

Intermittent Theta-Burst Stimulation (iTBS) Improves Motor Coordination and Modulates Neuroinflammation and Autophagy in SCA3/MJD Mice - Le-Wen Chen; Yan-Hua Lian; Xiao-Lei Dong; Kai-Liang Luo; Li-Qiong Zhan; Li-Li Xie; Qi-Kui Sun; Wei Lin; Shi-Rui Gan; Xiao-Ping Cheng; Jun Ni; Xin-Yuan Chen (The Cerebellum, 2026)

Petroleum Geological Conditions and Exploration Potential Prediction of Deepwater and Deep Formations in the Under-Explored Offshore Indus Basin - Baohua Lei; Jing Liao; Jie Liang; Qi Li; Jianming Gong; Xiaodong Yang; Jing Sun; Yinguo Zhang (Journal of Marine Science and Engineering, 2026)
The Offshore Indus Basin is located on the western margin of the Indian Plate, adjacent to the onshore Lower Indus Basin in Pakistan and the Kutch Basin along India’s western coast. Deepwater and deep formations in this basin are characterized by low exploration intensity and poor early data quality, which hinder the verification of hydrocarbon potential. Based on newly acquired high-resolution seismic data and onshore–offshore correlation, this study analyzes basin evolution and systematically evaluates petroleum geological conditions and exploration potential of deepwater and deep formations. The results show that the basin has experienced three evolutionary stages: Mesozoic rifting, Cenozoic post-rift thermal subsidence, and passive continental margin development, which collectively control the petroleum geological conditions of deepwater and deep strata. Mesozoic strata (Jurassic and Cretaceous) are widely developed beneath the Deccan volcanic rocks, with a stable distribution. Three sets of potential source rocks are identified: Cretaceous (Type II/III organic matter, high maturity, high quality), Paleo–Eocene (Type III, moderate maturity, high quality), and Lower Miocene (Type II2/III, low maturity, poor–moderate quality). Three sets of high-quality reservoirs are developed: Cretaceous deltaic–shallow marine sandstones, Paleocene reef limestones, and Miocene deltaic and subaqueous fan sandstones. Three hydrocarbon accumulation models are established. Favorable structural belts are mainly distributed in the NW, NE, and SE parts of the basin, dominated by structural and lithological traps. Thin Deccan volcanic rocks in deepwater areas exert a positive effect on the preservation of deep Mesozoic strata and petroleum system development. This study clarifies the key petroleum geological conditions and accumulation rules of deepwater and deep formations, providing a robust basis for hydrocarbon exploration potential evaluation in the Offshore Indus Basin.

Genetic analysis and reproductive interventions in families affected by congenital cataracts: a study of 107 cases - Yun-hao Li; Qi Wang; Yao Peng; Juan Du; Liang Hu; Zhen-hua Tan; Feng Gu; Hao Hu; Qian-jun Zhang; Ge Lin; Guang-xiu Lu; Yue-Qiu Tan; et al. (Journal of Applied Genetics, 2026)

The major chemical constituents of Penthorum chinense Pursh and their inhibitory activity against enzymes associated with metabolic dysfunction-associated steatotic liver disease - Chao-Qun Wang; Meng-Qi Wang; Xiao-Na Gan; Ting-Zhao Li; Xiang-Wei Zheng; Bo Li; Xin Fang; Shuang Liang (Natural Product Research, 2026)

Overexpression of the Mentha canadensis McTTG2 gene positively regulates trichome development and proanthocyanidins biosynthesis in transgenic Arabidopsis - Yang Bai; Yichuan Xu; Xiwu Qi; Li Li; Xu Yu; Hailing Fang; Dongmei Liu; Fei Chen; Chengyuan Liang (Plant Science, 2026)

Monitoring snow depth with ICESat-2 at mid-latitudes: a synergistic multi-scale framework integrating ground-airborne-satellite observations in northern Xinjiang, China - Liangchen Zhu; Lei Zheng; Jiake Wu; Chuyue Peng; Yuan Li; Shuhang Zhang; Xinyue Zhong; Qi Liang; Xiongxin Xiao; Xiao Cheng (Journal of Hydrology, 2026)

RDX as the sole nitrogen source affects the nitrogen metabolism in Rhodococcus sp. LMD - Songwei Hu; Mengdi Li; Yaya Huang; Yanchao Li; Songrui Zhang; Wenjia Li; Bing Lin; Jiaxin Zhengchen; Qi Lv; Xuanrui Shen; Huibin Zou; Fengbing Liang; et al. (Journal of Hazardous Materials, 2026)

Sensitivity analysis and multi-objective particle swarm optimization (MOPSO) of a hollow fiber membrane module for the solar-based heating and humidification system - Si Zeng; Peng Peng; Nan-Feng Li; Cai-Hang Liang; Rong-Hui Qi; Yan-fang Dong; Yu-Kui Men; Jia-Hui Li; Gui-Yin Li (Energy and Buildings, 2026)

Heteroatom bridging chemistries enabling fast polysulfide redox and stable lithium deposition - Guangfeng Zeng; Ruiqing Luo; Yumei Qin; Xue Li; Fangting Xie; Jiajia Wang; Shulong Wang; Jingru Liang; Zhiqi Ma; Duming Wei; Qi-Pin Qin; Xiang-Long Huang (Chemical Engineering Journal, 2026)

In-site fabrication of pheromone-loaded core-sheath fibers via handheld emulsion electrospinning with natural surfactants for Apolygus lucorum attraction - Hai-yan Ye; Wen-jie Shangguan; Han Wu; Jing Zhao; Liu-bin Xiao; De-jin Xu; Guang-chun Xu; Qi-liang Huang; Guo-hui Zhang; Li-dong Cao; Yong-an Tan (Chemical Engineering Journal, 2026)

ANKFN1 in skin fibroblasts may modulate mast cell activity and is associated with dupilumab response in atopic dermatitis - Qiu-ju Wei; Jia-rong Lu; Wan-yan Xiang; Hai-qi Liang; Si-qi Zhang; Si-yu Huang; Jun-wen Peng; Ze-feng Zhou; Qiu-ju Li; Wen-jun Zheng (Immunologic Research, 2026)

A state-of-the-art review of accurate and rapid prediction methods for thermal striping phenomenon in nuclear reactors - Mohsin Raza; Ikram UI Haq; Waqar ul Hassan; Jun-Liang Guo; Hong-Na Zhang; Xiao-Bin Li; Yue Wang; Wei-Hua Cai; Shu-Qi Meng; Fang Chen; Yu-Long Mao; Feng-Chen Li (Annals of Nuclear Energy, 2026)

Discovery and engineering of a new BvCas12a nuclease for mammalian genome editing and nucleic acid detection - Xuechun Shen; Lei Huang; Dan Wang; Chen Qi; Baitao Li; Chuan Liu; Ke Chen; Yuanqiang Zou; Liang Xiao; Yuan Jiang; Qiupeng Lin; Hongxia Lan; et al. (Science China Life Sciences, 2026)

Antimicrobial polyketides from an endophytic fungus Arcopilus aureus HJ-7 from Ardisia mamillata Hance - Li-Qi Liang; Xian-Hua He; Chun-Yan Wei; Jing-Xian Zhao; Qian Wu; Min Liang; Jun Li; Yan Luo; Wei-Feng Xu; Rui-Yun Yang (Natural Product Research, 2026)

Comparative analysis of chemical composition in Zanthoxylum avicennae leaves and branches based on UPLC-Q-Orbitrap HRMS, and evaluation of their antioxidant activities - Liang-Qian Zhang; Yuan Tian; Li-Ping Dai; Xing-Er Ye; Yi-Qin Zheng; Nan-Chen Lai; Wei Dai; Qi Wang (Natural Product Research, 2026)

Mitochondrial dysfunction and programmed cell death mediate berry abscission - Yizhou Xiang; Ming Qi; Qiannan Hu; Zhenchang Liang; Li Li (Postharvest Biology and Technology, 2026)

Vertical sediment stratification regulates dissolved nutrient dynamics and interface fluxes along the intertidal zone - Zhenyang Li; Yueqi Wang; Yashu Qi; Kai Xiao; Guangxuan Han; Hailong Li; Liang Liu; Dejuan Jiang; Xiaoying Zhang; Chunmiao Zheng (Journal of Hydrology, 2026)

Treatment performance and mechanism of source-separated blackwater using an earthworm-based reactor for rural applications - Le Zhong; Guang-Feng Liu; Shi-Chao Liang; Jie Ding; Han-Jun Sun; Ding-Ding Tang; Yan Zhou; Xiong Qin; Ji-Wei Pang; Yan Li; Nan-Qi Ren; Shan-Shan Yang (Journal of Environmental Management, 2026)

Vegetation-soil-soil microbes dominate ecosystem multifunctionality in typical grasslands of the core Sanjiangyuan region on the qinghai-tibet plateau - Xin Chen; Qi Li; Dongdong Chen; Chengkai Lin; Shuyang Wen; Liang Zhao (Journal of Environmental Management, 2026)

Sustainable production of V3.5 + electrolyte for vanadium redox flow batteries via thermal reduction of ammonium metavanadate - Feifei Hu; Zhiqiang Liu; Hao Du; Baohua Wang; Jian Qi; Liang Zhao; Shaona Wang; Lanjie Li (Journal of Environmental Chemical Engineering, 2026)

Techno-economic and environmental analysis of coal-to-olefin integrated with nature gas co-gasification and green hydrogen - Jinqiang Liang; Wei Ren; Qi Zhang; Jiahui Li; Danzhu Liu; Mao Ye (Fuel, 2026)

Experimental and numerical simulation study on high gravity regeneration equipment with new built-in reboiler - Qi Nie; Jianlu Zhu; Liang Hao; Jiatao Fan; Yuxing Li (Fuel, 2026)

Computational design of a highly active and stable alkaline pectate lyase: Unraveling the molecular mechanisms for superior performance - Mei Zhao; Haoyang Li; Jiaojiao Chen; Xiaohao Zhang; Xiaohong Pan; Lei Sun; Liang Guo; Xianghui Qi (Food Research International, 2026)

Curcumin-loaded composite nanoparticles from aggregated insoluble soybean protein hydrolysate and soluble soybean polysaccharide: Fabrication, characterization, and application in stabilizing W/O/W Pickering emulsions - Zheng Xu; Zhiyu Jia; Meiyun Li; Zhixian Xin; Xuhui Yang; Shizhang Yan; Jingwen Xu; Liang Cao; Baokun Qi (Food Chemistry, 2026)

Aroma in ‘Munage’ Grape Spirits response to different inoculation strategies of H. uvarum/P. fermentans in mixed fermentation with S. cerevisiae - Jia-Qi Wang; Jia-Liang Hu; Qian-Qian Feng; Yang Zhang; Hong-Yan Zhang; Su-Fang Zhang; Yun-Kui Li; Hua-Feng Yang; Guo-Jie Jin (Food Bioscience, 2026)

Enhanced metal-organic framework-driven deep learning-assisted magnetic crystal paper aptsensor for two-step sensitization and in-situ detection of pathogenic bacteria - Lulu Cao; Yuwei Ren; Shengshi Jiang; Hui Li; Maoling Hu; Xin Zhang; Xiaoyu Yu; Weichao Wu; Mengyu Li; Zhao Liang; Na Ling; Hongzhou Chen; et al. (Chemical Engineering Journal, 2026)

Boosting CO2 capture via microwave assistance with Fe3C–Doped Fe–Nx carbon foam - Zhengwei Liang; Lei Xing; Shuaiqi Wang; Jingxiang Zhang; Tieyue Qi; Qiangwei Li; Lidong Wang; Hongqi Jiang; Qiang Jing (Chemical Engineering Journal, 2026)

Interactions of carbon‑nitrogen coupling in the Agro-Pastoral Ecotone of Northern China - Shijun Tu; Wanfa Wang; Cai Li; Yuanbi Yi; Jinfeng Ge; Wenrui Yao; Wenhong Shi; Fu-Jun Yue; Zhongjun Wang; Yulin Qi; Si-Liang Li (CATENA, 2026)

Sustainable treatment of acetaminophen wastewater with simultaneous water recovery and energy generation in osmotic microbial fuel cells - Xin Ning; Shilong Li; Yanyan Jia; Qiusheng Gao; Lin Qi; Liang Duan (Bioresource Technology, 2026)

Determining the Biological Zero and Effective Accumulated Temperature for Gonadal Development in Diploid and Tetraploid Pacific Oysters, Crassostrea gigas - Geng Cheng; Jianmin Zhou; Yuanxin Liang; Wenlong Bi; Chengxun Xu; Qi Li (Journal of Ocean University of China, 2026)

The GATA3-RFPL3-ASK1 axis suppresses breast cancer growth and lung metastasis - Kang Li; Chang Liu; Jun-Hui Yin; Yu-Ting He; Zhi-Zhi Xu; Wen-Jing Zhang; Jian-Qi Wang; Lu-Yao Hou; Jing Feng; Le-Min Lin; Xiu-Qing Duan; Yi Zhou; et al. (Apoptosis, 2026)

Phosphogypsum and cadmium remediation agents: A synergy for mitigating Cd contamination and CH4 emissions in rice paddies - Wangbiao Lu; Chengling Huang; Weijun Luo; Qi Zhang; Xu Huang; Yongcheng Jin; Chen Yao; Xiaowen Li; Guangneng Zeng; Fang Yang; Liang Tang; Shi-Jie Wang (Acta Geochimica, 2026)

Design of robot navigation system under spatial constraints in shiitake mushroom fruiting room - Hualu Song; Kangkang Qi; Wenjie Feng; Yuanjie Mu; Jun Li; Xiangyu Lv; Zhichao Liang; Fengyun Wang (Computers and Electronics in Agriculture, 2026)

High breeding potential for growth exists in normal, black, and golden shell lines of tetraploid Fujian oyster revealed through three generations of mass selection - Yuanxin Liang; Qi Li; Xianchao Bai; Geng Cheng; Jianmin Zhou; Rui Xu; Fanzhi Chu; Zhiyang Cui; Chengxun Xu; Wenshu Luo (Aquaculture, 2026)

Diversity loss of soil microbiome stimulates soil carbon emissions - Haibo Pan; Yingyi Fu; Hairong Tu; Yongxing Cui; Beibei Chen; Jiejun Qi; Ziheng Peng; Shi Chen; Chunling Liang; Jiai Liu; Xiaomeng Li; Min Gao; et al. (Soil Biology and Biochemistry, 2026)

Ecological and functional diversity of sulfur-oxidizing and sulfate-reducing bacteria in Chinese mangrove ecosystems: A comparative review with insights from Guangxi Beihai - Muhammad Kashif; Qi Liang; Can Meng; Tingmei Li; Yujia Luo; Feng Guo; Dan Wang; Chengjian Jiang (Rhizosphere, 2026)

Synergistic regulation of calcium hydroxide and ARC microbial inoculant on rhizosphere microbiota and soil chemical properties during peanut middle growth stages in acidic red soils - Gongming Wu; Hong Yu; Ningbo Zeng; Zinan Luo; Sheng Gao; Qi Liang; Lin Li; Peiwu Li; Zemao Yang; Dengwang Liu (Rhizosphere, 2026)

Integrating SDGSAT-1 glimmer imagery with Sentinel-1/2 data for high-resolution building height estimation - Zilu Li; Huadong Guo; Linlin Lu; Yifang Ban; Qi Zhu; Dong Liang (Remote Sensing of Environment, 2026)

Two kinesin-12 class proteins are involved in post-cytokinetic membrane trafficking required for auxin responses in Arabidopsis - Wencai Qi; Xiaoru Li; Yuqin Sun; Aiyu Guo; Peipei Zhang; Liang Zhang (Plant Science, 2026)

Collapse mechanism and failure criteria of offshore monopile wind turbine towers under coupled typhoon and strong earthquake effects in the eyewall region - Yifan Qi; Shitang Ke; Ke Liang; Hao Li; Jingzhu Mao; Xingyu Zhang; Qi Liu (Ocean Engineering, 2026)

Posttranslational regulation of TOR kinase activity controls resource allocation between plant growth and immunity in Arabidopsis - Jianwei Li; Ran Wang; Chenying Li; Xijie Guo; Qinghong Li; Zhixuan Wu; Shanshan Zeng; Fan Qi; Yuchen Wang; Zhiyi Jia; Weiwei Yu; Zeming Huang; et al. (Molecular Plant, 2026)

Sevoflurane aggravated neuroinflammation and oxidative stress in neonatal mice by modulating microglia phenotype via circRNA2092/miR-873a-5p/KEAP1 - Yanan Li; Juan Du; Jiajie Zhang; Zhenzhen Cai; Lei Shi; Jia Liang; Qi Zhang (NeuroToxicology, 2026)

Production of peptide-calcium chelates from eggshell membranes: A comparison of high-pressure homogenization versus enzymatic hydrolysis - Ye Qi; Shenwan Wang; Zhaomeng Li; Xiang Yan; Yan Yang; Bin Li; Hongshan Liang (Food Research International, 2026)

Chemical aggregation of carbonyl compounds as the core contributor to chromatic alterations in jiangxiangxing baijiu aging - Zhisong Wang; Qi Chen; Chuanchuan Gao; Xiaogang Zhang; Liang Zhou; Huan Wang; Yi Luo; Cuimei Zhao; Jiangxue Han; Yan Li (Food Chemistry, 2026)

Five years of re-ploughing of grass cultivation (Elymus nutans) in the eastern Qinghai-Xizang Plateau proves to management measure: An eddy covariance-based analysis - Fuquan He; Dongdong Chen; Qi Li; Caiyun Luo; Yukun Zhang; Li Zhang; Zongjian Zhao; Liang Zhao (Field Crops Research, 2026)

circSCAP-encoded SCAP-129aa mediates platinum resistance in triple-negative breast cancer via the PI3K/AKT pathway - Qi Wang; Yudong Li; Zhuangqiu Yang; Wang Yang; Yujie Liu; Liang Jin; Shunying Li; Qianfeng Shi; Zijie Cai; Yiye Ouyang; Mengzi Wu; Ruiquan Liu; et al. (Science China Life Sciences, 2026)

Combined Straw Return and Organic Fertilizer Increases Soil Quality in Low-SOC Soils: Evidence from a Soil Quality Assessment - Guanjun Li; Zhi Ma; Ze Zhang; Qi Zhao; Chaoyun Ying; Shuang Wang; Liang Wei; Cuiyan Wu (Journal of Soil Science and Plant Nutrition, 2026)

The emerging role of fatty acids as key bioactive components of Ganoderma lucidum spore oil in alleviating tumor progression - Qi-Jun Chen; Zi-Xuan Li; Guo-Cai Wang; Ting Xie; Guan-Di Xiao; Hui Xu; Jing Li; Xiang Luo; Yi-Fang Li; Lei Liang; Ju-Yan Liu; Yan-Ping Wu; et al. (Journal of Natural Medicines, 2026)

The interplay between antihypertensive medication and lifestyle with cardiovascular outcomes in patients with hypertension: the PURE-China study - Biyan Wang; Zhiguang Liu; Tong Bu; Sumathy Rangarajan; Qiuyan Ma; Xiaocong Li; Qi Qiu; Yang Lin; Lap Ah Tse; Bo Hu; Salim Yusuf; Qiujing Cai; et al. (EPMA Journal, 2026)

Developmental trajectories of reading and neural substrates: a lifespan perspective on Chinese reading - Qianting Cheng; Hengyu Mao; Xinyang Liu; Xitong Liang; Yongbin Wei; Ting Qi; Li Liu (Brain Structure and Function, 2026)

PRSGNet: A robust framework for crop row detection in complex field scenarios - Dengbin Fu; Yinghu Cai; Zhanpeng Liang; Zhenyu Tang; Zhiqiang Yao; Hao Gong; Renjun Hu; Jiating Li; Long Qi (Computers and Electronics in Agriculture, 2026)

Photochemical transformation of dissolved organic matter: source, particulate matter interaction and disinfection byproduct formation potential - Dapeng Guo; Ruochun Zhang; Huiying Ma; Hao Zhang; Zekun Zhang; Yulin Qi; Peizhe Sun; Ding He; Si-Liang Li (Water Research, 2026)

Daily Arctic first-year sea ice thickness observed by China’s GNSS-R satellite constellation - Yuan Li; Lei Zheng; Qi Liang; Teng Li; Chuyue Peng; Lian He; Qiuyang Zhao; Zhuoqi Chen; Qi Tang; Ying Li; Beibei Liang; Shengli Wu; et al. (Science Bulletin, 2026)

Bombyx mori RPS3 participates in the UV damage repair of Bombyx mori nucleopolyhedrovirus by interacting with Bm65 - Qi Tang; Jiayin Huang; Qiannan Su; Guohui Li; Feifei Zhu; Qian Yu; Lindan Sun; Huiqing Chen; Liang Chen; Shangshang Ma; Xiaoyong Liu; Keping Chen (Pesticide Biochemistry and Physiology, 2026)

Numerical investigation on wave conversion performance of a wave-powered vertical profiler - Yan Liu; Haolei Li; Zhanfeng Qi; Xuanyu Chen; Zhiyuan Shang; Ziwen Xing; Liang Cheng (Ocean Engineering, 2026)

The preferential fractionation of dissolved organic matter (DOM) by co-precipitation with iron in diverse environmental conditions - Tingcang Hu; Chunmei Chen; Yulin Qi; Pingqing Fu; Si-Liang Li (Journal of Hydrology, 2026)

Amidoxime-modified PAN@Ce-UiO-66 nanocomposite fiber membrane for efficient removal of Cr(Ⅵ) from water - Yongzhang Qi; Hao Liang; Hebing Pei; Simin He; Hui Zhang; Shijing Li; Shikai Yu; Ruibin Guo; Nijuan Liu; Zunli Mo (Journal of Environmental Chemical Engineering, 2026)

Impact of pitaya peel powder particle size on bread quality and functional properties: a sustainable strategy for agro-industrial waste upcycling - Ying Chen; Qi Li; Zhen-Yang Quan; Wen Liu; Lunan Guo; Liang Zhang; Linghan Meng; Xiaojuan Xu; Jian-Ya Qian (Food Chemistry, 2026)

Hydration-driven structural engineering via enzymatic glycation: Sustained quercetin release in pullulan-zein coatings for extended walnut preservation - Zi-han Wang; Xue-li Liu; Rui-qi Sun; Bin Qi; Jun-xia Xia; Da-yong Zhou; Liang Song (Food Hydrocolloids, 2026)

Oil-in-water emulsions stabilized by hollow particles of zein and whey protein: Particle integrity, interfacial structure and interfacial adsorption - Kaiwen Chen; Qianqian Shen; Bohua Zhang; Shuning Zhang; Qi Fan; Gong Chen; Li Liang (Food Hydrocolloids, 2026)

Flexible and compressible thermoelectric foam for temperature–pressure dual sensor - Po-Shen Lin; Meng Li; Yong-Qi Chen; Bo-Xuan Hu; Cheng-Liang Liu; Zhi-Gang Chen (Chemical Engineering Journal, 2026)

A phytoalexin-inspired, natural product-based marine antifouling coating with synergistic active antimicrobial and passive anti-adhesive performances - Liang Ma; Xing-Yu Lei; Qi Xu; Ya-Fu Li; Yu-Hao Li; Peng-Fei Chen; Jian-Cai Chen; Hui-Jing Li; Yan-Chao Wu (Chemical Engineering Journal, 2026)

Cadmium exposure impaired the uterine decidualization through inducing the imbalance of mitochondrial fusion and fission - Yin-Fei Xing; Liang Yue; Chen-Hao Wang; Cai-Jiao Zhou; Jia-Qi Ye; Shi-Jie Li; Bin Guo (Chemico-Biological Interactions, 2026)

Correction to: Morphology-based genetic diversity analysis reveals introgressive hybridizations obscure species boundaries of three wild roses endemic to Taiwan Island - Cheng Zhang; Shi-Qi Li; Liang-Ying Li; Xin-Fen Gao (Horticulture, Environment, and Biotechnology, 2026)

Multiple Regression and Path Analysis of Morphological, Weight, and Fecundity Traits of Diploid and Tetraploid Pacific Oyster, Crassostrea gigas - Geng Cheng; Hong Hu; Yuanxin Liang; Wenlong Bi; Chengxun Xu; Haijun Liu; Qi Li (Journal of Ocean University of China, 2026)

EBV-miR-BART14-3p Targets LACTB to Enhance Gastric Cancer Cell Proliferation and Migration - Xiaomin Huang; Xuhui Zhao; Yujiao Qi; Tian Lan; Ruiling Wang; Shuang Liang; Yuxiu Ma; Cuixia Di; Hongling Li (Biochemical Genetics, 2026)

LncRNA AC098613.1 promotes acute myeloid leukemia cell differentiation through CDC5L/ADAP1/NRD1 axis - Qingling Jiang; Xiaoting Wang; Hang Yao; Jince Wang; Peiyu Tang; Mingpeng Liang; Zhaohai Pan; Bohan Li; Chunhua Lin; Qinxuan Wu; Qi Wang; Qiusheng Zheng; et al. (Apoptosis, 2026)

The promoter sequence of (-)-limonene synthase in Mentha Canadensis and its strong activity in the glandular trichome and in the stomatal guard cells - Shumin Li; Zhichao Xue; Taolan Xiao; Xiwu Qi; Hailing Fang; Li Li; Yang Bai; Dongmei Liu; Qun Liu; Zequn Chen; Xu Yu; Chengyuan Liang (Acta Physiologiae Plantarum, 2026)

Rainfall shapes CO₂ emission and dissolved organic matter dynamics in a karst catchment: Controlling factors revealed by isotopic and molecular signatures - Jinfeng Ge; Yulin Qi; Yuanbi Yi; Chao Ma; Wenrui Yao; Xin Liu; Haoyang Wang; Keyan Li; Fu-Jun Yue; Tao Peng; Si-Liang Li (Water Research, 2026)

The impact of biodegradable microplastics on soil aggregate stability across different afforestation ages and soil depths in poplar shelterbelts - Kaitao Jia; Mengfei Tian; Jiaying Liu; Xinle Li; Kaijia Xue; Yujiao Song; Qi Liang; Chunjian Zhao; Chunying Li (Waste Management, 2026)

The appearance of microblade technology at the onset of Marine Isotope Stage 2 in Northeast China - Wei Liu; Jian-Ping Yue; You-Qian Li; Ke-Liang Zhao; Si-Qi Lu; Guang-Yi Bai; Yang Liu; Yu-Xiu Zhang; Shi-Xia Yang (Quaternary Science Reviews, 2026)

Experimental investigation on the motion responses of a moored outfitting ship with and without pontoons under extreme conditions - Zhangjian Wang; Lin Qi; Mingxiao Liang; Junzheng Li; Zihan Liu; Yuxiang Ma; Congfang Ai (Ocean Engineering, 2026)

The biomarker signatures in the Niujiaotang sulfide ore field: Exploring the role of organic matter in ore formation - Yong Cheng; Jia-Xi Zhou; Yuzhao Hu; Saihua Xu; Shengbao Shi; Yiming Wen; Qi Nie; Ye Zhou; Kai Luo; Xiaolin Tan; Liang Zhou; Yadong Li; et al. (Marine and Petroleum Geology, 2026)

Curcumin-mediated photodynamic action disturbs TOM70-depedent MIC60 import to damage mitonchondria against breast cancer - Xiang-Yi Zhao; Min Yan; Liang Zheng; Chang-Long Gou; Qi Huang; Liu-Gen Li; Xin-Ran Yu; Jing-Yu Lu; Cui Hu; Si-Han Zhang; Cunqing Kong; Fan Leng; et al. (Journal of Photochemistry and Photobiology B: Biology, 2026)

Mono(2-ethylhexyl) phthalate activates JNK signaling via TLR4-MD2 binding to induce podocyte injury in chronic kidney disease - Jiajun Jing; Shaohui Liu; Li Yan; Li'e Zhang; Qiuju Liang; Yuting Wen; Xiaofeng Huang; Zijuan Qi; Mingjun Wang; Zi'ang Huang; Sijin Liu; Yunfeng Zou; et al. (Journal of Hazardous Materials, 2026)

Mechanistic insight into curcumin-induced conjugative plasmid transfer acceleration: Role of intracellular arginine uptake - Min-ge Wang; Kai-di Liu; Wen-jie Jin; Run-bo Li; Jun-qi Liu; Liang-xing Fang; Jian Sun; Xiao-ping Liao (Food Microbiology, 2026)

A dual-functional zinc based porous scaffold to promote osteogenesis and inhibit infection by an ultra-hydrophilic coating enriched with magnesium - Zhenbao Zhang; Aobo Liu; Yijie Liang; Jiabao Dai; Haixia Li; Yuhan Qi; Jing Xu; Manxi Li; Yantao Zhao; Peng Wen; Yanfeng Li (Chemical Engineering Journal, 2026)

Corrigendum to “Wear particles-induced periprosthetic osteolysis from a new perspective based on single-cell RNA-seq: crosstalk of osteoblast PANoptosis and macrophage efferocytosis in osteoimmunology microenvironment” [Chem. Eng. J. Volume 515, 1 July 2025, 163509/CEJ-D-25-01484R1] - Jia-xuan Li; Jian-ping Wen; Shuan-ji Ou; Yu-dun Qu; Chang-liang Xia; Wen-jun Li; Yang Yang; Jia bao Liu; Rong-shen Yang; Wei Zeng; Wei Zhang; Yun-fei Ma; et al. (Chemical Engineering Journal, 2026)

Early Rehabilitation Exercise Promotes Vestibular Compensation in UVN Mice by Regulating Microglial Polarization Balance via the PGC-1α/FNDC5/BDNF Pathway - Junyu Wu; Zhihui Zheng; Gengxin Lu; Junjie Guo; Minping Li; Dongxiao Zhou; Xiaoqiu Liang; Weiwei Qi; Xue Xu; Zhezhi Deng; Haiwei Huang (Molecular Neurobiology, 2026)

Oral Administrations of Short-Chain Fatty Acids or Probiotics Extend the Survival Times and Mitigate the Neuropathological Damages in the Scrapie-Infected Hamsters - Yuan Wang; Dong-Lin Liang; Run-Dong Cao; Ruhan A.; Jia-Feng Zeng; Bing Xu; Ju-Zheng Li; Wei-Wei Zhang; Li-Ping Gao; Kang Xiao; Xiao-Ping Dong; Qi Shi (Molecular Neurobiology, 2026)

Decoupled Stability of Above‐ and Belowground Productivity Across Global Change Drivers - Ze Zhang; Hongyan Liu; Zidong Li; Boyi Liang; Jinghua Qi; Jiamei Li; Yann Hautier (Global Change Biology, 2026)
Grassland ecosystems play essential roles in global carbon cycling and biodiversity conservation, yet it remains unclear whether belowground productivity is less sensitive to environmental change than aboveground productivity. Previous studies have predominantly focused on aboveground net primary productivity (ANPP) stability, potentially overestimating ecosystem vulnerability by neglecting critical belowground processes. By synthesizing 1513 observations from 113 studies across 85 grassland ecosystems worldwide, we quantified the responses of productivity, temporal stability, and carbon allocation to nine global change drivers, including nutrient enrichment, altered precipitation, elevated CO 2 , warming, mowing, and grazing. Our results reveal that belowground net primary productivity (BNPP) stability shows generally weaker responses to global change drivers than ANPP stability. In addition, variation in ANPP stability was most closely associated with broad‐scale climatic indices of water supply (precipitation and aridity, used here as proxies for plant‐available soil water), whereas BNPP stability was more closely associated with edaphic context (soil moisture‐related and fertility‐related properties). These distinct patterns suggest that broad‐scale climatic variability is more strongly reflected in aboveground stability, whereas belowground stability is better captured by edaphic predictors related to water retention and nutrient availability. Moreover, variation in belowground carbon allocation was consistently associated with stronger coordination between above‐ and belowground responses and with the maintenance of BNPP stability under global‐change perturbations, suggesting a potential allocation‐related pathway linked to ecosystem resistance. Our findings challenge traditional ecological theories emphasizing unified above‐belowground responses and suggest that previous research focusing solely on aboveground processes may have overestimated grassland vulnerability. This synthesis provides critical insights for predicting grassland ecosystem stability and functioning under ongoing global environmental changes.

Ecological functions coupled with plasmid and phage-mediated dissemination drive the global prevalence of high-risk antimicrobial resistance genes in influent - Fang Huang; Shu-Hong Gao; Yanmei Zhao; Qi Liu; Rui Gao; Zihan Dai; Jingni Xie; Bin Liang; Jinsong Liang; Lu Fan; Xin Li; Ai-Jie Wang (Water Research, 2025)

Chi-miR-146a promotes the propagation of Neospora caninum by targeting the TGF-β1/SMAD2 pathway - Jin-Ming Chen; Jing-Yu Li; Jia-Yi Jin; Xiao-Qi Bao; De-Liang Tao; Xiao-Yun Zhao; Jun-Ke Song; Xin Yang; Ying-Ying Fan; Guang-Hui Zhao (Veterinary Parasitology, 2025)

Precise measurements of the cosmic ray proton energy spectrum in the “knee” region - Zhen Cao; F. Aharonian; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; C.M. Cai; W.Y. Cao; Zhe Cao; et al. (Science Bulletin, 2025)

In-situ mineral carbonation of ultramafic tailings for carbon dioxide removal: A critical review - Xiangyang Lu; Liang Xu; Xiaochun Li; Yunlu Hou; Quan Chen; Qi Li (Process Safety and Environmental Protection, 2025)

Greenland supraglacial lakes albedo-depth parameterization from multi-source remote sensing: An application of lake-albedo feedback modeling - Jiake Wu; Lei Zheng; Zhuoqi Chen; Quan Zhou; Chuyue Peng; Qi Liang; Teng Li; Baojuan Huai; Weijun Sun; Xiao Cheng; Robert Law; Fengming Hui (Journal of Hydrology, 2025)

Recent advances in CO selective catalytic reduction technology: Catalyst reaction mechanisms and antitoxic strategies research - Zijing Liang; Silan Li; Qian Yang; Xinrui Li; Liqiang Qi (Journal of Environmental Chemical Engineering, 2025)

Multiscale mechanism-based and performance assessment of green dust control in open-pit coal mines via a dual-fiber interpenetrating network hydrogel suppressant - Feng Li; Changbo Du; Bing Liang; Fu Yi; Jian jun Guo; Qi Sun; Xilin Li (Journal of Environmental Chemical Engineering, 2025)

Identifying conservation gaps and proposing climate-smart strategies for amphibians and reptiles on the Qinghai-Tibet Plateau - Lu-Lu Sui; Zhong-Yi Yao; Shun Ma; Sheng-Chao Shi; Xiu-Dong Shi; Li-Wen Liang; Song Tan; Jie Wang; Bo Cai; Feng Xie; Jing-Feng Chen; Bin Wang; et al. (Journal of Environmental Management, 2025)

Phosphorus recovery using biochar for beryllium removal: Experimental evaluation and performance prediction via machine learning - Zipeng Zhang; Pengyan Zhang; Chong Liu; Fayong Li; Qi Yang; Xinqiang Liang (Journal of Environmental Chemical Engineering, 2025)

Application of microbial electrolysis cells in enrichment of anammox bacteria - Qi Gao; Liang Fu; Jing Wei; Xiao-Chun Wang; Xiang Xiao; Yang-Yang Yu; Liang Cheng; Yu-Hao Qiu; Shan-Wei Li (Journal of Environmental Chemical Engineering, 2025)

Bioinspired tetracycline absorbent based on waste cotton fabric and leaf-like zeolitic imidazolate frameworks - Qing Jiang; Tengfei Qi; Yuhao Liang; Wenjuan Li; Hongbo Lu; Peng Cui; Wentao Hao; Wen Yang (Journal of Environmental Chemical Engineering, 2025)

Graphite decorated Pt/α-Fe2O3 composite with outstanding CO oxidation performance in the presence of SO2 and moisture - Xinru Qi; Xiaoxuan Fan; Liang Li (Journal of Environmental Chemical Engineering, 2025)

Comparative study on the in vitro digestion characteristics and cholesterol-lowering function of soybean protein isolate and three storage proteins - Ziyi Zhao; Jiahui Liang; Hanyu Song; Yang Li; Shizhang Yan; Baokun Qi (Food Bioscience, 2025)

Protein enzymatic hydrolysate from sea cucumber intestine-ovum (SCIOH) boosts exercise endurance and mitigates oxidative stress in mice by modulating gut microbiota - Yuxiao Zhou; Shuchang Guo; Baoying Qi; Meng Li; Baoling Su; Tianzhu Liang; Zhenyang Zhang; Huan Yan; Qiuyu Wang; Lili Jin (Food Bioscience, 2025)

Multifunctional SIS-PEG-AC bio-patch with enhanced adhesion, sustained anti-inflammatory activity, and regenerative properties to promote lung repair - Heng Li; Deguang Wang; Zixun Wang; Wenjie Chen; Yuxin Guo; Han Liang; Yanqiu Zhao; Qi Wang; Yiqian Huang; Wei Jing; Pengfei Wei; Bo Zhao; et al. (Chemical Engineering Journal, 2025)

Crystal structure-dependent ammonium-ion storage mechanisms in nanostructured MnO2 polymorphs - Jingang Wu; Binbin Wei; Quanxing Guo; Haojun Zeng; Xin Liu; Qiaoyan Chen; Xutao Yan; Yuechan Li; Qi-Yuan Fan; Zhengbing Qi; Hanfeng Liang (Chemical Engineering Journal, 2025)

Efficient degradation of pollutants under high-salinity conditions dominated by non-radical pathways and its application - Mingyang Xu; Liang Zhang; Hui Li; Shengjun Yang; Chenxi Guo; Yinglong Wang; Jianguang Qi; Fengbin Zheng; Fanqing Meng (Chemical Engineering Journal, 2025)

From waste to value: Scalable, one-pot upcycling of PET into high-performance copolyesters via hydroxy transesterification - Weiqi Chen; Han Hu; Li Cai; Hanxu Zhu; Qingyang Luan; Qi Jiang; Peng Liang; Jie Feng; Jinggang Wang; Jin Zhu (Chemical Engineering Journal, 2025)

Structural characterization and oxidative stress modulation activity of an acidic Heteropolysaccharide from Microctis folium - Xiao-lu Liang; Yu-wen Liang; Jing Tian; Fei-fan Mo; Tian-ming Pan; Yan-feng Chen; Xiao-qi Shao; Kun-Ping Li (Carbohydrate Polymers, 2025)

Skeletal and sedimentary structures in yardang caverns in the Mars analog, Qaidam Basin: origin and implication - Qi-Tao Hu; Wen-Ping Liu; Yu-Lu Xue; Qi-Zhi Yao; Sheng-Quan Fu; Yi-Liang Li; Gen-Tao Zhou (CATENA, 2025)

Copalyl diphosphate synthase gene TaCPS1 mediated resistance to Fusarium graminearum in wheat in response to Piriformospora indica colonization - Liang Li; Fuyan Qi; Ruiying Hao (Theoretical and Applied Genetics, 2025)

Decades’ progress and prospects on maize functional genomics and molecular breeding - Qing Li; Jinsheng Lai; Jian Chen; Lin Li; Weibin Song; Beibei Xin; Hainan Zhao; Yingjie Xiao; Feng Tian; Gang Li; Yameng Liang; Lei Liu; et al. (Science China Life Sciences, 2025)

The African Swine Fever Virus pH108R Protein Negatively Regulates Innate Immune Response by Inhibiting NF-κB Activation - Enping Liu; Zehui Li; Xifang Zhu; Jingming Zhou; Hongliang Liu; Chao Liang; Yumei Chen; Yanhua Qi; Aiping Wang (Current Microbiology, 2025)

Global distribution, genesis, and enrichment characteristics of high-concentration natural hydrogen - Yufei Liang; Qingqiang Meng; Xiaowei Huang; Wang Lu; Yongbo Wei; Jiayi Liu; Yuan Zhou; Lei Huang; Qi Li; Jiahui Chen; Dongsheng Zhou (Frontiers in Marine Science, 2025)
Under the global decarbonization initiative, natural hydrogen has garnered significant attention as a green, high-calorific-value, zero-carbon emission clean energy source in marine and continental contexts. Previous research on natural hydrogen systems remains nascent. This study systematically synthesized the distribution characteristics, genetic mechanisms, and enrichment processes of high-concentration natural hydrogen globally, yielding four key insights: (1) Natural hydrogen originates from complex processes broadly categorized as organic and inorganic, predominantly including deep-Earth degassing, water-rock reactions, and radiolysis of water. (2) Hydrogen-rich accumulations exhibit widespread distribution, primarily occurring in rift systems, plate collision zones, subduction zones and their peripheries, as well as Precambrian iron-rich formations. (3) Natural hydrogen reservoirs form through dynamic accumulation processes requiring: high-quality source supply, favorable migration pathways and preservation conditions, and sustained influx exceeding leakage rates. (4) Favorable exploration targets should avoid microbial active zones and deep hydrogenation/hydrocarbon generation regions; current evidence suggests promising reservoirs occur in ultra-deep settings, peripheral areas of convergent zones, and shallow strata proximal to deep-seated faults. Exploration of natural hydrogen should prioritize evaluating the hydrogen anomalies to identify potential reservoirs and advance systematic comprehension of this emerging energy play.

Distribution, sources, and health risks of PM2.5 and PM1-bound polycyclic aromatic hydrocarbons in the Pearl River Delta - Guang-Hong Zhai; Yue Wen; Mo Yang; Qi-Zhen Wu; Wan-Ting He; Li-Xia Liang; Le-Bing Wang; Yun-Ting Zhang; Jing-Wen Huang; Jia-Xin Zhou; Min Li; Gao Meng; et al. (Environmental Monitoring and Assessment, 2025)

Global epidemiology and genomic perspectives on vancomycin-resistant Enterococcus faecium: Rising antimicrobial resistance and transmission risks within the one health framework - Xiangyu Yu; Zhaorong Yu; Liang Huang; Shumei Li; Qingwei Chen; Dan Xu; Zhao Qi (Science of The Total Environment, 2025)

Bifidobacterium animalis subsp. Lactis A6 alleviates comorbid constipation and depression by rebalancing tryptophan metabolism - Jian Wang; Yimei Ren; Juan Chen; Shanbin Chen; Xiaoxia Li; Jianwen Chen; Xifan Wang; Lijun Li; Liang Zhao; Yixuan Li; Qi Zhang; Wei Xiong; et al. (Science Bulletin, 2025)

Selective interaction of BmNPV Bm65 with host proteins before and after ultraviolet radiation - Yutong Liu; Jiayin Huang; Guohui Li; Feifei Zhu; Qian Yu; Lindan Sun; Huiqing Chen; Liang Chen; Qi Ge; Shangshang Ma; Xiaoyong Liu; Keping Chen; et al. (Pesticide Biochemistry and Physiology, 2025)

Stover return enhances the transformation and sequestration of photosynthetic carbon through regulating soil food web - Yijia Tian; Xinchang Kou; Tingting An; Liangjie Sun; Qi Li; Wenju Liang; Xiaoke Zhang (Journal of Cleaner Production, 2025)

Horizontally transferred NADAR genes contribute to immune defense of ladybird beetles against bacterial infection - Kun-Yu Yang; Yi-Fei Sun; Yuan-Sen Liang; Hao Li; Meng-Xue Qi; Zhaowei Wang; Luis Carlos Ramos Aguila; Li-Qun Cai; Hao-Sen Li; Hong Pang (Insect Biochemistry and Molecular Biology, 2025)

Safety and recyclability of active polyethylene terephthalate bottles: A comprehensive assessment using non-target screening and visual sensory evaluation - Can Xu; Sheng Chen; Qi-zhi Su; Jinxin Liang; Ying Zeng; Anqi Cui; Hanke Li; Ben Dong; Dan Li; Huai-ning Zhong (Food Chemistry, 2025)

Comprehensive analysis of microbial communities, metabolites, and biogenic amines in bagged fermented chili paste at varying salt levels - Wei-Qin Deng; Zhen-Ming Lu; Ze-Liang Wang; Si-Qiang Jiang; Xiong-Bo Li; Zhi-Yi Fan; Xiao-Juan Zhang; Li-Juan Chai; Qi-Sheng Zhang; Jin-Song Shi; Gong Chen; Zheng-Hong Xu (Food Bioscience, 2025)

When AI meets AIE: Machine learning in design function-oriented AIEgens for antibacterial ability - Leina Dou; Penghui Zhou; Fei Qi; Qing Li; Yuchen Bai; Liang Luo; Kai Wen; Wenbo Yu; Xuezhi Yu; Jianzhong Shen; Zhanhui Wang (Chemical Engineering Journal, 2025)

Novel pyrene-based metal-organic framework nanosheets' metal ions directly serve as coreaction accelerators to boost their electrochemiluminescence performance for fabricating supersensitive biosensor - Qiu-Yi Peng; Qiu-Yue Li; Yang Yang; Jun-Qi Song; Bing-Ling Yu; Wen-Bin Liang; Yan Li; Ruo Yuan; Dong-Rong Xiao (Chemical Engineering Journal, 2025)

Dipyridinium salt-enhanced type II ROS photodynamic antibacterial nanofiber films for long-term preservation of blueberries - Xue-Qi Zhang; Xiuxian Zhu; Fei Guo; Zi-Ming Zhou; Yu-Ting Zhao; Lin-Xuan Song; Zhao-Yang Zhi; Zi-Hui Liang; Zhen-Ke Li; Chang-Hai Yi; Zhen Wang (Chemical Engineering Journal, 2025)

Multifunctional hierarchical BN/MXene-Fe3O4 aerogel for efficient thermal management and ultra-broadband microwave absorption - Xin-Miao Liang; Qi-Fan Xuan; Hong-Hao Li; Peijia Ding; Yu Zhang; Martin C. Koo; Chen-Ming Liang; Shu-Hao Yang; Pei-Yan Zhao; Dongfeng Zhang; Guang-Sheng Wang (Chemical Engineering Journal, 2025)

Machine learning-guided discovery and stabilization of anomalous Ni4+ oxides with superior electrocatalysis for flow batteries - Jia-Qi Liu; Deng-Hua Zhang; Li-Xin Yang; Fang Liu; Tong-Tong Shi; Yu-Jia Wang; Yun-Long Tang; Yin-Lian Zhu; Xiu-Liang Ma (Chemical Engineering Journal, 2025)

Mapping the paleo ice-flow in Larsemann Hills, East Antarctica by UAV remote sensing and terrain analysis - Yibo Li; Teng Li; Baogang Zhang; Tiancheng Zhao; Lei Zheng; Qi Liang; Xiao Cheng; Jianmin Hu (CATENA, 2025)

YY1 lactylation promotes fibroblast senescence by targeting the PU.1-BTG2 axis to promote oral submucous fibrosis - Muhammad Tufail; Jing Zhang; Cai-Yun He; Jia-Ju Hu; Jie Liang; Wen-Dong Wan; Yu-Qi Huang; Zhen Rao; Hong Wu; Can-Hua Jiang; Ning Li (Chemico-Biological Interactions, 2025)

Recipient Periodic Fasting Promotes Osteogenesis of Implanted Mesenchymal Stromal Cell Aggregates and Safeguards Diabetic Mandibular Bone Regeneration - Zi-Qi Zhang; Yuan Yuan; Xiao-Hui Zhang; Jia-Ning Liu; Yuan Cao; Lu Liu; Lu-Fan Yang; Yi-Han Xiao; Shan-Shan Huang; Bing-Dong Sui; Jian-Fei Liang; Ji Chen; et al. (Stem Cell Reviews and Reports, 2025)

SnRNA-seq Interprets Mechanisms by which Three Glial Cell Types Influence Myelin Regeneration in Adult Drug-Resistant Epilepsy-Related Cognitive Impairment - Lu Wang; Jia-Qi Ma; Yong-Qian Bian; Xiao-Peng Qu; Yue Zhang; Chao Wang; Guo-Dong Gao; Long-Long Zheng; Qi-Xing Fang; Li-Jia Song; Liang-Liang Shen; Bei Liu (Molecular Neurobiology, 2025)
Myelin regeneration has been shown in previous studies to ameliorate varying degrees of cognitive impairment in patients with neurodegenerative disorders such as epilepsy. The problem of myelin regeneration in adults with drug-resistant status epilepticus is a major key to the difficulty of treating cognitive impairment in adults with drug-resistant epilepsy (DRE). The purpose of this study is to provide a molecular map of myelin-related molecules under the cognitive deficits seen in DRE. We used a lamotrigine-pentylenetetrazol-resistant epilepsy mouse model and verified the cognitive problems and myelin changes using a water maze and conventional molecular biology techniques. We then analyzed the OLs in the hippocampus of the mice and the effect on myelin using sn RNA-seq technology. We found that the problem of cognitive impairment in drug-resistant epileptic mice is due to altered myelin plasticity. OL maturation induces pathological myelin regeneration which ultimately leads to cognitive impairment. The three glial cell types are closely related to the occurrence of myelin regeneration and jointly promote pathological myelin regeneration. Our study revealed the presence of myelin regeneration in DRE. All of this evidence suggests that normal myelin regeneration contributes to cognitive impairment improvement, but pathological myelin regeneration impairs cognition. Graphical Abstract Schematic representation of myelin regeneration in cognitive impairment in adult drug-resistant epilepsy. Boxed are pathways or molecules related to the promotion of myelin regeneration in which a subpopulation is involved. Red font indicates promotion, blue font indicates inhibition, and gray font indicates unknown but relevant.

MSSI: a multi-scale shift-invariant metric learning network for visible and long-wave infrared image patch matching - Xiuwei Zhang; Yanping Li; Zhaoshuai Qi; Yue Liang; Yi Sun (International Journal of Remote Sensing, 2025)

Tree size and spatial clustering drive contrasting carbon sequestration in soil aggregates in temperate forests in China - Sijia Yang; Danqi She; Lei Wang; Chentao Liang; Guanchao Cheng; Xu Zhang; Lixin Jing; Yanbo Yang; Qi Li; Huimei Wang; Wenjie Wang (Urban Forestry & Urban Greening, 2025)

The protective mechanisms of glycyrrhizic acid for deoxynivalenol-induced toxicity in rabbit corneal stroma - Chunlan Liang; Xuewei Xiong; Qi Shi; Qingqing Li; Guocheng Yu; Jingxiang Zhong; Lian Liu (Toxicology in Vitro, 2025)

Reward-modulated spike-timing-dependent plasticity in van der Waals ferroelectric memtransistor for robotic recognition and tracking - Yi Cao; Jinhao Liang; Tao Liu; Weihui Sang; Yang Gan; Honghong Li; Yue Wang; Zheng Ren; Yuan Yu; Zhou Xin; Yukang Chen; Xumeng Zhang; et al. (Science Bulletin, 2025)

Effects of promotion and suppression by pentafluoroethane on methane explosions: Experimental and simulation discussion - Jing-Jing Li; Shulei Shi; Bingyou Jiang; Mingqing Su; Kunlun Lu; Tun Yang; Qi Yao; Xuerong Liang (Process Safety and Environmental Protection, 2025)

Characterization of the Lonicera japonica R2R3-MYB transcription factor gene LjaMYB305 that promotes the flavonoid biosynthesis - Hailing Fang; Yan Wan; Huiping Liu; Xiwu Qi; Xu Yu; Zequn Chen; Qun Liu; Li Li; Yang Bai; Dongmei Liu; Chengyuan Liang (Plant Science, 2025)

CPK12 decodes effector-triggered calcium signaling and phosphorylates PIP2;1 to facilitate apoplastic ROS transport into the cytoplasm in Arabidopsis - Zhiyi Jia; Weiwei Yu; Xijie Guo; Jianwei Li; Fan Qi; Yayun Zhu; Xinzhong Cai; Xiaoting Li; Ning Li; Hansong Dong; Fucheng Lin; Yan Liang (Molecular Plant, 2025)

Latest progress based on doped-TiO2 photocatalysis materials: Fabrication and applications - Xiao-Ni Qi; Ya-Qi Zhu; Hui Yuan; Zi-Xuan Xu; Hao-Ran Guo; Zhen-Liang Li (Journal of Water Process Engineering, 2025)

Metal bioaccumulation and lipid response in aquatic ecosystem: Evidence of machine learning from Chaohu Lake, China - Qi Lu; Zhi Yuan; Wei Chang; Shen-dong Xu; Lan-lan Wu; Gang Liu; Li-yan Yang; Si-ting Liu; Meng-xue Gao; Yi-fan Hu; Xu-dong Zhang; Huan Zhou; et al. (Journal of Hazardous Materials, 2025)

Research on fouling reduction performance of forward osmosis membrane modified by MIL-101(Fe)/β-PDI in osmotic microbial fuel cells - Lin Qi; Shilong Li; Liang Duan (Journal of Environmental Chemical Engineering, 2025)

Influential mechanisms of light exposure on the reduction of V5+ by extracellular polymeric substances: Role of the reductive and nonreductive components - Wen Qing; Dan Zhou; Liyuan Fu; Tianxin Zhou; Haoran Xiong; Mengmeng Liang; Yi Huang; Jinshu Zhang; Yubin Li; Chengye Yang; Jingxian Qi (Journal of Environmental Chemical Engineering, 2025)

Simultaneous removal of nitrogen and heavy metals in a modified coal gangue fixed-biofilm reactor driven by Fe(II)/Fe(III) cycle - Tianmeng Li; Shangzhe Qi; Junfeng Su; Shuyu Liu; Liang Xu; Yihan Bai; Xuan Li (Journal of Environmental Chemical Engineering, 2025)

Comprehensive comparison of physicochemical properties, volatile flavor compounds and functional activities of double protein yogurt with different soymilk and cow milk additions - Ruijie Li; Yifan Lu; Li Niu; Qi Zhao; Wei Liang; Xinyu Wang; Wenhao Li (Food Research International, 2025)

One-pot synthesis of injectable freeze-dried platelet lysate functionalized peptides hydrogel for pressure ulcers repair - Kun Liu; Lei Wang; Dongdong Li; Fengying Qi; Shaoduo Yan; Xiaoyang Yi; Yanhong Li; Yuyuan Ma; Xian Su; Yuxin Zhang; Xunuo Li; Ruotong Zhang; et al. (Chemical Engineering Journal, 2025)

Vertical distribution and regional transport of air pollution over Northeast China: Insights from an intensive aircraft study - Ye Shan; Yujiao Zhu; Haoxin Sui; Na Zhao; Hongyong Li; Liang Wen; Tianshu Chen; Yanbin Qi; Wenlong Qi; Xinfeng Wang; Yuqiang Zhang; Likun Xue; et al. (Atmospheric Environment, 2025)

Sensitivity analysis of key influencing factors for CO2 residual trapping within porous media - Xiangyang Lu; Liang Xu; Wenbin Gao; Yiyan Zhong; Qi Li (Advances in Water Resources, 2025)

Antifungal cytochalasans from the co-culture of two endophytic fungi Aspergillus spelaeus and Xylaria sp - Xian-Hua He; Ye-Fang Hu; Hua-Chun Feng; Li-Qi Liang; Lan-Fang Zou; Qian Wu; Min Liang; Jun Li; Wei-Feng Xu; Rui-Yun Yang (Natural Product Research, 2025)

Correction: Urolithin A Enhances Tight Junction Protein Expression in Endothelial Cells Cultured In Vitro via Pink1-Parkin-Mediated Mitophagy in Irradiated Astrocytes - Gengxin Lu; Junyu Wu; Zhihui Zheng; Zhezhi Deng; Xue Xu; Xintian Li; Xiaoqiu Liang; Weiwei Qi; Shifeng Zhang; Yuemin Qiu; Minping Li; Junjie Guo; et al. (Journal of Molecular Neuroscience, 2025)

Precise Prediction and Tiered Mitigation Strategies for Thermal Hazards in Deep Mines: A Data-Driven Approach Applied to Shicaocun Coal Mine - Feng-yuan Lv; Hao-nan Li; Qi-ming Wei; Yan-zi Lei; Long Chen; Yan-bin Yang; Biao Zhao; Yu-liang Sun (Applied Geophysics, 2025)

A review on membrane modification techniques for membrane fouling control: Mechanisms and membrane preparation - Lin Qi; Shilong Li; Liang Duan; Slav W. Hermanowicz; How Yong Ng (Critical Reviews in Environmental Science and Technology, 2025)

CDIP-ChatGLM3: A dual-model approach integrating computer vision and language modeling for crop disease identification and prescription - Changqing Yan; Zeyun Liang; Han Cheng; Shuyang Li; Guangpeng Yang; Zhiwei Li; Ling Yin; Junjie Qu; Jing Wang; Genghong Wu; Qi Tian; Qiang Yu; et al. (Computers and Electronics in Agriculture, 2025)

Integrating morphology, ecology, and genomics: Unraveling the population genetic and evolution within the Rosa graciliflora complex - Jia Miao; Liang-Ying Li; Zhen-Long Liang; Yu Feng; Cheng Zhang; Shi-Qi Li; Heng-Ning Deng; Jian Ru; Zhong-Yu Tang; Xin-Fen Gao (Molecular Phylogenetics and Evolution, 2025)

Crustal growth from collision to post-collision: implications from Cretaceous back-arc magmatism flare-up in southern Qiangtang of central Tibet - Sheng-Qiang Zhang; Neng Gong; Hui Qi; Yun-Chuan Zeng; Guo-Li Yuan; Pei-Pei Dong; Ying-Jie Li; Gen-Hou Wang; Zhi-Bo Liu; Xiao Liang (Lithos, 2025)

Recent advances in bioassays for assessing the toxicity of environmental contaminants in effect-directed analysis - Yao Liu; Minjie Li; Qi-Lin Wan; Xun Wang; Monika Mortimer; Wen-Di Fang; Liang-Hong Guo (Journal of Environmental Sciences, 2025)

Recent progress in two-dimensional materials: From emerging structures and synthesis approaches to electronic and sensing applications - Jing Hao Zhuang; Zhong Li; Yi Liang; Tao Tang; Xin Yi Hu; Rui Ou; Qi Jie Ma; Bao Yue Zhang; Yin Fen Cheng; Wen Lin Feng; Jian Zhen Ou (Chemical Engineering Journal, 2025)

Phosphorus flame retardant for enhancing spectral selectivity and fire safety of radiative cooling coatings - Jing Gao; Liangyuan Qi; Liang Chen; Wenyue Guo; Bicheng Lin; Zefan Feng; Suhong Li; Yuan Hu; Fukai Chu; Weiyi Xing (Chemical Engineering Journal, 2025)

Preparation and characterization of Zein/sodium alginate nanoparticle-stabilised Artemisia argyi essential oil Pickering emulsions for agricultural antifungal applications - Yifei Tan; Qianwei Liang; Qi Hong; Shengfu Zhang; Tianzhen Jiang; Zhen Li; Jianguo Feng (Chemical Engineering Journal, 2025)

Corrigendum to “90C fast-charge Na-ion batteries for pseudocapacitive faceted TiO2 anodes based on robust interface chemistry” [Chem. Eng. J. 465 (2023) 143032] - Hongshun Zhao; Jingjing Zhong; Yanli Qi; Kang Liang; Jianbin Li; Xiaobing Huang; Wenkai Chen; Yurong Ren (Chemical Engineering Journal, 2025)

Thermal comfort differences among patients with different orthopedic diseases: A case study of Shaanxi Provincial People's Hospital, China - Meng Zhen; Jingjing Liu; Weijie Xia; Minghui Sun; Qi Dong; Yansong Li; Haijuan Liang (Building and Environment, 2025)

Engineered exosomal miR140 modulates mitophagy of chondrocytes through targeting CAPN1 to alleviate osteoarthritis - Yuan Liu; Kai Huang; Sheng-Liang Zhou; Shuai Li; Hai-Bo Si; Yi Zeng; Hui-Qi Xie; Bin Shen (Science China Life Sciences, 2025)

Isoliquiritigenin alleviates radiation-induced intestinal injury in lung cancer by inhibiting TNF-α/caspase3 signaling pathway - Ya-ping Chen; Liang-liang Shi; Yang-yang Li; Yi-Ming Zhang; Shang-zu Zhang; Hong-dou Hou; Yan Chen; Qi-hong Zhuo; Yong-qi Liu; Ben-jun Wei; Li-ying Zhang (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

TAT-T407 Mitigates Apoptosis and Cognitive Impairments Following Cerebral Ischemia Through Disruption of TRPV1-CDK5 Interaction - Qian Feng; Ying Li; Xiangru Wen; Hui Li; Chengyu Qi; Nan Wang; Guang Zhu; Yanyan Fu; Changdong Liu; Dan Liu; Zhen Zhang; Fan Yang; et al. (Molecular Neurobiology, 2025)

Linking rhizosphere bacterial life-history strategies with wheat growth under drought stress - Yanshuo Pan; Binhui Liu; Shan Zhuang; Hongzhe Wang; Yanjie Qi; Jieyin Chen; Didier Lesueur; Liang Xiao; Yuzhong Li; Dongfei Han (Soil Ecology Letters, 2025)

Water availability regulates the carbon uptake period and amplitude of net ecosystem exchange in alpine grasslands of the Qinghai-Xizang Plateau - Fuquan He; Qi Li; Dongdong Chen; Caiyun Luo; Yukun Zhang; Li Zhang; Sichen Pan; Zongjian Zhao; Liang Zhao (Agricultural and Forest Meteorology, 2025)

Changes in growth and transcriptome expression patterns in mandarin fish (Siniperca scherzeri) under different photoperiods - Jiao Li; Yong Wei; Jun Song; Jun Yang; Xu-Fang Liang; Ke Lu; Qiuling Wang; Ke-Xiang Wang; Kaiting Zhi; Dan Zhao; Yan Wang; Yufeng Zhang; et al. (Acta Oceanologica Sinica, 2025)

Butenolide synergises with vancomycin to eradicate pre-formed biofilm of Staphylococcus aureus by interfering with energy-associated metabolism - Dai-Xin Hu; Jinyou Liang; Jing Yan; Zhi-Wen Ma; Hai-Lin Li; Ying Xu; Yu Zhang; Qi Yin (Biofouling, 2025)

Sources and dynamics of nitrate in groundwater in a crystalline terrain of tropical Sri Lanka based on a dual isotope approach - Charitha Udeshani; Fu-Jun Yue; Yao-Qi Gong; Si-Liang Li; Rohana Chandrajith (Water Research, 2025)

Targeted discovery of oxygen-bridged sesquiterpenes from Cinnamomum migao by MS/MS-based molecular networking and their neuroprotective activities - Lang Zhou; Xiong Pan; Fa-ju Chen; Mei Peng; Yu Wang; Ming Gao; Li-shou Yang; Liang-qun Li; Juan Yang; Xiao-sheng Yang; Qi-ji Li (Phytochemistry, 2025)

A series of meroterpenoids with highly oxygenated skeletons from the endophytic fungus Penicillium sp. and their anti-inflammatory activities - Tu-Xiang Mo; Liu-Xia Lv; Xi-Shan Huang; Jia-Tong Zhou; Qian Wu; Xian-Hua He; Li-Qi Liang; Wei-Feng Xu; Jun Li; Rui-Yun Yang (Phytochemistry, 2025)

Hydrological impact of small hydropower development on mountain rivers in Southwest China and the role of environmental flows - Xintong Li; Wouter Buytaert; Qi Tang; Yuanming Wang; Ruifeng Liang; Kefeng Li (Journal of Hydrology, 2025)

Cross-protection and cross-feeding mediated by signaling molecules enhanced the viability of P. fluorescens S01 and R. erythropolis S02 under the dual stresses of polycyclic aromatic hydrocarbons (PAHs) and low temperature - Qiuying Song; Zihui Qi; Ning Liang; Ning Hou; Chi Zhang; Chenghao Pei; Xinyue Zhao; Dapeng Li (Journal of Hazardous Materials, 2025)

Automated detection and recognition of oocyte toxicity by fusion of latent and observable features - Shuai Huang; Kun Zhao; Chu Chu; Qi Fan; Yuanyuan Fan; Yongqi Luo; Yiming Li; Ke Mo; Guanghui Dong; Huiying Liang; Xiaomiao Zhao (Journal of Hazardous Materials, 2025)

Sustainable remediation of butyl xanthate-contaminated mine wastewater by combining emergent macrophyte Cyperus alternifolius with a versatile bacterial isolate - Qi Liu; Yao-Yao Ye; Sha Yang; Cheng-Yu Cui; Huan Du; Jin-Cheng Ye; Ji-Liang Cheng; Rui-Wen Hu; Lei Xiang; Bai-Lin Liu; Yan-Wen Li; Quan-Ying Cai; et al. (Journal of Hazardous Materials, 2025)

Efficient caproate production from ethanol and acetate via chain elongation reinforced by Fe/Fe3O4 in mixed culture system - Cunsheng Zhang; Chengmei Li; Tianyu Liang; Min Li; Yuxuan Sun; Ziwei Chen; Mei Zhao; Xianghui Qi (Journal of Environmental Management, 2025)

Scandium and gallium in weathered basalts as unconventional resources - Mei-Fu Zhou; Wen Winston Zhao; Zhenchao Wang; Min Wang; Shengbiao Yang; Lei Meng; Liang Qi; Guangfu Xing; Xiang Li; Dai Zhou (Journal of Asian Earth Sciences, 2025)

Insight into the enhancement mechanism of repeated freezing-thawing pretreatment promotes carboxymethylation for improving the properties of sweet potato starch: From a multiscale structural perspective - Li Niu; Siwen Yu; Xinyi He; Wei Liang; Qian Lin; Qi Zhao; Xinyu Wang; Ruijie Li; Wenhao Li (Food Chemistry, 2025)

Functional nucleic acid-stabilized selenium nanotechnology enable synergistic healing of diabetic chronic wounds - Si-Wei Yang; Jing Wang; Yan Tan; Xiao Jing; Chen-Yu Wang; Zhi-Li Yao; Wen-Hui Wang; Yong-Ji Li; Hao-Rui Li; Yan Zhao; De-Ming Kong; Qi-Liang Cai (Chemical Engineering Journal, 2025)

A boronate-affinity thermoresponsive molecularly imprinted resin as a green solid-phase extraction filler for highly selective adsorption of psoralen - Mengying Zhang; Kuiwang Chen; Mengfei Tian; Xiaolong Yang; Jiahui Gong; Qi Liang; Xiaofei Xie; Chunying Li; Chunjian Zhao (Chemical Engineering Journal, 2025)

Degradation of organic pollutant by natural biofilm based biophotovoltaic cells: The combined role of illumination, reactive oxygen species, and enhanced electron transfer - Zihan Qi; Xiuyi Hua; Anfeng Li; Haiyang Liu; Deming Dong; Dapeng Liang; Zhiyong Guo; Na Zheng (Bioresource Technology, 2025)

Electroacupuncture may alleviate diabetic neuropathic pain by inhibiting the microglia P2X4R and neuroinflammation - Si-ying Qu; Han-zhi Wang; Qun-qi Hu; Yi-qi Ma; Yu-rong Kang; Li-qian Ma; Xiang Li; Lu-hang Chen; Bo-yu Liu; Xiao-mei Shao; Bo-yi Liu; Jun-ying Du; et al. (Purinergic Signalling, 2025)

Effects of soil fauna on soil carbon accumulation under organic amendments: Insights from community composition and energy flux - Yang Bai; Yingbin Li; Xiaofang Du; Yixin Sun; Zhenxin Xu; Wenju Liang; Qi Li (Applied Soil Ecology, 2025)

Ultra-processed foods, biological ageing, and all-cause mortality risk: a prospective cohort study using 172,225 participants from UK Biobank - Yifan Wang; Tianchen Qi; Xiaoli Wu; Chunhao Li; Boyan Zeng; Peiqi Huang; Dan Liu; Shuang Liang; Fan Yang; Feifei Xu; Chang Su; Bo Zhang; et al. (GeroScience, 2025)

Integrated Transcriptome and Microbiome Analyses Reveal Growth- and Stress-Response-Related Genes and Microbes in Mandarin Fish (Siniperca chuatsi) - Fan Zhou; Wei Liu; Ming Qi; Qianrong Liang; Gaohua Yao; Cheng Ma; Xueyan Ding; Zaihang Yu; Xinyu Li; Zhanqi Wang (Fishes, 2025)
Mandarin fish (Siniperca chuatsi) are known to exhibit distinct physiological and immunological adaptations to environmental stressors, but the underlying molecular and microbial mechanisms remain unclear. In this study, we integrated transcriptome and microbiome analyses to investigate adaptations across three geographically distinct mandarin fish groups: Guangdong (G), Qiupu (Q), and native Taihu (T). Liver RNA sequencing revealed 5339 differentially expressed genes (DEGs) between T and G and 1531 DEGs between T and Q. Functional enrichment analysis revealed group-specific responses. Specifically, DEGs from T vs. G were linked to small-molecule metabolism and innate immunity whereas the DEGs from T vs. Q were related to immune regulation and chromatin organization. The concurrent 16S rRNA sequencing of the intestinal microbiota identified 2680 amplicon sequence variants, with principal coordinate analysis showing distinct clustering (31.77% variance). Group T had higher Firmicutes abundance whereas groups G and Q had a higher relative abundance of Fusobacteriota. Correlation networks revealed key microbe–gene interactions, including positive links between Lactobacillus and immune genes in group T and negative associations with Romboutsia. These findings suggest that enhanced immune homeostasis and metabolic flexibility in group T may result from coordinated host gene expression and Lactobacillus-driven microbiome modulation. We provide new insights into the mechanisms of adaptation in mandarin fish and identify potential biomarkers for enhancing aquaculture resilience.

Machine learning strategy secures urban smart drinking water treatment plant through incremental advances - Yu-Qi Wang; Hong-Cheng Wang; Zi-Jie Xiao; Ling-Jun Bu; Jiuling Li; Xiao-Chi Feng; Bin Liang; Wen-Zong Liu; Fei-Yun Sun; Shi-Qing Zhou; Ai-Jie Wang (Water Research, 2025)

Enhancement mechanism of chitosan/tannic acid curing and functional group modification on uranium adsorption in five types of wastewater by Cu-MOF - Yulin Huang; Qingliang Wang; Qi Xin; Zhiwu Lei; Eming Hu; Le Li; Feng Liang; Hongqiang Wang (Journal of Hazardous Materials, 2025)

Rapid and efficient nitrogen removal by a novel heterotrophic nitrification-aerobic denitrification bacteria Marinobacterium maritimum 5-JS in aquaculture wastewater: Performance and potential applications - Fu-Rong Wang; Shi-Yu Feng; Shuai Liang; Wei-Yu Du; Long-Qi Wang; Yu-Wei Zhang; Jia-Yu Ren; Shuang Gao; Yu-Jie Zhu; Yu-Ting Cong; Li Wang; Jing Gu; et al. (Environmental Research, 2025)

A non-orthogonal elastoplastic constitutive model incorporating cohesion degradation for frozen soil - Jingyu Liang; Haowen Li; Jilin Qi; Dechun Lu (Computers and Geotechnics, 2025)

Cascade-responsive nanoplatform for synergistic cancer therapy via ROS amplification and hypoxia targeting - Chunyun Xu; Yanfang Ding; Jingjing Qi; Peng Chu; Hongjie Huo; Zhuang Wang; Qingxuan Han; Yuan Liang; Ning Yang; Youwei Xu; Ligeng Xu; Lixue Chen; et al. (Chemical Engineering Journal, 2025)

Utilizing reverse oxygen spillover effect to enhance hydrodeoxygenation performance of CuCoCeOx catalysts via low-temperature air pretreatment - Ziyi Yan; Xiaofeng Wang; Fandi Zeng; Liang Qi; Yanfei Zhang; Qingbo Li (Chemical Engineering Journal, 2025)

Innovative immunosonogen nanoplatform combining sonodynamic oxygenation and immunomodulation for superior cancer therapy - Jiali Tang; Yanlu Chen; Hao Lai; Qi Zeng; Yu Li; Junqi Feng; Ningjing Lin; Ronghua Jin; Junjie Liu; Tao Luo; Zixuan Liang (Chemical Engineering Journal, 2025)

Wear particles-induced periprosthetic osteolysis from a new perspective based on single-cell RNA-seq: crosstalk of osteoblast PANoptosis and macrophage efferocytosis in osteoimmunology microenvironment - Jia-xuan Li; Jian-ping Wen; Shuan-ji Ou; Yu-dun Qu; Chang-liang Xia; Wen-jun Li; Yang Yang; Jia-bao Liu; Rong-shen Yang; Wei Zeng; Wei Zhang; Yun-fei Ma; et al. (Chemical Engineering Journal, 2025)

WRKY Transcription Factors are Required in Piriformospora indica-Induced Resistance to Fusarium Crown Rot in Wheat - Liang Li; Fuyan Qi; Ruiying Hao; Zhenghui Bi; Xiurong Yang (Journal of Plant Growth Regulation, 2025)

Effects and interaction of humidex and air pollution on influenza: A national analysis of 319 cities in mainland China - Qi Gao; Baofa Jiang; Michael Tong; Hui Zuo; Chuanlong Cheng; Yuqi Zhang; Sihao Song; Liang Lu; Xiujun Li (Journal of Hazardous Materials, 2025)

Occurrence, spatial-seasonal variation and air-soil exchange of traditional and novel organochlorine pesticides across 30° latitude in Eastern China: Old tales and new realities - Liang Wang; Wan-Li Ma; Pu-Fei Yang; Chun-Yan Huo; Peng-Tuan Hu; Wen-Long Li; Meng-Qi Fu (Journal of Hazardous Materials, 2025)

Zirconium-iron oxide nitrogen-doped biochar particle electrodes for enhanced tetracycline degradation: Mechanisms and reactive species analysis - Jingran Li; Chen Wang; Wenjin Zhou; Xuetao Liang; Bingyang Liu; Qi Yang; Zhilin Yang (Journal of Environmental Chemical Engineering, 2025)

Effects of novel bio-organic fertilizer on the remediation of PAEs-contaminated soil and its bacterial community composition - Hong-Jia Huang; Bogui Pan; Qi-Feng Liang; Wan-Ting Zhang; Yan-Wen Li; Lei Xiang; Hai-Ming Zhao; Bai-Lin Liu; Quan-Ying Cai; Nai-Xian Feng; Ce-Hui Mo (Journal of Environmental Chemical Engineering, 2025)

Co@Al2O3/C3N4 micro-nano catalysts with photothermal confinement effect for enhanced full-spectrum-solar-light-driven CO2 conversion - Yanan Wang; Qi Yin; Rui Zhang; Jie Ma; Song Xu; Qian Liang; Man Zhou; Zhongyu Li (Journal of Environmental Chemical Engineering, 2025)

An extended bond-based peridynamic model with bond transverse deformation effects for quasi-brittle rocks - Wei-Jian Li; Qi-Zhi Zhu; Yan-Liang Du; Jian-Fu Shao (International Journal of Rock Mechanics and Mining Sciences, 2025)

A green and sustainable synthesis of polydopamine molecularly imprinted resin for selective recognition emodin in Rumex acetosa L.: experiments and simulation - Chunying Li; Jiahui Gong; Mengfei Tian; Hongying Ge; Xiaofei Xie; Qi Liang; Ying Yang; Chunjian Zhao; Ying Liu (Food Bioscience, 2025)

Soil potentially toxic elements promote carbon metabolism in alpine meadows on the Qinghai-Xizang Plateau - Sichen Pan; Caiyun Luo; Xin Chen; Dongdong Chen; Qi Li; Fuquan He; Yukun Zhang; Li Zhang; Liang Zhao (European Journal of Soil Biology, 2025)

Schistosoma japonicum cystatin attenuated CLP-induced sepsis in mice though inducing tolerogenic dendritic cells and regulatory T cells - Yi-Xiang Wang; Yi-Dan Ma; Hui-Hui Li; Wen-Juan Duo; Qi-Wang Jin; Kai-Jun Zhou; Yan-Ran Gao; Jun-Nan He; Yu-Jie Xie; Liang Chu; Xiao-Di Yang (Comparative Immunology, Microbiology and Infectious Diseases, 2025)

Versatile Dual-Emissive Boron-Nitrogen Co-Doped carbon Dots: Unlocking efficient electroluminescent Light-Emitting diodes with breakthrough EQE Approaching 7% - Ming-Zhu Li; Hong-Ji Tan; Qi-Rui Liang; Jie-Rong Yu; Peng Huang; Xiao-Qi Lai; Chun-Fa Wen; Chun-Sing Lee; Qing-Xiao Tong; Jing-Xin Jian (Chemical Engineering Journal, 2025)

Manipulating molecular conformation of charge-transfer cocrystal for NIR-II absorption and light/thermal-responsive imaging - Yun Rong; Si-Qi Chen; Yu Dong Zhao; Sheng Zhuo; Yuan-Yuan Li; Jin-Zhuo Liu; Yi-Yi Ju; Yue-Min Xie; Liang-Sheng Liao; Ming-Peng Zhuo; Ke-Qin Zhang (Chemical Engineering Journal, 2025)

Halophyte inspired solar-driven salt extractor for saline soil remediating - Zixuan Liu; Junhui Li; Yongxu Liu; Qi Sun; Dengchao Liang; Xuan Yang; Wenwen Zhao; Yafang Zhang; Hong Liu; Jiebing Tang; Weijia Zhou; Guobin Xue (Chemical Engineering Journal, 2025)

Accordion-structured robust zinc anodes via MXene-guided deposition towards durable zinc-ion batteries - Yiyang Mao; Zhuo Li; Qidi Zhang; Qi Fan; Yuao Wang; Jing Zhao; Guiling Wang; Dianxue Cao; Kun Liang; Kai Zhu (Chemical Engineering Journal, 2025)

Epigenetics in the modern era of crop improvements - Yan Xue; Xiaofeng Cao; Xiangsong Chen; Xian Deng; Xing Wang Deng; Yong Ding; Aiwu Dong; Cheng-Guo Duan; Xiaofeng Fang; Lei Gong; Zhizhong Gong; Xiaofeng Gu; et al. (Science China Life Sciences, 2025)
Epigenetic mechanisms are integral to plant growth, development, and adaptation to environmental stimuli. Over the past two decades, our comprehension of these complex regulatory processes has expanded remarkably, producing a substantial body of knowledge on both locus-specific mechanisms and genome-wide regulatory patterns. Studies initially grounded in the model plant Arabidopsis have been broadened to encompass a diverse array of crop species, revealing the multifaceted roles of epigenetics in physiological and agronomic traits. With recent technological advancements, epigenetic regulations at the single-cell level and at the large-scale population level are emerging as new focuses. This review offers an in-depth synthesis of the diverse epigenetic regulations, detailing the catalytic machinery and regulatory functions. It delves into the intricate interplay among various epigenetic elements and their collective influence on the modulation of crop traits. Furthermore, it examines recent breakthroughs in technologies for epigenetic modifications and their integration into strategies for crop improvement. The review underscores the transformative potential of epigenetic strategies in bolstering crop performance, advocating for the development of efficient tools to fully exploit the agricultural benefits of epigenetic insights.

The Application of MicroRNAs in Traumatic Brain Injury: Mechanism Elucidation and Clinical Translation - Hong Wang; Xiaolin Fan; Yuhao Zhang; Ning Ma; Liang Li; Qing Lu; Qi Wang; Boya Yu; Xiao Li; Junhong Gao (Molecular Neurobiology, 2025)

Coexistence Patterns of Biocrust-Vascular Plant in the Loess Plateau - Yali Ma; Li Ma; Liping Yang; Hongyu Jiang; Siqing Wang; Yuhan Qi; Qianhai Ye; Weiqi Yao; Yafeng Zhang; Defei Liang; Changming Zhao; Ning Chen (Ecosystems, 2025)

Transcriptomic Analysis Under Drought and Salt Stress Provides Insight into Genes Putatively Involved in Ginsenoside Biosynthesis in Panax japonicus Meyer - Jiangbo Zhou; Jing Li; E. Liang; Minjie Qi; Yuanshe Huang; Lai Zhang (Biochemical Genetics, 2025)

Effects of hybridization on growth, nutrition and reproductive potentiality of the Pacific oyster: Examination of annual variation in phenotypic and biochemical composition - Yuanxin Liang; Jiafeng Fang; Chengxun Xu; Qi Li (Aquaculture, 2025)

Preparation and characterization of epoxy vitrimer asphalt based on transesterification dynamic covalent bond system - Zhe Zhao; Cong Qi; Guanyu Li; Yujin Yao; Liang Fan; Dongliang Kuang; Huaxin Chen; Yongchang Wu; Peng Xu (Fuel, 2025)

A fluorescence biosensor with a dual-function DNA probe targeting the activated estrogen receptor for estrogenic activity evaluation - Qi Zhang; Yuewei Li; Jiali Li; Jiateng Ma; Minjie Li; Liang-Hong Guo (Environmental Research, 2025)

The role of marine microalgae in the transmission of HOCs from contaminated microplastics in the aqueous environment - Jiji Li; Xinjie Liang; Yingying Ye; Shuai Mao; Jiayin Lü; Chengkai Qu; Pengzhi Qi (Environmental Pollution, 2025)

A Novel Model of Traumatic Optic Neuropathy Under Direct Vision Through the Anterior Orbital Approach in Non-human Primates - Zhi-Qiang Xiao; Xiu Han; Xin Ren; Zeng-Qiang Wang; Si-Qi Chen; Qiao-Feng Zhu; Hai-Yang Cheng; Yin-Tian Li; Dan Liang; Xuan-Wei Liang; Ying Xu; Hui Yang (Neuroscience Bulletin, 2025)

Heavy metal pollution and probabilistic risk assessment in soil of desert road shelterbelts in typical oasis cities in Northwest China - Yifan He; Qi Liu; Shengli Wang; Chongbin Li; Tiantian Liang; Ximei Cai (Environmental Geochemistry and Health, 2025)

CTHRC1 expresses in cancer-associated fibroblasts and is associated with resistance to anti-androgen therapy in prostate cancer - Hai-qi Liang; Qi-huan He; Qiu-ju Wei; Qi-zhou Mo; Guang-lin Yang; Fa-ye Wei; Li-wei Wei; Yu-jian Li; Min Qin; Ji-wen Cheng (Genes & Genomics, 2025)

CORBES: Radiation belt survey with international small satellite constellation - Ji Wu; Li Deng; Jaan Praks; Marius Anger; Philipp Oleynik; Wojciech Hajdas; Jin-Dong Wang; Shen-Yi Zhang; Bin Zhou; Li Zeng; Jinbin Cao; David Fischer; et al. (Advances in Space Research, 2025)

Mapping and gene cloning of a wheat mutant dsc with dwarf and compacted spikes - Ying Xue; Junchang Li; Yumei Jiang; Yongjing Ni; Qi Wang; Zhiheng Liang; Peipei Zhang; Ting Wang; Ziping Yao; Jiaqi Wang; Qiaoyun Li; Jishan Niu (Journal of Genetics, 2025)

A Salt-Tolerance evaluation system for Chinese cabbage using multispectral image data fusion and Fine-Tuned, pruned convolutional-LSTM-ResNet networks - Jun Zhang; Yikun Ai; Hao Liang; Dongfang Zhang; Yuxi Liu; Lu Li; Sijiao Qi; Hongda Ma; Siqi Zhao; Jingyi Xue; Yifan Zhao; Xiaofei Fan; et al. (Computers and Electronics in Agriculture, 2025)

Ginkgoites manchurica from the Lower Cretaceous Shahezi Formation of Liaoning, China, and its palaeoclimate implications - Yan Liu; Qiao-Er Ying; Qi-Jia Li; Ning Zhou; Chao Zhang; Yu-Jin Zhang; Xiao Tan; Fei Liang (Palaeoworld, 2025)

A comprehensive omics resource and genetic tools for functional genomics research and genetic improvement of sorghum - Chengxuan Chen; Fengyong Ge; Huilong Du; Yuanchang Sun; Yi Sui; Sanyuan Tang; Zhengwei Shen; Xuefeng Li; Huili Zhang; Cuo Mei; Peng Xie; Chao Li; et al. (Molecular Plant, 2025)

Enhanced visible-light-driven photocatalytic degradation of tetracycline wastewater using surfactant-modified Au-loaded CeO2 nanorods - Junzi Huang; Mengjie Lu; Min Liu; Yahong Xie; Peng Wei; Huihui Xie; Liang Li; Weitao Han; Zhiwei Zhang; Ying Qi (Journal of Environmental Management, 2025)

Copper-enhanced 3D porous FCCA catalysts: Efficient activation of PMS for rapid degradation and stabilization of organic pollutants in complex waters over a wide pH range for application - Bingyang Liu; Yu Wang; Xue Hao; Xuetao Liang; Jingran Li; Qi Yang; Zhilin Yang (Journal of Environmental Chemical Engineering, 2025)

Stable layered oxide cathode materials with ultra-low volume change for high-performance sodium-ion batteries - Liang Gao; Jia-Ning Yang; Qinfeng Zheng; Yixiao Zhang; Xuheng Jiang; Shang-Qi Li; Jie-Sheng Chen; Kai-Xue Wang (Chemical Engineering Journal, 2025)

Phosphorus doping-induced electron transfer promotes cobalt-iron biochar activation of peracetic acid: Selective reactive substance generation for pesticide degradation - Xuetao Liang; Yujie Zhao; Jingran Li; Bingyang Liu; Yanlong Cui; Wenhao Hou; Dongrun Xie; Haoze Liu; Han Wang; Pihong Geng; Qi Yang; Zhilin Yang (Chemical Engineering Journal, 2025)

Achieving ultra-low latent heat of water evaporation in capillary water by regulating hydrophilic groups and pore structure of cellulose/chitosan gel - Dengchao Liang; Jiebin Tang; Qi Sun; Wenwen Zhao; Junhui Li; Yongxu Liu; Zixuan Liu; Xuan Yang; Hong Liu; Guobin Xue (Carbohydrate Polymers, 2025)

Identification and characterization of anthocyanins’ composition and regulatory genes involved in anthocyanins biosynthesis in water dropwort (Oenanthe javanica) - Kai Feng; Nan Sun; Ya-Qing Bian; Wu-Di Rui; Ya-Jie Yan; Zhi-Yuan Yang; Jia-Lu Liu; Zi-Qi Zhou; Shu-Ping Zhao; Peng Wu; Liang-Jun Li (Planta, 2025)

Optimization of Microsatellite Multiplex PCRs for Triploidy Verification and Genetic Diversity Assessment in the Pacific Oyster, Crassostrea gigas - Huilin Zheng; Yuanxin Liang; Geng Cheng; Jianmin Zhou; Wenlong Bi; Hong Hu; Qi Li (Marine Biotechnology, 2025)

Genetic Parameters of Growth and Survival in the Tetraploid Larvae of Pacific Oyster Crassostrea gigas - Xianchao Bai; Yuanxin Liang; Geng Cheng; Ziheng Wang; Chengxun Xu; Qi Li (Journal of Ocean University of China, 2025)

Navigating the gut-liver axis: The potential of tea to alleviate inflammatory bowel disease and associated metabolic syndromes - Qi Fang; Chunyin Qin; Ying Peng; Liang Zhang; Daxiang Li; Shanshan Hu (Trends in Food Science & Technology, 2025)

Combining Landsat 5 TM and UAV images to estimate river discharge with limited ground-based flow velocity and water level observations - Maomao Li; Changsen Zhao; Qi Huang; Tianli Pan; Hervé Yesou; Françoise Nerry; Zhao-Liang Li (Remote Sensing of Environment, 2025)

Targeted isolation of lignans and triterpenoids from kadsura coccinea by molecular networking and anti-RA-FLS activity - Shi-qi Liu; Qing-ling Xie; Ya-si Deng; Ling Liang; Han-wen Yuan; Bin Li; Huang-he Yu; Xing Tian; Yi-xing Qiu; Guy Paulin Kemayou Mouthe; Nuzhat Shehla; Ye Zhang; et al. (Phytochemistry, 2025)

Genomic analysis of Isoptericola halotolerans SM2308 reveals its potential involved in fucoidan degradation - Yu-Qi Zhang; Qi Yuan; Ji-Qing Liu; Xiao-Chen Liang; Jing-Ping Wang; Wen-Xin Jiang; Ping-Yi Li (Marine Genomics, 2025)

Interaction mechanism between membrane biofouling and reverse solute diffusion in an osmotic membrane bioreactor - Si-Qi Zhai; Jing Nan; Wen-Jun Cai; Xi-Wei He; Xiao-Li Yang; Yu-Li Yang; Hai-Liang Song (Journal of Water Process Engineering, 2025)

Assessing the effectiveness of atmospheric pollution control policies by monitoring the changes in trace elements in atmospheric deposition, Lanzhou: 2010–2021 - Liang He; Chongbin Li; Zhaoming Chen; Wen Huang; Yinwen Dong; Qi Liu; Xiang Ning; Shengli Wang (Journal of Cleaner Production, 2025)

Microbial augmented aerobic composting for effective phthalates degradation in activated sludge - Bogui Pan; Hong Tian; Qi-Feng Liang; Hong-Jia Huang; Yi-Tong Huang; Bai-Lin Liu; Yan-Wen Li; Lei Xiang; Hai-Ming Zhao; Quan-Ying Cai; Nai-Xian Feng; Ce-Hui Mo (Journal of Environmental Management, 2025)

An efficient superhydrophilic photothermal membrane of graphene-decorated TiO2 nanotube arrays for solar desalination - Fei Liu; Liang Wang; De Sun; Bingbing Li; Hui Tian; Zhi Qi; Shenglan Zhou (Desalination, 2025)

Direct dehydrogenation condensation of ethanol to ethyl acetate with superior selectivity over acid-base balanced CuZnZrO solid solution catalyst - Siqi Li; Yuda Zhang; Qiang Guo; Yafei Liang; Yuji Qi; Xiaowei Zhao; Yehong Wang; Feng Wang (Chemical Engineering Journal, 2025)

Radiomics-based Modelling Unveils Cerebellar Involvement in Parkinson’s Disease - Yini Chen; Yiwei Qi; Yiying Hu; Tao Qiu; Meichen Liu; Qiqi Jia; Yubing Sun; Xinhui Qiu; Bo Sun; Zhanhua Liang; Weidong Le; Tianbai Li (The Cerebellum, 2025)

Urolithin A Enhances Tight Junction Protein Expression in Endothelial Cells Cultured In Vitro via Pink1-Parkin-Mediated Mitophagy in Irradiated Astrocytes - Gengxin Lu; Junyu Wu; Zhihui Zheng; Zhezhi Deng; Xue Xu; Xintian Li; Xiaoqiu Liang; Weiwei Qi; Shifeng Zhang; Yuemin Qiu; Minping Li; Junjie Guo; et al. (Journal of Molecular Neuroscience, 2025)

Study on hydrophobic characteristics and mechanism of modified biomass-coal mixed combustion ash geopolymer sustainable backfill - Weize Sun; Qi Sun; Bing Liang; Botao Li; Mengyang Shi (Sustainable Chemistry and Pharmacy, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Impaired tactile processing in autism-associated Shank3 mutant dogs: neural mechanism and intervention - Qi Shi; Liang Wu; Baolong Ren; Kun Guo; Yong-Hui Jiang; Yong Q. Zhang; Li Hu (Science Bulletin, 2025)

Insights into P-doping effect of the activity and anti-SO2/H2O poisoning of V2O5-MoO3/TiO2 catalysts for NH3-SCR - Silan Li; Bo Wang; Zijing Liang; Liqiang Qi (Journal of Environmental Chemical Engineering, 2025)

Transfer and risk assessment of perchlorate during green/black tea processing and brewing - Hezhi Sun; Yabo Liang; Peipei Qi; Yan Liu; Fengjian Luo; Zongmao Chen; Li Zhou (Food Research International, 2025)

Advancements in wastewater treatment: A comprehensive review of ozone microbubbles technology - Jiahao Liang; Yu Fei; Yuhan Yin; Qi Han; Yongze Liu; Li Feng; Liqiu Zhang (Environmental Research, 2025)

NO3−-N pulse supply caused by biodegradable plastics exacerbates Trifolium repens L. invasion - Mengfei Tian; Chunjian Zhao; Xiaofei Xie; Qi Liang; Chunying Li (Environmental Pollution, 2025)

Superabsorbent hydrogel evaporator with sandwich SA/CNTs/SA cellular wall for solar-driven water purification - Xi Yu; Jianhui Fang; Xuan Kong; Zikang Yu; Senyi Zheng; Chaomei Pan; Huafeng Liang; Lihuan Wang; Hui Yu; Zijin Liu; Longfei Fan; Qi Zuo; et al. (Chemical Engineering Journal, 2025)

Advanced fabrication of three-dimensional bicontinuous MXene/agarose composite monoliths for high-selective rapid separation of antibodies - Xiang-Dong Xu; Jing Li; Jun-Qi Zhang; Yuan Peng; Chen-Mei Sun; Ru-Qi Liang; Jian-Bo Qu (Chemical Engineering Journal, 2025)

High performance piperidinium based anion exchange membranes with different twisted backbone structures for fuel cells - Ying Jie Liu; Guo Liang Zhang; Yong Qi Hu; Hui Peng; Li Wei Lai; Ai Mei Zhu; Qiu Gen Zhang; Qing Lin Liu (Chemical Engineering Journal, 2025)

Development of a spinopelvic complex finite element model for quantitative analysis of the biomechanical response of patients with degenerative spondylolisthesis - Ziyang Liang; Xiaowei Dai; Weisen Li; Weimei Chen; Qi Shi; Yizong Wei; Qianqian Liang; Yuanfang Lin (Medical & Biological Engineering & Computing, 2025)

Comparative transcriptome analysis identified genes involved in testicular development in Takifugu rubripes - Jinfeng Chen; Mingtao Hu; Meiyuan Li; Chenqi Wang; Liu Wang; Yushun Tian; Hongwei Yan; Qi Liu; Xinyan Liang; Xiuli Wang (Fish Physiology and Biochemistry, 2025)

Hydrochemistry Predominantly Shapes the Unique Nitrogen-Fixing Bacterial Communities in Tibetan Hot Springs - Zhao-Qi Song; Li Wang; Yaru Ma; Dandan Deng; Yang Song; Feng Liang; Xiangyu Guan; Wen-Jun Li; Hongchen Jiang (Journal of Earth Science, 2025)

The effects of a combination of maize/peanut intercropping and residue return on soil microbial nutrient limitation in maize fields - Fanyun Yao; Wei Qi; Yujun Cao; Jie Liang; Xiaodan Liu; Zhiming Liu; Yanjie Lv; Wenwen Wei; Wenhua Xu; Yang Yu; Xiang Li; Jian Feng; et al. (Applied Soil Ecology, 2025)

A Comparative Analysis of Growth, Survival, and Combining Ability Based on Diallel Crosses Among Three Selected Lines of the Fujian Oyster Crassostrea angulata with Normal, Golden, and Black Shell Colors - Yuanxin Liang; Hong Hu; Zhenzong Pan; Chengxun Xu; Qi Li (Journal of Marine Science and Engineering, 2025)
Crossing between selected lines could combine the additive genetic variance accumulated within the lines and the non-additive genetic variance between the lines in the genetic improvement of aquatic animals, thus obtaining progeny with favorable traits. However, the value of this breeding strategy has not been investigated in the Fujian oyster Crassostrea angulata due to the lack of available sufficiently selected lines. In this study, a complete 3 × 3 diallel cross was established between the normal (N), golden (G), and black (B) shell lines of C. angulata. The growth (shell height and living weight) and survival of three purebred groups and six hybrid groups under three environments (Luoyu, Jiangkou, and Houhai) were comprehensively evaluated during the larval and grow-out stages. The general combining ability (GCA) of the parental lines and the specific combining ability (SCA) of the hybrid groups were also estimated. The shell heights of the hybrid groups were significantly lower than those of their parental groups on day 25, exhibiting negative heterosis (MPH: −13.01 to −1.45; HPH: −16.69 to −5.76). Meanwhile, the survival rates of the hybrids were significantly higher than those of the parental groups. A negative value of SCA was recorded for NG (N♀ × G♂) (−0.031), which was in line with its lower survival rate on day 25. Significant heterosis was observed in the growth and survival of each hybrid group during the grow-out stage. The shell height and living weight of the hybrid groups were significantly higher in Houhai than in Luoyu and Jiangkou, but the survival rate in Houhai was significantly lower than in the other two sites. BG (B♀ × G♂) and GB (G♀ × B♂) had higher SCA values than the other four groups, which was consistent with their superior traits. The heterosis of shell height, living weight, and survival rate of BG was significantly greater than in the other five hybrid groups, which could be used as potential parents for breeding high-quality diploid and triploid Fujian oysters. This study demonstrated that the traits of C. angulata could be significantly improved by crossing between different selected lines, providing a reference for evaluating the utilization value of non-additive genetic effects (heterosis) between selected lines in bivalves.

Seasonal variations and comparative nutritional composition of hatchery-reared, hatchery-released, and wild black rockfish (Sebastes schlegelii) - Liu Wang; Yunhai He; Xu Wei; Xinyan Liang; Ruonan Zhang; Qi Liu; Chenqi Wang; Jinfeng Chen; Meiyuan Li; Zhi Ma; Shaodong Qu (Frontiers in Marine Science, 2025)
The black rockfish ( Sebastes schlegelii ) is a commercially important marine species in the Northwest Pacific Ocean. Its population has significantly declined due to overfishing and environmental changes. Stock enhancement has been launched in response to wild populations decline. However, limited evidence is available to confirm the ecological effects after release. Empirically, if the hatchery-released individuals are well-adapted to the wild environment, they should show good or similar nutritional conditions as well as their wild counterparts. Therefore, nutritional analysis was essential and conducted in the present study, by using 146 S. schlegelii individuals in order to compare the differences among hatchery-reared (before-release), hatchery-released, and wild conspecifics (post-release) groups in consideration of different environments during a whole stock enhancement practice. Our results exhibited that hatchery-reared S. schlegelii exhibited significantly lower levels of crude protein and amino acid content than that of hatchery-released and wild ones ( P < 0.05). Specifically, both the hatchery-released and wild S. schlegelii generally showed similar trends of nutrition profiling compared with their hatchery-reared counterparts, such as moisture, crude ash, crude lipid, crude protein, and amino acid profiles ( P > 0.05), indicating homogeneity in their nutritional contents. Our research suggested that S. schlegelii exhibited extensive ecological plasticity, and the variations in nutrition of a population was mainly influenced by environmental factors rather than the origin. However, several differences in fatty acid composition between hatchery-released and wild S. schlegelii indicated that hatchery-released fish might not have fully adapt to the food supply in the wild. This study provided insights into promoting responsible stock enhancement of this species in the future.

A new isoflavone from the stems of Derris eriocarpa How - Ying Liu; Zhen-Xin Zhu; Yue Lu; Cong Wang; Hong-Cun Liu; Juan Meng; Jin Qi; Xiao-Ning Huang; Xiao-Mei Lu; Wen-Sen Lu; Shu-Han Luo; Hai-Na Liang; et al. (Natural Product Research, 2025)

Nano-magnetite enhances dissimilated iron reduction to vivianite from sewage by structuring an enormous and compact electron transfer network - Jifei Chang; Danhui Liang; Yan Gao; Yitong Sun; Xin Wang; Nan-Qi Ren; Nan Li (Water Research, 2025)

Sustainable lectrochemical rocesses-ontrolled xtraction of aluable etal ons from iquid etal ines - Wanpei Sun; Jiahao Tang; Qi Dang; You Li; Liang Tang (Journal of Water Process Engineering, 2025)

Review: Development and application of porous materials to antibiotic drug adsorption and removal - Chao-Ping Hou; Qiang Wang; Qi Liu; Zhi-Guang Li; Chang-Liang Ke; Xu-Feng Wang; Ke Huang (Journal of Water Process Engineering, 2025)

Rhenium residency in molybdenite, compressional textures and relationship to polytypism - Mao Tan; Yiping Yang; Xiao-Wen Huang; Jiaxin Xi; Nuo Li; Yu-Miao Meng; Liang Qi (Geochimica et Cosmochimica Acta, 2025)

Selenium absorption, translocation and biotransformation in pak choi (Brassica chinensis L.) after foliar application of selenium nanoparticles - Wenchao Li; Lan Ma; Yixing Ye; Qi Tang; Yue Shen; Zidan Zou; Hongjian Zhou; Changhao Liang; Guozhong Wang (Food Chemistry, 2025)

Metagenomics reveals the differences in flavor quality of rice wines with Hongqu and Maiqu as the fermentation starters - Siwen Hou; Zihua Liang; Qi Wu; Qiqi Cai; Qibiao Weng; Weiling Guo; Li Ni; Xucong Lv (Food Microbiology, 2025)

Ingenious microfluidic-microwave integrated biosensor for cell sorting and concentration detection of mixed white blood cells and yeasts solution - Yuan-Bo Li; Yan-Xiong Wang; Sen Yang; Qian-Long Chen; Zhong-Hao Li; Jun-Ge Liang; Qi-Gao Fan; Yan-Feng Jiang; Xiaoman Zhou; Tian Qiang (Chemical Engineering Journal, 2025)

Establishing and maintaining stable anammox pathway for nitrogen removal in a pure floc sludge A2/O reactor treating low COD/N municipal wastewater - Yang Zhao; Liang Zhang; Qiyu Liu; Xiaoguang Liu; Qi Zhao; Xiyao Li; Yongzhen Peng (Chemical Engineering Journal, 2025)

Bismuth/manganese-doped carbon dots in calcium phosphate matrix: Dynamic conformational nanoparticles enhancing tumor accumulation, deep penetration, and radiosensitivity - Jiahao Liu; Qingnian Li; Hanyu Tu; Jie Feng; Xiaofei Fan; Ze Mi; Hongpei Han; Xiaoqian Ma; Qi Liang; Zheng Zhang; Hongshuai Hou; Pengfei Rong; et al. (Chemical Engineering Journal, 2025)

Supramolecular assembly strategy of modified starch chains for achieving recyclable emulsion biocatalysis within a narrow pH range - Yang Li; Qunyu Gao; Liang Qi; BinBin Nian (Carbohydrate Polymers, 2025)

Achieving efficient anammox contribution and the enrichment of functional bacteria in partial denitrification/anammox system: Performance, microbial evolution and correlation analysis - Zilong Hou; Wenyi Dong; Yanchen Li; Shuo Chen; Huaguang Liu; Qi Han; Zilong Zhao; Jie Liu; Liang Zhang; Hongjie Wang; Yongzhen Peng (Bioresource Technology, 2025)

Huanglian decoction prevents and treats radiation-induced intestinal injury in lung cancer by regulating endoplasmic reticulum stress - Liang-liang Shi; Ya-ping Chen; Hao-ming Guo; Xue-peng Wang; Yang-yang Li; Shuai-zhe Wang; Shang-zu Zhang; Qi-hong Zhuo; Yong-qi Liu; Ben-jun Wei; Li-ying Zhang (Journal of Natural Medicines, 2025)

Intramolecular distance-regulated G4 DNA enzymatic activity-based chromophotometric system for visual monitoring of diquat - Ya You; Wei-Guo Yang; Shun Zhang; Ming-Li Su; Qi-Lin Peng; Wan-Jiang Zhao; Ruo Yuan; Shang-Cheng Xu; Wen-Bin Liang (Analytica Chimica Acta, 2025)

A systemic review of yak milk and its products on the Qinghai-Tibet Plateau: Unique products, chemical composition, biological activities, and microbial composition - Zhiqiang Liang; Xiaoqian Chen; Xinyu Wang; Xiaoxi Qi; Lina Zhang; Yu Xin; Zhenyu Yang; Rui Fan; Yang Li; Libo Liu; Chun Li (Trends in Food Science & Technology, 2024)

Unveiling spatiotemporal distribution, partitioning, and transport mechanisms of tire additives and their transformation products in a highly urbanized estuarine region - Hai-Yan Zhang; Yue-Hong Liu; Li-Ni Wei; Rui-Qi Zhu; Jian-Liang Zhao; Shan Liu; Xiang-Rong Xu; Guang-Guo Ying (Science of The Total Environment, 2024)

Fe3+/Fe2+ cycling drove novel ammonia oxidation and simultaneously removed lead, cadmium, and copper - Shangzhe Qi; Liang Xu; Junfeng Su; Tianmeng Li; Hao Wei; Xuan Li (Journal of Hazardous Materials, 2024)

Impacts of hydrophobic chain length on foam stability and CO2 geo-sequestration capacity of sugar-based nonionic surfactants: Molecular dynamics simulation and laboratory experiments - Yiping Wen; Peihua Zeng; Liang Xu; Qi Li; Xueqian Guan; Kai Wei; Xiaotong Wang (Journal of Environmental Chemical Engineering, 2024)

Effective strategy for C3N5 with improved photodegradation performance: The key role of the robust built-in electric field and enhanced oxygen adsorption capacity - Xiang Li; Haijuan Zhan; Wei Xu; Jiantong Wen; Gang Wang; Qi Guo; Heping Li; Lijuan Liang; Wanyi Liu (Journal of Environmental Chemical Engineering, 2024)

Chiral FeNC single-atom nanozymes with multi-enzyme activity for dye degradation - Guobao Ning; Huan Liang; Linjiang Guo; Xiaokang Lu; Lin Xiao; Tianle Qi; Hui Zhao; Can-Peng Li (Journal of Environmental Chemical Engineering, 2024)

1T/2H-MoS2/CdS heterojunction for the co-production of lactic acid photoreforming to hydrogen and value-added chemicals - Ermiao Liang; Xue Liu; Zheng Yang; Jifang Zhang; Yabo Qi; Rui Teng; Wenbo Cui; Mingcong Xu; Sha Luo; Chunhui Ma; Shouxin Liu; Wei Li (Journal of Environmental Chemical Engineering, 2024)

Pulsed uplift of the South Tianshan since the Late Miocene indicated by the linear inversion on river longitudinal profiles - Jiangang Li; Wentian Liang; Yizhou Wang; Shida Song; Qi Shen; Sihua Yuan (Geomorphology, 2024)

Two-stage Mesozoic oceanic subduction and related mantle metasomatism beneath the South Qiangtang terrane with implications for post-collisional magmatism - Neng Gong; Sheng-Qiang Zhang; Hui Qi; Guo-Li Yuan; Jun Li; Gen-Hou Wang; Xiao Liang; Zhi-Bo Liu (Gondwana Research, 2024)

Ameliorative effects of Trichosanthes kirilowii Maxim. seed oil on hyperlipidemia rats associated with the regulation of gut microbiology and metabolomics - Weili Chen; Zhangbao Zhou; Ruida Qi; Jun Zhou; Huiying Liang; Pinxi Huang; Zebin Zou; Ling Dong; Hua Li; Bing Du; Pan Li (Food Research International, 2024)

Corrigendum to “A critical review on graphene oxide membrane for industrial wastewater treatment” [Environ. Res. 223 (2023) 115409] - Ye-Chen An; Xiao-Xu Gao; Wen-Li Jiang; Jing-Long Han; Yuan Ye; Tian-Ming Chen; Rui-Yun Ren; Jia-Hui Zhang; Bin Liang; Zhi-Ling Li; Ai-Jie Wang; Nan-Qi Ren (Environmental Research, 2024)

Application of earthworm can enhance biological power generation and accelerate sulfamethoxazole removal in agricultural soils - Hui-Xiang Wang; Qi-Wei Peng; Yu-Li Yang; Xi-Wei He; Yi-Jing Yang; Shuai Zhang; Hai-Liang Song (Bioresource Technology, 2024)

Optimizing ABA-based chemically induced proximity for enhanced intracellular transcriptional activation and modification response to ABA - Zeng Zhou; Yue-Qi Wang; Xu-Nan Zheng; Xiao-Hong Zhang; Lu-Yao Ji; Jun-You Han; Ze-Cheng Zuo; Wei-Liang Mo; Li Zhang (Science China Life Sciences, 2024)

Analysis of PANoptosis-related ceRNA network reveals lncRNA MIR17HG involved in osteogenic differentiation inhibition impaired by tumor necrosis factor-α - Jia-Xuan Li; Yu-Dun Qu; Chang-Liang Xia; Wei Zhang; Song-Song Wang; Shuan-Ji Ou; Yang Yang; Yong Qi; Chang-Peng Xu (Molecular Biology Reports, 2024)
Background Inflammatory cytokines such as Interleukin 1β(IL1β), IL6,Tumor Necrosis Factor-α (TNF-α) can inhibit osteoblast differentiation and induce osteoblast apoptosis. PANoptosis, a newly identified type of programmed cell death (PCD), may be influenced by long noncoding RNA (lncRNAs) which play important roles in regulating inflammation. However, the potential role of lncRNAs in inflammation and PANoptosis during osteogenic differentiation remains unclear. This study aimed to investigate the regulatory functions of lncRNAs in inflammation and apoptosis during osteogenic differentiation. Methods and results High-throughput sequencing was used to identify differentially expressed genes involved in osteoblast differentiation under inflammatory conditions. Two lncRNAs associated with inflammation and PANoptosis during osteogenic differentiation were identified from sequencing data and Gene Expression Omnibus (GEO) databases. Their functionalities were analyzed using diverse bioinformatics methodologies, resulting in the construction of the lncRNA-miRNA-mRNA network. Among these, lncRNA (MIR17HG) showed a high correlation with PANoptosis. Bibliometric methods were employed to collect literature data on PANoptosis, and its components were inferred. PCR and Western Blotting experiments confirmed that lncRNA MIR17HG is related to PANoptosis in osteoblasts during inflammation. Conclusions Our data suggest that TNF-α-induced inhibition of osteogenic differentiation and PANoptosis in MC3T3-E1 osteoblasts is associated with MIR17HG. These findings highlight the critical role of MIR17HG in the interplay between inflammation, PANoptosis, and osteogenic differentiation, suggesting potential therapeutic targets for conditions involving impaired bone formation and inflammatory responses.

Disintegration of Cav-1/β-catenin complex attenuates neuronal death after ischemia–reperfusion injury by promoting β-catenin nuclear translocation - Peng Guo; Wan Wang; Zhiyan Liang; Yihang Li; Xiangling Ou; Ming Li; Bin Wang; Xuewen Wei; Linyan Huang; Suhua Qi (Molecular Biology Reports, 2024)

Shikonin improves the effectiveness of PD-1 blockade in colorectal cancer by enhancing immunogenicity via Hsp70 upregulation - Jinghua Chen; Jie Liu; Xiaolin Liu; Jun Wang; Xiumei Wang; Xin Ye; Qi Xie; Jing Liang; Yan Li (Molecular Biology Reports, 2024)
Background PD-1 blockade has shown impressive clinical outcomes in colorectal cancers patients with high microsatellite instability (MSI-H). However, the majority of patients with colorectal cancer who present low microsatellite instability (MSI-L) or stable microsatellites (MSS) show little response to PD-1 blockade therapy. Here, we have demonstrated that Shikonin (SK) could induce cell death of CT26 cells via classically programmed and immunogenic pathways. Methods and results SK promoted the membrane exposure of calreticulin and upregulated the expression of heat shock protein 70 (Hsp70). The upregulation of Hsp70 was dependent on ROS induced by SK and silencing of PKM2 in CT26 cells reverts ROS upregulation. Besides, SK synergizes with PD-1 blockade in CT26 tumor mice model, with the increase of intramural DC cells and CD8 + T cells. The expression of Hsp70 in tumor tissue was also increased in combinational SK plus αPD-1 therapy group. Conclusions Our study elucidated the potential role of ‘Shikonin-PKM2-ROS-Hsp70’ axis in the promotion of efficacy of PD-1 blockade in CRC treatments, providing a potential strategy and targets for improving the efficacy of PD-1 blockade in colorectal cancer.

PRDX1 Interfering Peptide Disrupts Amino Acids 70–90 of PRDX1 to Inhibit the TLR4/NF-κB Signaling Pathway and Attenuate Neuroinflammation and Ischemic Brain Injury - Xiang-Yu Ma; Cheng-yu Qi; Xing-yi Xu; Hui Li; Chang-Dong Liu; Xiang-Ru Wen; Yan-Yan Fu; Yan Liu; Jia Liang; Cheng-Yu Huang; Dan-Dan Li; Yan Li; et al. (Molecular Neurobiology, 2024)

Integrated analysis of methylation and transcriptome identifies a novel risk model for diagnosis, prognosis, and immune characteristics in head and neck squamous cell carcinoma - Jun-wei Zhang; Xi-Lin Gao; Sheng Li; Shuang-hao Zhuang; Qi-Wei Liang (Molecular Genetics and Genomics, 2024)

Detection of Ginkgo biloba seed defects based on feature adaptive learning and nuclear magnetic resonance technology - Shuaishuai Zhao; Maocheng Zhao; Liang Qi; Dawei Li; Xiwei Wang; Zhong Li; Min Hu; Kaixuan Fan (Journal of Plant Diseases and Protection, 2024)

Morphology-based genetic diversity analysis reveals introgressive hybridizations obscure species boundaries of three wild roses endemic to Taiwan Island - Cheng Zhang; Shi-Qi Li; Liang-Ying Li; Xin-Fen Gao (Horticulture, Environment, and Biotechnology, 2024)

A comparative study of the survival, growth, and gonad development of the diploid and triploid Pacific oyster, “Haida No.2” strain - Geng Cheng; Yuanxin Liang; Haining Zhang; Chengxun Xu; Qi Li (Aquaculture International, 2024)

Nanoparticles (NPs)-meditated si-lncRNA NONHSAT159592.1 inhibits glioblastoma progression and invasion through targeting the ITGA3/FAK/PI3K/AKT pathway - Renjie Wang; Qi Li; Xiaolei Chu; Nan Li; Haiqian Liang; Feng He (Metabolic Brain Disease, 2024)

Optimal operation of CCHP system with duality operation strategy considering hydrogen trading and carbon capture - Zhi-Feng Liu; Ya-He Huang; Qing Kang; Ze-Qi Li; Jing Lu; Rui-Zheng Gu; Xing-Fu Luo; Xiao-Rui Chen; You-Yuan Liu; Yu Tang; Liang Guo (Sustainable Cities and Society, 2024)

Bioaccessibility and bioavailability assessment of cadmium in rice: In vitro simulators with/without gut microbiota and validation through in vivo mouse and human data - Fei-Fei Xu; Ying-Si Chen; Xiu-Qin Lin; Ai-Hua Zhong; Min Zhao; Yue-Qi Li; Zi-Yin Li; Yue-Fei Lai; Jia Song; Jia-Liang Pan; Zhan-Fan Cai; Xu-Xia Liang; et al. (Science of The Total Environment, 2024)

Short-term air pollution and greenness exposures on oxidative stress in urban and peri-urban residents in Beijing: A part of AIRLESS study - Wenhao Qi; Hanbin Zhang; Yiqun Han; Wu Chen; Yanbo Teng; Lia Chatzidiakou; Benjamin Barratt; Rod Jones; Frank Kelly; Tong Zhu; Junfeng Zhang; John S. Ji; et al. (Science of The Total Environment, 2024)

Transcriptional regulation and functional validation analysis of the McbZIP1 in Mentha canadensis L. - Xu Yu; Shumin Li; Taolan Xiao; Xiwu Qi; Hailing Fang; Li Li; Yang Bai; Dongmei Liu; Qun Liu; Zequn Chen; Zhichao Xue; Chengyuan Liang (Plant Science, 2024)

Optimizing the nested PCR method for Decapod iridescent virus 1 (DIV1) targeting ATPase gene by reselecting the inner primers - Jing-Yi Xing; An-Qi Li; Xiao-Meng Guo; Meng Wang; Xin Guan; Liang Qiu; Qing-Li Zhang; Jie Huang (Journal of Invertebrate Pathology, 2024)

Differential spatial responses and assembly mechanisms of soil microbial communities across region-scale Taiga ecosystems - Zheng-Xiao Liu; Yue-Ming Lyu; Yang Liu; Yun-Qi Wang; Ming-Min Xiong; Yuan Tang; Xing-Yue Li; Han Sun; Ji-Liang Xu (Journal of Environmental Management, 2024)

Effect of electron beam pretreated wheat flour on dough properties - Li Niu; Mengting Yan; Wei Liang; Qian Lin; Qi Zhao; Ruijie Li; Xinyu Wang; Raushan Moldakhmetova; Wenhao Li (Journal of Cereal Science, 2024)

Effects of cutting temperature on the genes and fatigue properties of asphalt during its refining process - Guanyu Li; Cong Qi; Shanjian Han; Liang Fan; Dongliang Kuang; Huanxin Chen; Yongchang Wu (Fuel, 2024)

Screening, characterization and mechanism of a potential stabiliser for nisin nanoliposomes with high encapsulation efficiency - Qibin Li; Linao Lv; Weiqi Liang; Zhibao Chen; Qi Deng; Lijun Sun; Yaling Wang; Ying Liu (Food Chemistry, 2024)

Grain and nutritional yield merits of sustainable intensification through maize-legume rotations in land constrained smallholder farms of Malawi - Donald Nyamayevu; Isaiah Nyagumbo; Wei-li Liang; Rui-qi Li; João Vasco Silva (Field Crops Research, 2024)

Blood mercury mediates the associations between fish consumption and serum uric acid levels among Chinese adults: A nationally representative study - Changzi Wu; Bing Wu; Yingli Qu; Hui Fu; Yue Chen; Yifu Lu; Saisai Ji; Liang Ding; Zheng Li; Qi Sun; Miao Zhang; Xu Zhang; et al. (Environmental Research, 2024)

Long-term evolution of the Sulzberger Ice Shelf, West Antarctica: Insights from 74-year observations and 2022 Hunga-Tonga volcanic tsunami-induced calving - Aiguo Zhao; Yuan Cheng; Alexander D. Fraser; Luke G. Bennetts; Haifeng Xiao; Qi Liang; Teng Li; Rongxing Li (Earth and Planetary Science Letters, 2024)

Mussel-inspired, fully biobased, mechanically robust, and room temperature healable supramolecular elastomer composites for sustainable strain sensors - Ming-Liang Wu; Shuang-Li Li; Yi-Dong Li; Man-Qi Zhang; Jian-Bing Zeng (Chemical Engineering Journal, 2024)

Green massive mechanical synthesis of highly efficient Zn-Doped Cs3Cu2I5 for LED and X-ray imaging applications - Qi-Hua Yang; Gui-Hua Li; Yu-Chen Ao; Shu-Juan Zhao; Han-Qi Wei; Le Fu; Zhi-Wei Luo; Tian-Liang Zhou; Chu-Jie Wang; Ge-Mei Cai (Chemical Engineering Journal, 2024)

Efficient activation of peroxyacetic acid by cobalt-iron alloy/oxide heterojunctions anchored in defect-rich biochar for pesticide degradation in water: Unravelling the radical-unradical mechanism - Xuetao Liang; Xueying Li; Yujie Zhao; Jingran Li; Bingyang Liu; Qingbang Yang; Longyan Cui; Zhilin Yang; Qi Yang (Chemical Engineering Journal, 2024)

PbHfO3-based antiferroelectric materials: Fundamentals, properties, and advanced applications - Dong-Liang Li; Xin-Gui Tang; Shui-Feng Li; Xiao-Bin Guo; Dan Zhang; Qi-Jun Sun; Wen-Hua Li; Zhen-Hua Tang; Yan-Ping Jiang; Qiu-Xiang Liu (Chemical Engineering Journal, 2024)

Aberrant Enhanced NLRP3 Inflammasomes and Cell Pyroptosis in the Brains of Prion-Infected Rodent Models Are Largely Associated with the Proliferative Astrocytes - Dong-Hua Zhou; Xiao-Xi Jia; Yue-Zhang Wu; Wei-Wei Zhang; Yuan Wang; Dong-Lin Liang; Li-Ping Gao; Kang Xiao; Cao Chen; Xiao-Ping Dong; Qi Shi (Molecular Neurobiology, 2024)

Estimation of Regional Evapotranspiration Based on the Decouple Model and Remote Sensing Information ——a Case Study in Beijing City and Nearby Region - Su-Chuang Di; Zhao-Liang Li; Yanmin Ren; Meng Liu; Ya-Zhen Jiang; Fan-Dong Zheng; Xue-Min Li; Yan-Bing Qi; Hong-Lu Liu; Ronglin Tang (International Journal of Remote Sensing, 2024)

Contamination profile and hazards of neonicotinoid insecticides in honey from apiaries in Beijing, China - Yuan Huang; Benyan Tang; Liming Wu; Chongbo Liang; John P. Giesy; Wanli Li; Yandong Xu; Kai Wang; John R. Purdy; Keith R. Solomon; Suzhen Qi (Environmental Science and Pollution Research, 2024)

Growth, survival and thermotolerance of diploids, triploids and tetraploids of the Fujian oyster Crassostrea angulata with normal, golden and black shell colors - Yuanxin Liang; Hong Hu; Geng Cheng; Chengxun Xu; Qi Li (Aquaculture, 2024)

Thyroxine regulates pig Sertoli cell line proliferation and maturation through the IKK/NFκB and p38 MAPK signaling pathways - Jing Li; Shao-Xuan Zhang; Da-Li Wang; Jia-Jia Qi; Chun-Yan Bai; Hao Sun; Bo-Xing Sun; Shuang Liang (Theriogenology, 2024)

Synergistic effects of bivalve and microalgae co-cultivation on carbon dynamics and water quality - Shuang Liang; Haocheng Li; Jian Liang; Huiru Liu; Xiaoyu Wang; Limei Chen; Li Gao; Jianfei Qi; Yongjun Guo (Marine Environmental Research, 2024)

Deciphering microbial metabolic interactions and their implications for community dynamics in acid mine drainage sediments - Shao-Ming Gao; Pandeng Wang; Qi Li; Wen-Sheng Shu; Ling-Yun Tang; Zhi-Liang Lin; Jin-Tian Li; Li-Nan Huang (Journal of Hazardous Materials, 2024)

A novel biofilm reactor drives Feammox and removes ammonia, nickel, and ciprofloxacin simultaneously: Optimization and species characteristics - Shangzhe Qi; Liang Xu; Junfeng Su; Shuyu Liu; Enlei Liang; Jingting Feng; Xuan Li (Journal of Environmental Chemical Engineering, 2024)

Understanding anti-corrosion mechanisms of the 2,6-dithiopurine (DTP) inhibitor molecule on iron surfaces - Qi Zheng; Chengyao Liang; Jinyang Jiang; Shaofan Li (Journal of Environmental Chemical Engineering, 2024)

Study on pre-oxidation of silver concentrate and leaching behaviour of Zn, Cu and In during oxygen-pressure leaching - Liu Qiang; Li Cun-xiong; Gu Zhi-hui; Li Chang-wen; Wang Qi-liang (Hydrometallurgy, 2024)

Flavonoid localization in soybean seeds: Comparative analysis of wild (Glycine soja) and cultivated (Glycine max) varieties - Zhentao Ren; Xin Yin; Laipan Liu; Li Zhang; Wenjing Shen; Zhixiang Fang; Qi Yu; Liang Qin; Lulu Chen; Ruizong Jia; Xiaodong Wang; Biao Liu (Food Chemistry, 2024)

DNAzyme-driven tripedal DNA walker for ratiometric electrochemical aptasensor ultrasensitive detection of aflatoxin B1 - Jiong Liang; Yunzhe Zhang; Zikun Li; Xin Lu; Congyan Qi; Qian Yang; Wei Zhang (Food Control, 2024)

A positive loop between relish and cuticle proteins and their roles in regulating AMPs expression during bacterial infection in Eriocheir sinensis - Xia Liang; Ying Huang; Hao Xu; Qian Ren; Di Cui; Xin Qi; Hai-Li Zhang (Fish & Shellfish Immunology, 2024)

DPA-Zn enables targeting and bypassing endosomal trapping delivery of a genome-editing system into cancer cells via phosphatidylserine-mediated endocytic pathway - Qi Shao; Cai-Liang Shen; Wei You; Xuan Nie; Wei-Qiang Huang; Fan Gao; Xiao-Hong Zhou; Hai-Li Wang; Long-Hai Wang; Guang Chen; Chang-Hui Wang; Chun-Yan Hong; et al. (Chemical Engineering Journal, 2024)

Na/Bi-co-doping and heterogeneous interfaces leading to enhanced thermoelectric performance of p-type Mg3Sb2-based Zintls - Zhe Xu; Xiao-Lei Shi; Yibo Zhang; Jisheng Liang; Meng Li; Chengyan Liu; Lei Miao; Siqi Liu; Shihao Wang; Qi Zhou; Jie Gao; Zhongwei Zhang; et al. (Chemical Engineering Journal, 2024)

Anchored Ru nanoclusters strategy enhances hydrogen spillover effect for high-efficiency hydrogen storage - Xiao-Qi Zhang; Yi-Qiang Qi; He Liu; Jun-Yu Wang; Li-Ying Xie; Jun-Lian Shi; Feng Wang; Yue-Liang Liu; Zong-Xian Wang; Ai-Jun Guo (Chemical Engineering Journal, 2024)

Triarylamine-based polyimide COFs for achieving high performance ambipolar multi-color electrochromic energy-storage films - Lei Huang; Rong Guo; Qingqing Qiu; Huan Li; Putrakumar Balla; Jinming Zeng; Tongxiang Liang; Xiaopeng Qi; Ping Liu (Chemical Engineering Journal, 2024)

Heterologous expression and characterization of a dye-decolorizing peroxidase from Ganoderma lucidum, and its application in decolorization and detoxifization of different types of dyes - Dongmei Liu; Wentong Diao; Hong Chen; Xiwu Qi; Hailing Fang; Xu Yu; Li Li; Yang Bai; Chengyuan Liang (World Journal of Microbiology and Biotechnology, 2024)

Benefit and risk: Keystone biomes in maize rhizosphere associated with crop yield under different fertilizations - Xiyuan Xu; Kunkun Fan; Qi Li; Teng Yang; Gui-Feng Gao; Yuying Ma; Li Nie; Wenju Liang; Jiabao Zhang; Haiyan Chu (Applied Soil Ecology, 2024)

Effects of temperature and salinity on the larval early development, growth, and settlement of the diploid, triploid, and tetraploid Pacific oyster “Haida No. 2” strain - Geng Cheng; Yuanxin Liang; Haining Zhang; Chengxun Xu; Qi Li (Aquaculture International, 2024)

Applications of Digital Enzyme-Linked Immunosorbent Assays in Ophthalmology - He Yu; Jiaping Song; Junrong Li; Yuanyuan Qi; Zhe Fan; Qiming Liu; Liang Yu; Jian Song; He Dong (Cell Biochemistry and Biophysics, 2024)

The Ecological Niches and Interspecific Associations of the Dominant Fishes in the Xiamen Seas, China - Liang-Min Huang; Hao-Qi Xu; Jia-Yue Yu; Yong-He Chen; Jia-Qiao Wang; Fen-Fen Ji; Jun Li; Jian-Di Cai; Ta-Jen Chu (Fishes, 2024)
Fish are vital in enhancing the stability of marine ecosystems. Therefore, understanding the ecological niches and interspecific correlation characteristics of their dominant species provides a good scientific basis for the protection and management of marine biodiversity. In this study, on the basis of survey data from trawls conducted in the waters off Xiamen in the spring (April) and autumn (November) of 2021, the ecotopes and interspecies connectivity of the dominant fish species were investigated using the relative importance index (IRI), χ2 tests, the association coefficient (AC), and Pearson and Spearman analyses. According to the IRI, there were 23 fish species with higher values, including 15 species in spring and 15 species in autumn. The 15 dominant fish species could be subdivided into wide-, medium-, and narrow-ecotope species, of which there were 2 and 3 wide-ecotope types in spring and autumn. The niche overlap indices exhibited a range of 0.000–0.809 in the spring and 0.000–0.915 in the autumn, showing small differences between the two seasons. The interspecific correlations between the dominant fishes in Xiamen’s waters in spring and autumn were weak, and both showed non-significant positive correlations, indicating that the correlations between the dominant fishes in this sea area are relatively independent. The findings of this investigation provide a fundamental database and theoretical framework for researching the adaptive mechanisms of marine fish in the Xiamen Seas.

Evidence for particle acceleration approaching PeV energies in the W51 complex - Zhen Cao; F. Aharonian; Axikegu; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; Q. Cao; W.Y. Cao; et al. (Science Bulletin, 2024)

Controllable preparation of graphene glass fiber fabric towards mass production and its application in self-adaptive thermal management - Ruojuan Liu; Fan Yang; Shuting Cheng; Xianghe Yue; Fushun Liang; Wenjuan Li; Jingnan Wang; Qinchi Zhang; Liangyu Zou; Hao Yuan; Yuyao Yang; Kangyi Zheng; et al. (Science Bulletin, 2024)

Preliminary design and hydrodynamic study of power-driven float pole system in Pacific saury fishery - Chuanxiang Hua; Wanhua Liang; Fei Li; Qingcheng Zhu; Qi Li; Leilei Chen (Ocean Engineering, 2024)

B/N modified carbon nanofiber mesh covered with layered double hydroxide for large current overall water splitting - Ji Qi; Chunqi Zhu; Jianing Hu; Shuai Ran; Tauqeer Ahmad; Siraj Ullah; Lixu Chen; Yi Chen; Yuqing Xia; Xue Sun; Chuang Li; Xiao Chen; et al. (Fuel, 2024)

Applications and characterization of anti-browning enzymatically modified potato starch (EPS) film associated with chitosan (CTS)/L-Cys/citric acid (CA) on fresh-cut potato slices - Hongmei Zhu; Lan Gao; Jingyi Liang; Erihemu; Gongqin Li; Xiaoqing Song; Wenliang Qi (Food Chemistry, 2024)

Deciphering dissolved organic matter characteristics and its fate in a glacier-fed desert river—the Tarim river, China - Yufu Han; Yulin Qi; Jun Zhong; Yuanbi Yi; Hui Nai; Ding He; Chen He; Quan Shi; Si-Liang Li (Environmental Research, 2024)

Molecularly imprinted beads based on modified cellulose hydrogel:A novel solid phase extraction filler for specific adsorption of camptothecin - Chunying Li; Zidan Luo; Mengfei Tian; Qi Liang; Xiaofei Xie; Chunjian Zhao (Carbohydrate Polymers, 2024)

TBC1D1 is an energy-responsive polarization regulator of macrophages via governing ROS production in obesity - Qi Wang; Ping Rong; Wen Zhang; Xinyu Yang; Liang Chen; Ye Cao; Minjun Liu; Weikuan Feng; Qian Ouyang; Qiaoli Chen; Hailong Li; Hui Liang; et al. (Science China Life Sciences, 2024)

Identification of LRRC46 as a novel candidate gene for high myopia - Lingxi Jiang; Chao Dai; Yao Wei; Bo Zhao; Qi Li; Zhengzheng Wu; Liang Zou; Zimeng Ye; Zhenglin Yang; Lulin Huang; Yi Shi (Science China Life Sciences, 2024)

Overcoming mechanistic limitations of process-based phenological models: A data clustering method for large-scale applications - Jiaojiao Tan; Gang Zhao; Qi Tian; Lei Zheng; Xiaofeng Kang; Qinsi He; Yu Shi; Bin Chen; Dingrong Wu; Ning Yao; Liang He; Amit Kumar Srivastava; et al. (Agricultural and Forest Meteorology, 2024)

Assessing the degree of impact from iceberg activities on penguin colonies of Clarence Island - Hong Lin; Xiao Cheng; Teng Li; Qian Shi; Qi Liang; Xinyu Meng; Shaoyin Wang; Lei Zheng (Acta Oceanologica Sinica, 2024)

Mushroom poisoning of Panaeolus subbalteatus from Ningxia, northwest China, with species identification and tryptamine detection - Yi Yao; Yi-Zhe Zhang; Jia-Qi Liang; Feng Liu; Zhong-Feng Li; Hai-Jiao Li; Fei Xu (Toxicon, 2024)

Invasion of Trifolium repens L. aggravated by biodegradable plastics: adjustable strategy for foraging N and P - Mengfei Tian; Bin Qiao; Ziqi Xu; Qi Liang; Xiaofei Xie; Kuiwang Chen; Yaru Zhang; Chunjian Zhao; Chunying Li (Journal of Hazardous Materials, 2024)

Engineering marine phospholipid nanoliposomes via glycerol-infused proliposomes: Mechanisms, strategies, and versatile applications in scalable food-grade nanoliposome production - Dong-wen Fu; Hang Xu; Rui-qi Sun; Xue-li Liu; Zhe Ji; Da-yong Zhou; Liang Song (Food Chemistry, 2024)

A degradable multi-functional packaging based on chitosan/silk fibroin via incorporating cellulose nanocrystals-stabilized cinnamon essential oil pickering emulsion - Jian-Dong Wang; Shi-Liang Yang; Guo-Sheng Liu; Quan Zhou; Li-Na Fu; Qi Gu; Zi-Hui Cai; Su Zhang; Yu-Jie Fu (Food Hydrocolloids, 2024)

Characterization, hazard identification, and risk assessment of volatile organic compounds in Poly(butylene adipate-co-terephthalate)-based food contact articles - Hanke Li; Hongjian Miao; Lichang Chen; Qi-Zhi Su; Zhenwei Liu; Canghao Xie; Jinxin Liang; Siliang Wu; An-Qi Cui; Can Xu; Ben Dong; Dan Li; et al. (Food and Chemical Toxicology, 2024)

Ammonia detection based on Pd/Rh-GaN and recognition of disease markers of nitrogen compounds assistant by deep learning - Jiexu Shi; Dan Han; Yuxuan Wang; Qi Duan; Hongwei Li; Xiaqin Zhang; Hua Liang; Shengbo Sang (Chemical Engineering Journal, 2024)

Distribution, risk evaluation, and source allocation of cesium and strontium in surface soil in a mining city - Jia-li Li; Chun-dan Gan; Xin-yue Du; Xue-ying Yuan; Wen-lin Zhong; Meng-qi Yang; Rui Liu; Xiao-yu Li; Hao Wang; Yu-liang Liao; Zheng Wang; Mu-cheng Xu; et al. (Environmental Geochemistry and Health, 2024)

Establishment of an efficient regeneration system and in vitro polyploid induction based on the bulblet centre in Lilium rosthornii Diels - Yongyao Fu; Xiaomeng Liang; Hong Zhang; Shiyuan Cheng; Anqin Li; Minjing Liao; Lang Tan; Liping Yang; Xiangying Qi (In Vitro Cellular & Developmental Biology - Plant, 2024)

Identifying the Interaction Between Tuberculosis and SARS-CoV-2 Infections via Bioinformatics Analysis and Machine Learning - Ze-Min Huang; Jia-Qi Kang; Pei-Zhen Chen; Lin-Fen Deng; Jia-Xin Li; Ying-Xin He; Jie Liang; Nan Huang; Tian-Ye Luo; Qi-Wen Lan; Hao-Kai Chen; Xu-Guang Guo (Biochemical Genetics, 2024)

A synthetic TLR4 agonist significantly increases humoral immune responses and the protective ability of an MDCK-cell-derived inactivated H7N9 vaccine in mice - Jian Luo; Min Zhang; Qian Ye; Feixia Gao; Wenting Xu; Beibei Li; Qi Wang; Liang Zhao; Wen-Song Tan (Archives of Virology, 2024)

Caspase-12 is Expressed in Purkinje Neurons and Prevents Psychiatric-Like Behavior in Mice - Lin-Yan Huang; Yi-Ning Liu; Jie Chen; Hai-Xue Zhu; Li-Li Li; Zhi-Yan Liang; Jin-Xiu Song; Yu-Jie Li; Zhao-Li Hu; Dieter Demon; Andy Wullaert; Wan Wang; et al. (Molecular Neurobiology, 2024)

An enhanced sparrow search swarm optimizer via multi-strategies for high-dimensional optimization problems - Shuang Liang; Minghao Yin; Geng Sun; Jiahui Li; Hongjuan Li; Qi Lang (Swarm and Evolutionary Computation, 2024)

Tomato NAC transcription factor NOR-like1 positively regulates tomato fruit softening - Zhen-Zhen Peng; Hong-Li Li; Gang-Shuai Liu; Xiao Su; Xiaodan Zhao; Donald Grierson; Lan-Ting Xiang; Jian-Lin He; Gui-Qin Qu; Hong-Liang Zhu; Ben-Zhong Zhu; Yun-Bo Luo; et al. (Postharvest Biology and Technology, 2024)

Analysis of relationship between mixed heavy metal exposure and early renal damage based on a weighted quantile sum regression and Bayesian kernel machine regression model - Qi An; Qingyao Wang; Rujie Liu; Jiachen Zhang; Shuangjing Li; Weitong Shen; Han Zhou; Yufen Liang; Yang Li; Lina Mu; Lijian Lei (Journal of Trace Elements in Medicine and Biology, 2024)

Characteristics of zero-valent iron surface oxide films under the catalytic interface reactions by assisting ligands in nitrate-contaminated groundwater - Wen Zhang; Liang Qi; Ling Li; Chengchen Guo; Liwen Xiao (Journal of Hazardous Materials, 2024)

Characterization and modulation of the unimolecular conformation of integrins with nanopore sensors - Rongjie Li; Daixin Liu; Meili Ren; Fupeng Qin; Guodong Qi; Dawei Tian; Mingkun Zhang; Wanyi Xie; Liang Wang; Shouqin Lü; Deqiang Wang; Jun Pan; et al. (Chemical Engineering Journal, 2024)

Dual response Hst1@CBTC hydrogel promoting diabetic wounds healing by improving mitochondrial autophagy and inhibiting ferroptosis via Nrf2/HO-1 - Shuyun Zhang; Bohua Peng; Yong Qi; Changpeng Xu; Yan Wang; Tinghui Xian; Jie Huang; Lin Liang; Zhen Lin; Hao Wu; Lihua Li (Chemical Engineering Journal, 2024)

Porous molecularly imprinted beads for highly specific separation of 10-hydroxycamptothecine: An imprinted strategy based on modified cellulose hydrogel - Zidan Luo; Mengfei Tian; Shuo Liu; Qi Liang; Yaru Zhang; Xiaofei Xie; Yu Zhang; Ziqi Xu; Chunying Li; Chunjian Zhao (Chemical Engineering Journal, 2024)

sp2-c linked Cu-based metal-covalent organic framework for chemical and photocatalysis synergistic reduction of uranium - Jin-Lan Liu; Mu-Xiang Lin; Juan Huang; Cheng-Rong Zhang; Jia-Xin Qi; Yuan-Jun Cai; Xiao-Juan Chen; Li Zhang; Ru-Ping Liang; Jian-Ding Qiu (Chemical Engineering Journal, 2024)

Foxg1 Modulation of the Prkcd Gene in the Lateral Habenula Mediates Trigeminal Neuralgia-Associated Anxiety-Like Behaviors in Mice - Abudula Aji; Chen Zhang; Wenbo Liu; Teng Chen; Zhechen Liu; Jiaxin Zuo; Haojun Li; Wenli Mi; Qi-Liang Mao-Ying; Yanqing Wang; Qing Zhao; Yu-Xia Chu (Molecular Neurobiology, 2024)

Exendin-4 blockade of T1R2/T1R3 activation improves Pseudomonas aeruginosa-related pneumonia in an animal model of chemically induced diabetes - Shanjun Yu; Chaoqun Xu; Xiang Tang; Lijun Wang; Lihua Hu; Liang Li; Xiangdong Zhou; Qi Li (Inflammation Research, 2024)
Objective Poorly controlled diabetes frequently exacerbates lung infection, thereby complicating treatment strategies. Recent studies have shown that exendin-4 exhibits not only hypoglycemic but also anti-inflammatory properties. This study aimed to explore the role of exendin-4 in lung infection with diabetes, as well as its association with NOD1/NF-κB and the T1R2/T1R3 sweet taste receptor. Methods 16HBE human bronchial epithelial cells cultured with 20 mM glucose were stimulated with lipopolysaccharide (LPS) isolated from Pseudomonas aeruginosa (PA). Furthermore, Sprague‒Dawley rats were fed a high-fat diet, followed by intraperitoneal injection of streptozotocin and intratracheal instillation of PA. The levels of TNF-α, IL-1β and IL-6 were evaluated using ELISAs and RT‒qPCR. The expression of T1R2, T1R3, NOD1 and NF-κB p65 was assayed using western blotting and immunofluorescence staining. Pathological changes in the lungs of the rats were observed using hematoxylin and eosin (H&E) staining. Results At the same dose of LPS, the 20 mM glucose group produced more proinflammatory cytokines (TNF-α, IL-1β and IL-6) and had higher levels of T1R2, T1R3, NOD1 and NF-κB p65 than the normal control group (with 5.6 mM glucose). However, preintervention with exendin-4 significantly reduced the levels of the aforementioned proinflammatory cytokines and signaling molecules. Similarly, diabetic rats infected with PA exhibited increased levels of proinflammatory cytokines in their lungs and increased expression of T1R2, T1R3, NOD1 and NF-κB p65, and these effects were reversed by exendin-4. Conclusions Diabetic hyperglycemia can exacerbate inflammation during lung infection, promote the increase in NOD1/NF-κB, and promote T1R2/T1R3. Exendin-4 can ameliorate PA-related pneumonia with diabetes and overexpression of NOD1/NF-κB. Additionally, exendin-4 suppresses T1R2/T1R3, potentially through its hypoglycemic effect or through a direct mechanism. The correlation between heightened expression of T1R2/T1R3 and an intensified inflammatory response in lung infection with diabetes requires further investigation.

Determination of optimal temperature, salinity, and stocking density combinations for larval growth and survival of diploid, triploid, and tetraploid Fujian oyster (Crassostrea angulata) - Yuanxin Liang; Xianchao Bai; Chengxun Xu; Qi Li (Aquaculture, 2024)

Characterization and elimination efficiency of volatile organic compounds in mechanically recycled polyethylene terephthalate at various recycling stages - Siliang Wu; Dan Li; Hanke Li; Qi-zhi Su; Jinxin Liang; Jianguo Zheng; Huai-ning Zhong; Ben Dong (Waste Management, 2024)

A novel histone deacetylase inhibitor Se-SAHA attenuates isoproterenol-induced heart failure via antioxidative stress and autophagy inhibition - Tianwei Cheng; Chang Liu; Yufei Wang; Guangru Li; Lifeng Feng; Shengzheng Zhang; Bing Qi; Jianlin Cui; Lihong Guo; Lei Cao; Yanming Wang; Zhi Qi; et al. (Toxicology and Applied Pharmacology, 2024)

Inorganic carbon limitation decreases ammonium removal and N2O production in the algae-nitrifying bacteria symbiosis system - Qi Li; Yifeng Xu; Shi Chen; Chuanzhou Liang; Wenshan Guo; Huu Hao Ngo; Lai Peng (Science of The Total Environment, 2024)

A dynamic risk assessment model based on multidimensional and quantitative inference theory - Qi Jing; Guang Yang; Chao-ke Shi; Yun-tao Li; Guo-hua Luan; Xin Li; Tao Liang (Process Safety and Environmental Protection, 2024)

Photocatalytic degradation of organic pollutants in sewage using CeO2/ZnO 3D nanoflowers - Junzi Huang; Mengjie Lu; Peng Wei; Yahong Xie; Huihui Xie; Min Liu; Liang Li; Jindou Hu; Zhiwei Zhang; Ying Qi (Journal of Environmental Chemical Engineering, 2024)

Reinforcing the efficiency of photocatalytic CO2 conversion with H2O vapor through the integration of photothermal Cu/C@Bi/C supported on 3D g-C3N4 under full-spectrum solar irradiation - Yanan Wang; Jiayu Ding; Qi Yin; Cheng Zhang; Yiqing Zeng; Song Xu; Qian Liang; Man Zhou; Zhongyu Li (Journal of Environmental Chemical Engineering, 2024)

Enhancing hydrological extremes prediction accuracy: Integrating diverse loss functions in Transformer models - Xue Li; Qi-Liang Sun; Yanfei Zhang; Jian Sha; Man Zhang (Environmental Modelling & Software, 2024)

C@MOF composite material for rapid and efficient capture of gaseous iodine - Rui-Li Yu; Mei-Qi Sun; Xiao-Yu Wang; Dao-Tong Li; Zhen-Le Li; Liang-Zhi Xia (Chemical Engineering Journal, 2024)

Variability in morphology of soot particles during non-cloud and in-cloud processes - Yuanyuan Wang; Liang Xu; Zexuan Zhang; Jian Zhang; Lei Liu; Yinxiao Zhang; Yuner Pang; Qi Yuan; Pingqing Fu; Dantong Liu; Weijun Li (Atmospheric Environment, 2024)

Identification of candidate genes for Fusarium head blight resistance from QTLs using RIL population in wheat - Mingxia Zhang; Peng Jiang; Qun Wu; Xu Han; Junxia Man; Junsheng Sun; Jinlong Liang; Jingchuan Chen; Qi Zhao; Ying Guo; Yanrong An; Haiyan Jia; et al. (Plant Molecular Biology, 2024)

Viperin inhibits interferon-γ production to promote Mycobacterium tuberculosis survival by disrupting TBK1-IKKε-IRF3-axis and JAK-STAT signaling - Yao Liang; Yun Liang; Qi Wang; Qianna Li; Yingqi Huang; Rong Li; Xiaoxin Pan; Linmiao Lie; Hui Xu; Zhenyu Han; Honglin Liu; Qian Wen; et al. (Inflammation Research, 2024)
Objectives and design As an interferon-inducible protein, Viperin has broad-spectrum antiviral effects and regulation of host immune responses. We aim to investigate how Viperin regulates interferon-γ (IFN-γ) production in macrophages to control Mycobacterium tuberculosis (Mtb) infection. Methods We use Viperin deficient bone-marrow-derived macrophage (BMDM) to investigate the effects and machines of Viperin on Mtb infection. Results Viperin inhibited IFN-γ production in macrophages and in the lung of mice to promote Mtb survival. Further insight into the mechanisms of Viperin-mediated regulation of IFN-γ production revealed the role of TANK-binding kinase 1 (TBK1), the TAK1-dependent inhibition of NF-kappa B kinase-epsilon (IKKε), and interferon regulatory factor 3 (IRF3). Inhibition of the TBK1-IKKε-IRF3 axis restored IFN-γ production reduced by Viperin knockout in BMDM and suppressed intracellular Mtb survival. Moreover, Viperin deficiency activated the Janus kinase (JAK)-signal transducer and activator of transcription (STAT) signaling pathway, which promoted IFN-γ production and inhibited Mtb infection in BMDM. Additionally, a combination of the anti-TB drug INH treatment in the absence of Viperin resulted in further IFN-γ production and anti-TB effect. Conclusions This study highlights the involvement of TBK1-IKKε-IRF3 axis and JAK-STAT signaling pathways in Viperin-suppressed IFN-γ production in Mtb infected macrophages, and identifies a novel mechanism of Viperin on negatively regulating host immune response to Mtb infection.

Effects of fuel and driving conditions on particle number emissions of China-VI gasoline vehicles: based on corrections to test results - Xiaohan Miao; Xin Zhang; Chang Wang; Jingyuan Li; Jie Zhao; Liang Qu; Yu Liu; Songbo Qi; Honglin Li; Mengqi Fu; Taosheng Jin (Environmental Monitoring and Assessment, 2024)

Culture of cerebrospinal fluid-contacting neurons from neonatal mouse spinal cord - Liang Cao; Hui-Qian Zhang; Yu-Qi He; Ping-Jiang An; Lei-Luo Yang; Wei Tan; Gang Liu; Chun-Qing Wang; Xiao-Wei Dou; Qing Li (Cell and Tissue Banking, 2024)

Isolation, identification, and tolerance analysis of yeast during the natural fermentation process of Sidamo coffee beans - Bei-Bei Ying; Jian Cai; Xiu Gao; Li-Fang Zhang; Qing-Fang Xu; Qi-He Xu; Wei-Liang Liu; Xian-Min Huang; Yu-Chen Wang; Ling Zhu (Archives of Microbiology, 2024)

Combined effects of temperature, salinity and rearing density on the larval growth and survival of the diploid, triploid and tetraploid of the Pacific oyster Crassostrea gigas - Xianchao Bai; Yuanxin Liang; Haining Zhang; Geng Cheng; Chengxun Xu; Qi Li (Aquaculture, 2024)

Hepatic injury and ileitis associated with gut microbiota dysbiosis in mice upon F–53B exposure - Shenpan Li; LuYin Wu; HuiXian Zeng; Jing Zhang; ShuangJian Qin; Li-Xia Liang; John Andersson; Wen-Jie Meng; Xing-Yu Chen; Qi-Zhen Wu; Li-Zi Lin; Wei-Chun Chou; et al. (Environmental Research, 2024)

Simultaneous removal of As(V) and sulfamethazine from water in FeS2-H2O2 system - Wen Li; Shanshan Yang; Shuiyu Sun; Tianming Wang; Qi Yao; Jingyi Zhan; Shanwen Ye; Yating Liang; Yunzhuo Deng; Wenxiang Wang; Hongsheng Fang; Yunmei Cai (Chemical Engineering Journal, 2024)

An Hsp70 promoter–based mouse for heat shock–induced gene modulation - Hangang Chen; Yangli Xie; Mei Zhang; Junlan Huang; Wanling Jiang; Ruobin Zhang; Can Li; Xiaolan Du; Hua Chen; Qiang Nie; Sen Liang; Qiaoyan Tan; et al. (Journal of Molecular Medicine, 2024)

Cost-effectiveness of latent tuberculosis infection testing and treatment with 6-week regimen among key population in rural communities in China: a decision analysis study - Xuefang Cao; Tonglei Guo; Henan Xin; Jiang Du; Chenlu Yang; Boxuan Feng; Yijun He; Lingyu Shen; Yuanzhi Di; Zihan Li; Yanxiao Chen; Jianguo Liang; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2024)

Correction to: BMP2 induces chondrogenic differentiation, osteogenic differentiation and endochondral ossification in stem cells - Nian Zhou; Qi Li; Xin Lin; Ning Hu; Jun-Yi Liao; Liang-Bo Lin; Chen Zhao; Zhen-Ming Hu; Xi Liang; Wei Xu; Hong Chen; Wei Huang (Cell and Tissue Research, 2024)

Partial denitrifying phosphorus removal coupling with anammox (PDPRA) enables synergistic removal of C, N, and P nutrients from municipal wastewater: A year-round pilot-scale evaluation - Qi Zhao; Xiyao Li; Liang Zhang; Jianwei Li; Tipei Jia; Yang Zhao; Luyao Wang; Yongzhen Peng (Water Research, 2024)

Structurally diverse cucurbitane-type triterpenoids from the tubers of Hemsleya chinensis with cytotoxic activity - Xiao-San Li; Qi-Lin Wang; Zhi-Peng Xu; Ming-Shang Liu; Xiao-Yan Liang; Jia-Chon Zheng; Hong-Yao Deng; Li Liu; Yong-Mei Huang; Mao-Xun Yang; Xue-Mei Yang (Phytochemistry, 2024)

Potential safety concerns of volatile constituents released from coffee-ground-blended single-use biodegradable drinking straws: A chemical space perspective - Hanke Li; Qi-zhi Su; Jinxin Liang; Hongjian Miao; Zhongming Jiang; Siliang Wu; Ben Dong; Canghao Xie; Dan Li; Tongmei Ma; Xiaoxia Mai; Sheng Chen; et al. (Journal of Hazardous Materials, 2024)

Fast pyrolysis of Enteromorpha prolifera model compounds for syngas: A simulated and experimental study - Zhaoying Li; Jinfu Lyu; Hao Qi; Daokuan Liang; Xiaofeng Li; Haoxi Ben; Lianghuan Wei; Qirong Yang (Journal of Environmental Chemical Engineering, 2024)

Deoxynivalenol Damages Corneal Epithelial Cells and Exacerbates Inflammatory Response in Fungal Keratitis - Qi Shi; QingQing Li; Changlin Wu; Shisi Ma; Chunlan Liang; Xiaoyi Fan; Jingxiang Zhong; Lian Liu (Mycopathologia, 2024)

Remote effects of Tibetan Plateau spring land temperature on global subseasonal to seasonal precipitation prediction and comparison with effects of sea surface temperature: the GEWEX/LS4P Phase I experiment - Yongkang Xue; Ismaila Diallo; Aaron A. Boone; Yang Zhang; Xubin Zeng; William K. M. Lau; J. David Neelin; Tandong Yao; Qi Tang; Tomonori Sato; Myung-Seo Koo; Frederic Vitart; et al. (Climate Dynamics, 2024)
The prediction skill for precipitation anomalies in late spring and summer months—a significant component of extreme climate events—has remained stubbornly low for years. This paper presents a new idea that utilizes information on boreal spring land surface temperature/subsurface temperature (LST/SUBT) anomalies over the Tibetan Plateau (TP) to improve prediction of subsequent summer droughts/floods over several regions over the world, East Asia and North America in particular. The work was performed in the framework of the GEWEX/LS4P Phase I (LS4P-I) experiment, which focused on whether the TP LST/SUBT provides an additional source for subseasonal-to-seasonal (S2S) predictability. The summer 2003, when there were severe drought/flood over the southern/northern part of the Yangtze River basin, respectively, has been selected as the focus case. With the newly developed LST/SUBT initialization method, the observed surface temperature anomaly over the TP has been partially produced by the LS4P-I model ensemble mean, and 8 hotspot regions in the world were identified where June precipitation is significantly associated with anomalies of May TP land temperature. Consideration of the TP LST/SUBT effect has produced about 25–50% of observed precipitation anomalies in most hotspot regions. The multiple models have shown more consistency in the hotspot regions along the Tibetan Plateau-Rocky Mountain Circumglobal (TRC) wave train. The mechanisms for the LST/SUBT effect on the 2003 drought over the southern part of the Yangtze River Basin are discussed. For comparison, the global SST effect has also been tested and 6 regions with significant SST effects were identified in the 2003 case, explaining about 25–50% of precipitation anomalies over most of these regions. This study suggests that the TP LST/SUBT effect is a first-order source of S2S precipitation predictability, and hence it is comparable to that of the SST effect. With the completion of the LS4P-I, the LS4P-II has been launched and the LS4P-II protocol is briefly presented.

A design of a nature-like fishway to solve the fractured river connectivity caused by small hydropower based on hydrodynamics and fish behaviors - Jianing Rao; Qi Wei; Lian Tang; Yuanming Wang; Ruifeng Liang; Kefeng Li (Environmental Science and Pollution Research, 2024)

Transforming waste brake pads from automobiles into Nano-Catalyst: Synergistic Fe-C-Cu triple sites for efficient fenton-like oxidation of organic pollutants - Fuyuan Qi; Jianfei Peng; Zilu Liang; Jiliang Guo; Jiawei Yin; Ainan Song; Zongxuan Li; Jiayuan Liu; Tiange Fang; Jinsheng Zhang; Lin Wu; Qijun Zhang; et al. (Waste Management, 2024)

Active dark carbon fixation evidenced by 14C isotope assimilation and metagenomic data across the estuarine-coastal continuum - Bolin Liu; Yanling Zheng; Xinyu Wang; Lin Qi; Jie Zhou; Zhirui An; Li Wu; Feiyang Chen; Zhuke Lin; Guoyu Yin; Hongpo Dong; Xiaofei Li; et al. (Science of The Total Environment, 2024)

Morphology control of Co3O4/CeO2 heterojunctions toward efficient peroxymonosulfate activation for trichloroethylene removal: Effect of oxygen precursors - Xuetao Liang; Yanxiang Li; Longyan Cui; Qi Yang (Journal of Water Process Engineering, 2024)

Efficient capture of iodine in steam and water media by hydrogen bond-driven charge transfer complexes - Li Zhang; Yu-Ting Luo; Jia-Qi Fan; Sai-Jin Xiao; Qiong-Qing Zheng; Xiao-Lin Liu; Quan-Gen Tan; Chen Sun; Qiang Shi; Ru-Ping Liang; Jian-Ding Qiu (Journal of Hazardous Materials, 2024)

Mechanistic investigation of an inorganic-organic hybrid coagulant with Fe3O4 magnetic loading-enhanced flocculation for water treatment - Yuansong Tian; Qi Li; Guizhou Xu; Yalan Zhang; Yizhou Tu; Zhengyu Jin; Ying Liang; Yongdong Zhang; Jianjun Dai; Xianchuan Xie (Journal of Cleaner Production, 2024)

Regulatory effect of trehalose metabolism on chitin synthesis in Spodoptera frugiperda (J. E. Smith) (Lepidoptera: Noctuidae) as determined using RNAi - Yan-qi Yang; Yu-jian Liang; Jun-rui Zhi; Ding-yin Li; Cao Li (Journal of Asia-Pacific Entomology, 2024)

The multifunctionality of soil aggregates is related to the complexity of aggregate microbial community during afforestation - Qi Zhang; Hanyu Liu; Yueqi Liang; Yaoyue Liang; Yongtao Zhao; Zhengchen Wang; Yuze Li; Weichao Liu; Xing Wang; Gaihe Yang; Chengjie Ren; Wei Zhang; et al. (CATENA, 2024)

Removal of Bismuth from Water by Orange Peel Biochar - Adil Abbas Kareem; Yu-liang Liao; Ya-qi Yu; Ning Ning; Shan-shan Guo; Qiao-yu Song; Jia-li Li; Jin-yan Yang (Water, Air, & Soil Pollution, 2024)

PHLDA1 is a P53 target gene involved in P53-mediated cell apoptosis - Xuhong Song; Lulu Zhou; Wenrui Yang; Xinyan Li; Jiazi Ma; Kun Qi; Rui Liang; Meijing Li; Lingzhu Xie; Tin Su; Dongyang Huang; Bin Liang (Molecular and Cellular Biochemistry, 2024)

Bioethanol Production from Alkali-Treated Corn Stover via Acidic Adjustment by Furfural Residue - Mengxuan Zhang; Yunyun Liu; Wentao Li; Wen Wang; Cuiyi Liang; Yu Zhang; Bao Jia; Wei Qi (BioEnergy Research, 2024)

Seasonal variation and dissolved organic matter influence on the distribution, transformation, and environmental risk of pharmaceuticals and personal care products in coastal zone: A case study of Tianjin, China - Wenrui Yao; Yulin Qi; Yufu Han; Jinfeng Ge; Yuanyuan Dong; Jianwen Wang; Yuanbi Yi; Dietrich A. Volmer; Si-Liang Li; Pingqing Fu (Water Research, 2024)

Occurrence, seasonal variation and gas/particle partitioning of current used pesticides (CUPs) across 60 °C temperature and 30° latitudes in China - Liang Wang; Gang Cao; Zi-Feng Zhang; Li-Yan Liu; Shi-Ming Jia; Meng-Qi Fu; Wan-Li Ma (Journal of Hazardous Materials, 2024)

Domain-limited thermal transformation preparation of novel graphitized carbon-supported layered double oxides for efficient tetracycline degradation - Si Wu; Huicong Liang; Kexin Sun; Zexin Li; Mingzhi Hu; Liqi Wang; Lili Yang; Qiang Han; Qi Zhang; Jihui Lang (Journal of Environmental Management, 2024)

Improved tolerance capacity and expression of degradation genes drive efficient removal of sulfamethizole by Chlorella pyrenoidosa - Ying Liang; Xin Qi; Jia-Min Xu; Mayur B. Kurade; Byong-Hun Jeon; Li-Qiang Yang; Jiu-Qiang Xiong (Journal of Environmental Chemical Engineering, 2024)

Changes of sediment provenance driven by the sea level and Indian summer monsoon in the northern Ninetyeast Ridge over the past 50 kyr - Wenjing Qi; Shengfa Liu; Xiaoyan Li; Hui Zhang; Peng Cao; Xuefa Shi; Dejiang Fan; Zhengxin Yin; Liang Chen (Journal of Asian Earth Sciences, 2024)

Numerical investigation of the tensile behaviors of needle-punched nonwoven geotextiles - Ke-Yi Li; Xiao-Wu Tang; Min-Liang Fei; Qing-Qing Xiang; Tian-Qi Wang (Geotextiles and Geomembranes, 2024)

Straw management in paddy fields can reduce greenhouse gas emissions: A global meta-analysis - Zijian He; Hongxia Cao; Chen Qi; Qingyang Hu; Jiaping Liang; Zhijun Li (Field Crops Research, 2024)

Crystal defect engineering to construct oxygen vacancies in MXene-derived TiO2 nanocomposites for boosting photocatalytic degradation of 2,4,6-trichlorophenol - Feihong Wang; Qi Zhao; Hongpeng Li; Qiangshun Wu; Luyan Zhang; Yan Li; Liang Qiao; Ye Yuan; Jun Ma; Panpan Wang; Tianming Chen (Chemical Engineering Journal, 2024)

Correlational analysis of physicochemical indexes, microbial communities, and volatile components in light-flavor Daqu from north and south regions of China - Qi Yu; Feiyan Mou; Junwen Xiao; Cheng Zhan; Liang Li; Xu Chang; Xiaoyuan Dong; Maobin Chen; Xinrui Wang; Mei Chen; Shangling Fang (World Journal of Microbiology and Biotechnology, 2024)

Effects of Brown Fishmeal on Growth Performance, Digestibility, and Lipid Metabolism of the Chinese Soft-Shelled Turtle (Pelodiscus sinensis) - Guo-Fang Zhong; Liang-Fa Zhang; Yi Zhuang; Qi Li; He Huang; Cong Cao; Zhan-Ying Zhu; Zhong-Yuan Huang; Nu-An Wang; Kun Yuan (Marine Biotechnology, 2024)

Comparative study on tetraploid induction of the Fujian oyster Crassostrea angulata utilizing three typical methods - Yuanxin Liang; Geng Cheng; Xianchao Bai; Jianmin Zhou; Haining Zhang; Yong Chi; Gaowei Jiang; Chengxun Xu; Qi Li (Aquaculture International, 2024)

Role of sleep in asthenospermia induced by di (2-ethyl-hexyl) phthalate - Xiao-lu Li; Xiao-yue Cai; Xia Ning; Yue-yue Liang; Yun Hong; Qi-meng Li; Die Hu; Yuan-zhuo Zheng; Yang Cai; Tao Xu; Ling-li Zhao (Environmental Science and Pollution Research, 2024)

Three new cardenolides from the fruits of Cascabela thevetia (L.) Lippold and their cytotoxic activities - Juan Long; Jia-Cheng Ouyang; Yu-Hao Luo; Qi-Jing Wu; Xiao-Tong Liao; Zhi-Le Chen; Qi-Lin Wang; Xiao-Yan Liang; Li Liu; Xue-Mei Yang; Xiao-San Li (Natural Product Research, 2024)

Eliminating senescent cells by white adipose tissue–targeted senotherapy alleviates age-related hepatic steatosis through decreasing lipolysis - Qi Tang; Xiaotao Xing; Haisen Huang; Jian Yang; Maojiao Li; Xun Xu; Xin Gao; Cheng Liang; Weidong Tian; Li Liao (GeroScience, 2024)

MSWIFA and cement cooperate in the disposal of soft soil — experimental study on silty sand and silty clay - Zong-Hui Liu; Jia-Qi Li; Xiao-Lei Zhang; Hao-Dong Li; Dong-Po Su; Jia-Wei Liang (Environmental Science and Pollution Research, 2024)

Constructing a novel type-Ⅱ ZnO/BiOCOOH heterojunction microspheres for the degradation of tetracycline and bacterial inactivation - Min Liu; Junzi Huang; Huihui Xie; Liang Li; Weitao Han; Xinhui Jiang; Jide Wang; Peng Wei; Yahong Xie; Ying Qi (Chemosphere, 2024)

Chlorogenic acid ameliorates the heat stress-induced impairment of porcine Sertoli cells by suppressing oxidative stress and apoptosis - Shao-Xuan Zhang; Da-Li Wang; Jia-Jia Qi; Yu-Wei Yang; Hao Sun; Bo-Xing Sun; Shuang Liang (Theriogenology, 2024)

Spatial-temporal variation of soil organic matter decomposition potential in China - Qi Chen; Zeyan Zhou; Sulin Cai; Meiqi Lv; Yinghui Yang; Yunchao Luo; Han Jiang; Run Liu; Tingting Cao; Bei Yao; Yunru Chen; Qiang Li; et al. (Soil and Tillage Research, 2024)

Optimizing biochar application rates for improved soil chemical environments in cotton and sugarbeet fields under trickle irrigation with plastic mulch - Xingyun Qi; Guang Yang; Yi Li; Zhenan Hou; Penghui Shi; Shibin Wang; Xiaofang Wang; Jiaping Liang; Benhua Sun; Kadambot H.M. Siddique; Shufang Wu; Hao Feng; et al. (Soil and Tillage Research, 2024)

A kinetic model for porosity evaluation in Fe(0) mixed material-based sequential groundwater remediation - Wen Zhang; Liang Qi; Dunzhu Li; Liwen Xiao (Science of The Total Environment, 2024)

Aridity drives the variability of desert soil microbiomes across north-western China - Lei Dong; Mei-Xiang Li; Shuai Li; Ling-Xiang Yue; Mukhtiar Ali; Jia-Rui Han; Wen-Hui Lian; Chao-Jian Hu; Zhi-Liang Lin; Guo-Yuan Shi; Pan-Deng Wang; Shao-Ming Gao; et al. (Science of The Total Environment, 2024)

Pipeline sharing: Boosting multi-product pipeline transport biofuels in the shift to low-carbon energy - Renfu Tu; Hao Zhang; Siyuan Xu; Guangtao Fu; Zhengbing Li; Qi Liao; Jian Du; Yongtu Liang (Journal of Cleaner Production, 2024)

Monolithic melamine foam@COF composite: Preparation, characterization and applications in ultrafast removal and on-site quick assessment of Cd2+ pollution - Wei Li; Yue-Lei Hao; Wei-Liang Jin; Jing-Qi Liu; An-Na Tang; Li-Na Zhu; Hong-Xin Jiang; De-Ming Kong (Journal of Cleaner Production, 2024)

Stable carbon isotopes and stomatal frequency of Middle Jurassic ginkgophyte fossils from the Turpan basin, northwestern China: Implications for reconstructing paleo-CO2 changes - Liang Xiao; Jia-qi Liang; Li-yan Guo; De-shuang Ji; Man Yuan; Xiang-chuan Li; Nan Sun; Zuo-chen Li (Journal of Asian Earth Sciences, 2024)

Natural self-assembled supramolecules as green inhibitors against methane hydrate formation - Yanzhen Liu; Xin Lv; Qingping Li; Huiyong Liang; Fen Qiao; Junfeng Wang; Lei Yang; Yanbo Liu; Jiafei Zhao; Huiping Qi (Gas Science and Engineering, 2024)

Urban green, blue spaces and their joint effect are associated with lower risk of emotional and behavior problem in children and adolescents, a large population-based study in Guangzhou, China - Jing-hong Liang; Ru-yu Yang; Mei-ling Liu; Ying-qi Pu; Wen-wen Bao; Yu Zhao; Li-xin Hu; Yu-shan Zhang; Shan Huang; Nan Jiang; Xue-ya Pu; Shao-yi Huang; et al. (Environmental Research, 2024)

Dynamic relationship between membrane fouling and reverse diffusion of inorganic draw solutes in forward osmosis - Hai-Liang Song; Si-Qi Zhai; Jing Nan; Wen-Jun Cai; Shi-Yun Xu; Yue-Wei Tang; Yu-Li Yang (Desalination, 2024)

Soil pH differently affects N2O emissions from soils amended with chemical fertilizer and manure by modifying nitrification and denitrification in wheat-maize rotation system - Gong Wu; Fei Liang; Qi Wu; Xiao-Gang Feng; Wen-ding Shang; Hua-wei Li; Xiao-xiao Li; Zhao Che; Zhao-rong Dong; He Song (Biology and Fertility of Soils, 2024)

Nitrous oxide production from biological and chemodenitrification by Fe(II) in estuarine and coastal sediments - Mengting Qi; Dengzhou Gao; Hongpo Dong; Xia Liang; Zhao Song; Min Liu; Lijun Hou; Xiaofei Li (Applied Geochemistry, 2024)

Technological diversity in the tropical-subtropical zone of Southwest China during the terminal Pleistocene: excavations at Fodongdi Cave - Fa-Xiang Huan; Shi-Xia Yang; Feng Gao; Xin-Ying Zhou; Jian-Ping Yue; Yu-Xiu Zhang; Jin-Xu Wu; Qi-Jun Ruan; Kai-Wei Qiu; Jing-wen Xu; Nai-Ru Lin; Yi-Ren Wang; et al. (Archaeological and Anthropological Sciences, 2024)

The neglected roles of adjacent natural ecosystems in maintaining bacterial diversity in agroecosystems - Ziheng Peng; Yunfeng Yang; Yu Liu; Lianyan Bu; Jiejun Qi; Hang Gao; Shi Chen; Haibo Pan; Beibei Chen; Chunling Liang; Xiaomeng Li; Yining An; et al. (Global Change Biology, 2024)
A central aim of community ecology is to understand how local species diversity is shaped. Agricultural activities are reshaping and filtering soil biodiversity and communities; however, ecological processes that structure agricultural communities have often overlooked the role of the regional species pool, mainly owing to the lack of large datasets across several regions. Here, we conducted a soil survey of 941 plots of agricultural and adjacent natural ecosystems (e.g., forest, wetland, grassland, and desert) in 38 regions across diverse climatic and soil gradients to evaluate whether the regional species pool of soil microbes from adjacent natural ecosystems is important in shaping agricultural soil microbial diversity and completeness. Using a framework of multiscales community assembly, we revealed that the regional species pool was an important predictor of agricultural bacterial diversity and explained a unique variation that cannot be predicted by historical legacy, large‐scale environmental factors, and local community assembly processes. Moreover, the species pool effects were associated with microbial dormancy potential, where taxa with higher dormancy potential exhibited stronger species pool effects. Bacterial diversity in regions with higher agricultural intensity was more influenced by species pool effects than that in regions with low intensity, indicating that the maintenance of agricultural biodiversity in high‐intensity regions strongly depends on species present in the surrounding landscape. Models for community completeness indicated the positive effect of regional species pool, further implying the community unsaturation and increased potential in bacterial diversity of agricultural ecosystems. Overall, our study reveals the indubitable role of regional species pool from adjacent natural ecosystems in predicting bacterial diversity, which has useful implication for biodiversity management and conservation in agricultural systems.

Toxicologic effect and transcriptome analysis for sub-chronic exposure to carbendazim, prochloraz, and their combination on the liver of mice - Shuwen Zhang; Ting Luo; You Weng; Dou Wang; Li Sun; Zheping Yu; Yao Zhao; Senmiao Liang; Haiying Ren; Xiliang Zheng; Yuanxiang Jin; Xingjiang Qi (Environmental Science and Pollution Research, 2023)

Diversity and distribution of yeasts in intertidal zones of China - Hai-Yan Zhu; Da-Yong Han; Liang-Chen Guo; Jun-Ning Li; Xu-Yang Wei; Ri-Peng Zhang; Qi-Ming Wang; Yu-Jie Shang; Lu-Jun Luo; Yu-Hua Wei; Xin-Zhan Liu; Feng-Yan Bai (Frontiers in Marine Science, 2023)
China has the second greatest extent of intertidal zones in the world. The intertidal zone is the most dynamic environments in the biosphere and potentially supports high biodiversity. Marine yeasts show excellent performance in various industrial, environmental and medical applications, however, the marine yeast diversity has rarely been studied in China. In this study, we collected 1241 samples including marine sediments, marine water, plants, and benthos at 161 GPS sites in different types of intertidal zones along the Chinese coastline from north to south. A total of 4436 strains were isolated from these samples using different methods and 286 species including 39 potential novel species were identified from these strains based on the internal transcribed spacer (ITS) region or the D1/D2 domain of the large subunit rRNA gene sequence analysis. The majority of the yeast species in different geographical locations belong to the five orders Serinales , Saccharomycetales , Tremellales , Sporidiobolales , and Pichiales . The yeast species diversity varied depending on sample types, depth of marine sediments, intertidal zone types and geographical locations. Mean annual temperature (MAT), salinity and pH had the greatest effect on the community structures of the yeasts isolated from the intertidal zones. This study represents one of the most comprehensive surveys of marine yeasts in China to date and provides a better understanding of marine yeast diversity and distribution.

Formulation and stability study of vitamin E microemulsion with green surfactant - Yunqin Qi; Yuan Zhou; Xiuquan Yang; Jiahao Li; Liang Bai; Zhiyu Wu; Ziyu Qin (Sustainable Chemistry and Pharmacy, 2023)

Molecular and optical signatures of photochemical transformation of dissolved organic matter: Nonnegligible role of suspended particulate matter in urban river - Jingyi Hou; Ruochun Zhang; Jinfeng Ge; Chao Ma; Yuanbi Yi; Yulin Qi; Si-Liang Li (Science of The Total Environment, 2023)

The key role of ecological resilience in radial growth processes of conifers under drought stress in the subalpine zone of marginal deserts - Ruhong Xue; Liang Jiao; Peng Zhang; Dashi Du; Xuan Wu; Mengyuan Wei; Qian Li; Xuge Wang; Changliang Qi (Science of The Total Environment, 2023)

Increased productivity of temperate vegetation in the preceding year drives early spring phenology in the subsequent year in northern China - Qi Zhang; Hongfang Zhao; Wanying Cheng; Nan Cong; Xuhui Wang; Hangqi Liang; Xia Li (Science of The Total Environment, 2023)

Cross-regional scale studies of organochlorine pesticides in air in China: Pollution characteristic, seasonal variation, and gas/particle partitioning - Liang Wang; Gang Cao; Li-Yan Liu; Zi-Feng Zhang; Shi-Ming Jia; Meng-Qi Fu; Wan-Li Ma (Science of The Total Environment, 2023)

Two new eudesmane sesquiterpenoids with neuroprotective activity from Pogostemon cablin - Qi Zheng; Chuan Ma; Liang Xiong; Cheng Peng; Li Guo; Da-Le Guo; E Zhao; Qin-Mei Zhou; Ou Dai (Phytochemistry Letters, 2023)

Microbial mechanism of biochar addition to reduce N2O emissions from soilless substrate systems - Xiaofeng Liang; Wanlai Zhou; Rui Yang; Dongdong Zhang; Hong Wang; Qiaozhen Li; Zhiyong Qi; Yuzhong Li; Wei Lin (Journal of Environmental Management, 2023)

The regulatory effects of microbial community on the formation of higher alcohols and volatile flavor components in Hongqu rice wine brewing - Yujie Yuan; Ziyi Yang; Zihua Liang; Qi Wu; Yingyin Yan; Shiyun Chen; Xiangyou Li; Lianzhong Ai; Li Ni; Xucong Lv (Food Bioscience, 2023)

Triptolide induces PANoptosis in macrophages and causes organ injury in mice - Hong-Rui Zhang; Ya-Ping Li; Zi-Jian Shi; Qi-Qi Liang; Si-Yuan Chen; Yi-Ping You; Tao Yuan; Rong Xu; Li-Hui Xu; Dong-Yun Ouyang; Qing-Bing Zha; Xian-Hui He (Apoptosis, 2023)

Understanding the compound marine heatwave and low-chlorophyll extremes in the western Pacific Ocean - Qiaojun Chen; Delei Li; Jianlong Feng; Liang Zhao; Jifeng Qi; Baoshu Yin (Frontiers in Marine Science, 2023)
The western Pacific Ocean is the global center for marine biodiversity, with high vulnerability to climate change. A better understanding of the spatiotemporal characteristics and potential drivers of compound marine heatwaves (MHWs) and low-chlorophyll (LChl) extreme events is essential for the conservation and management of local marine organisms and ecosystems. Here, using daily satellite sea surface temperature and model-based chlorophyll concentration, we find that the climatological spatial distribution of MHW-LChl events in total days, duration, and intensity exhibits heterogeneous distributions. The southwest sections of the South China Sea (WSCS) and Indonesian Seas are the hotspots for compound events, with total MHW-LChl days that are more than 2.5 times higher than in the other sub-regions. Notably, there is a trend toward more frequent (> 4.2 d/decade), stronger (> 0.5), and longer-lasting (> 1.4 d/decade) MHW-LChl occurrences in the WSCS. The occurrence of compound MHW-LChl extremes exhibits remarkable seasonal differences, with the majority of these events transpiring during winter. Moreover, there are generally statistically significant increasing trends in MHW-LChl events for all properties on both seasonal and inter-annual timescales. Furthermore, we reveal that the total days of compound MHW-LChl extremes are strongly modulated by large-scale climate modes such as the El Niño-Southern Oscillation and Dipole Mode Index. Overall, pinpointing MHW-LChl hotspots and understanding their changes and drivers help vulnerable communities in better preparing for heightened and compounded risks to marine organism and ecosystems under climate change.

Machine learning framework for intelligent aeration control in wastewater treatment plants: Automatic feature engineering based on variation sliding layer - Yu-Qi Wang; Hong-Cheng Wang; Yun-Peng Song; Shi-Qing Zhou; Qiu-Ning Li; Bin Liang; Wen-Zong Liu; Yi-Wei Zhao; Ai-Jie Wang (Water Research, 2023)

Emerging organophosphate ester resorcinol bis(diphenyl phosphate) exerts estrogenic effects via estrogen receptor pathways - Yue Xie; Qi Zhang; Lu Chen; Fangfang Li; Minjie Li; Liang-Hong Guo (Toxicology, 2023)

Tidal dynamics regulates potential coupling of carbon‑nitrogen‑sulfur cycling microbes in intertidal flats - Yuhui Niu; Zhirui An; Dengzhou Gao; Feiyang Chen; Jie Zhou; Bolin Liu; Lin Qi; Li Wu; Zhuke Lin; Guoyu Yin; Xia Liang; Hongpo Dong; et al. (Science of The Total Environment, 2023)

Analysis of the spatial-temporal evolution of Green and low carbon utilization efficiency of agricultural land in China and its influencing factors under the goal of carbon neutralization - Jun Fu; Rui Ding; Yu-qi Zhu; Lin-yu Du; Si-wei Shen; Li-na Peng; Jian Zou; Yu-xuan Hong; Juan Liang; Ke-xin Wang; Wen-qian Xiao (Environmental Research, 2023)

Effects of rainfall pattern and soil surface roughness on surface–subsurface hydrological response and particle size distribution of red soil slope - Yichun Ma; Yaojun Liu; Liang Tian; Yifan Yang; Yu Long; Ming Lei; Ziwei Zhang; Qi Li; Huade Zhu; Zhongwu Li (CATENA, 2023)

Hydrogel bioreactor drives Feammox and synergistically removes composite pollutants: Performance optimization, microbial communities and functional genetic differences - Enlei Liang; Liang Xu; Junfeng Su; Yan Liu; Shangzhe Qi; Xuan Li (Bioresource Technology, 2023)

Experimental studies on active oxygen control performance of solid PbO mass exchanger in liquid lead–bismuth eutectic loop - Ruixian Liang; Huiping Zhu; Zhenhua Sheng; Xiaobo Li; Muran Qi; Yifeng Wang; Lingfeng Yang; Xu Tu; Hao Wu; Fang Liu; Zhangpeng Guo; Haicai Lyu; et al. (Annals of Nuclear Energy, 2023)

Synergistic impact of co-exposures to whole blood metals on chronic kidney disease in general US adults: a cross‑sectional study of the National Health and Nutrition Examination Survey 2011–2020 - Jing-hong Liang; Ying-qi Pu; Mei-ling Liu; Wen-wen Bao; Yu-shan Zhang; Li-xin Hu; Shan Huang; Nan Jiang; Shao-yi Huang; Xue-ya Pu; Guang-hui Dong; Ya-jun Chen (Environmental Science and Pollution Research, 2023)

Gravity-driven membrane system treating heavy metals-containing secondary effluent: Improved removal of heavy metals and mechanism - Xiaobin Ma; Yanrui Wang; Le Tong; Jiaoying Luo; Rui Chen; Yuanxin Wang; Xishou Guo; Jinlong Wang; Zhiwei Zhou; Jingyao Qi; Guibai Li; Heng Liang; et al. (Chemosphere, 2023)

Spatiotemporal changes of coastal land use land cover and its drivers in Shanghai, China between 1989 and 2015 - Chen Meng; Caiyan Wu; Jiong Wu; Qi Zhang; Liang Xin; Junxiang Li; Dezhi Li; Conghe Song (Ocean & Coastal Management, 2023)

Cardiovascular effects of wearing respirators against particulate matter: A randomized crossover trial - Xin Meng; Meilin Yan; Meijie Jiang; Xueling Meng; Liang Qi; Xinyan Hu; Ruiwei Xu; Yunxiu Shi; Weiju Li; Shiyi Chen; Tong Zhu; Jing Deng; et al. (Science of The Total Environment, 2023)

Magnetic and geochemical scanning reveals growth history of marine ferromanganese crust on Detroit Seamount, northwest Pacific since the early Miocene - Liang Yi; Yibing Li; Pavel Mikhailik; Youqiang Qi; Chenglong Deng (Quaternary International, 2023)

Four previously undescribed diketopiperazines from marine fungus Aspergillus puniceus FAHY0085 and their effects on liver X receptor α - Qi Hong; Miao-Miao Guo; Jin Yang; Xing Wei; Li Liao; Xiu-Juan Xin; Di Zhang; Fa-Liang An (Phytochemistry, 2023)

Effects of dietary resveratrol supplementation in cattle on the anti-oxidative capacity and meat quality of beef steaks under high‑oxygen packaging - Ying Cui; Jiajing Qi; Jiqiang Li; Yimin Zhang; Xiaoyin Yang; Luo Xin; Lebao Niu; Baochen Xu; Zhanyu Qian; Lixian Zhu; Rongrong Liang (Meat Science, 2023)

Efficient denitrification of liquid digestate with its indigenous microflora - Yuxi Jin; Wen Wang; Wentao Li; Cuiyi Liang; Yunzi Hu; Yu Zhang; Bao Jia; Shanzhi Xin; Wei Qi (Journal of Environmental Chemical Engineering, 2023)

Activation of xanthine oxidase by 1,4-naphthoquinones: A novel potential research topic for diet management and risk assessment - Sicheng Liang; Li Liu; Bing He; Wenjing Zhao; Wei Zhang; Lijun Xiao; Mingming Deng; Xiaoling Zhong; Su Zeng; Xiaoyi Qi; Muhan Lü (Food Chemistry, 2023)

The effect of free ammonia on ammonium removal and N2O production in a consortium of microalgae and partial nitritation cultures - Lai Peng; Yujia Li; Qi Li; Chuanzhou Liang; Mahmoud Nasr; Yifeng Xu; Yiwen Liu; Yan Zhou (Chemical Engineering Journal, 2023)

Performance and microbial metabolic mechanism of imidacloprid removal in a microbial electrolysis cell-integrated adsorption biological coupling system - Xinjuan Li; Shuo Fan; Yunnan Zhang; Daoning Li; Chengyuan Su; Zhifei Qi; Huayu Liang; Shu Gao; Menglin Chen (Bioresource Technology, 2023)

Genesis of No. 2 orebody of the Jinchuan magmatic Ni-Cu-(PGE) sulfide deposit, NW China: New constraints from the newly discovered deep extension - Ting-Mao Long; Xie-Yan Song; Jian Kang; Qing-Lin Liang; Yong-Cai Wang; De-Xian Li; Qi-Xing Ai; Wen-De Suo; Jian-Quan Lu (Mineralium Deposita, 2023)

Sequencing and Bioinformatics analysis of lncRNA/circRNA-miRNA-mRNA in Glioblastoma multiforme - Renjie Wang; Qi Li; Xiaolei Chu; Nan Li; Haiqian Liang; Feng He (Metabolic Brain Disease, 2023)

Interspecific interactions between crops influence soil functional groups and networks in a maize/soybean intercropping system - Guizong Zhang; Hao Yang; Weiping Zhang; T. Martijn Bezemer; Wenju Liang; Qi Li; Long Li (Agriculture, Ecosystems & Environment, 2023)

Genetic diversity and structure in a selected strain of hybrid oysters between Crassostrea gigas and C. angulata evaluated from microsatellites and mitochondrial COI sequences - Gaowei Jiang; Yifei Zhang; Lijie Du; Yulu Chen; Yuanxin Liang; Yi Yu; Chengxun Xu; Qi Li (Aquaculture, 2023)

Growth, survival and color segregation of F2 hybrids between selected “Haida no.1” and Orange-shell lines of the Pacific oyster - Yuanxin Liang; Chengxun Xu; Qi Li (Aquaculture, 2023)

Current status of ecological compensation for Bohai Sea reclamation and management countermeasures - Wei Li; Qi Yue; Heng Hu; Liang Liu (Marine Policy, 2023)

Irrigation leads to new Se-toxicity paddy fields in and around typical Se-toxicity area - Yuanzhe Ma; Fei Zhou; Dasong Yu; Nanchun Zhang; Mingxing Qi; Yanan Li; Fuyong Wu; Dongli Liang (Science of The Total Environment, 2023)

Occurrence and transport of N-nitrosamines in the urban water systems of the Pearl River Delta, southern China - Wenwen Chen; Shengyang Li; Huanfang Huang; Yingjie Chen; Wei Chen; Yang Ding; Xiaoyu Yan; Yanpeng Liang; Kuang Cen; Shihua Qi (Science of The Total Environment, 2023)

Vegetation structural shift tells environmental changes on the Tibetan Plateau over 40 years - Yanfen Wang; Kai Xue; Ronghai Hu; Boyang Ding; Hong Zeng; Ruijin Li; Bin Xu; Zhe Pang; Xiaoning Song; Congjia Li; Jianqing Du; Xiuchun Yang; et al. (Science Bulletin, 2023)

Multi-sensor imaging of winter buried lakes in the Greenland Ice Sheet - Lei Zheng; Lanjing Li; Zhuoqi Chen; Yong He; Linshan Mo; Dairong Chen; Qihan Hu; Liangwei Wang; Qi Liang; Xiao Cheng (Remote Sensing of Environment, 2023)

Undescribed steroidal alkaloids from the bulbs of Fritillaria sinica - Jia-yuan Li; Shi-fei Wu; Ya-ling An; Chang-liang Yao; Shuai Yao; Yong Huang; Wen-long Wei; Jian-qing Zhang; Qi-rui Bi; Hua Qu; De-an Guo (Phytochemistry, 2023)

Release and mobility characteristics of thallium from polluted farmland in varying fertilization: Role of cation exchange - Ying Huang; Dexin Wang; Junhong Jiang; Jian Gong; Yuxian Liu; Long Li; Linjun Kong; Yang Ruan; Hang Lv; Yongheng Chen; Zibiao Chen; Qi Liang; et al. (Journal of Hazardous Materials, 2023)

Enhanced methane production from the co-digestion of food waste and thermally hydrolyzed sludge filtrate - Kai Feng; Luxin Yang; Liang Chen; Qi Jing; Huan Li; Debin Li; Jiayi Liu; Jiabai Cai; Zhou Deng (Journal of Environmental Management, 2023)

The enrichment of a specialized elemental sulfur–producing bacterium under extremely acidic condition - Tipei Jia; Liang Zhang; Yi Peng; Shihao Sun; Xiyao Li; Qi Zhao; Qiong Zhang; Yongzhen Peng (Chemical Engineering Journal, 2023)

Sulfurized poly(o-phenylenediamine) as a novel high-performance solid-phase conversion sulfur cathode - Qi Wang; Xi Zhang; Junxiao Wang; Jun Chu; Minle Li; Liang Huang; Zijun Hu; Yonggang Wang; Zhiping Song (Chemical Engineering Journal, 2023)

Review of triazole scaffolds for treatment and diagnosis of Alzheimer's disease - Qi Li; Shulei Qi; Jinxin Liang; Yuqing Tian; Siyu He; Qinghong Liao; Shuaishuai Xing; Lingfei Han; Xuehong Chen (Chemico-Biological Interactions, 2023)

Direct evidence of pyrogenic aerosol iron by intrusions of continental polluted air into the Eastern China Seas - Liang Xu; Minkang Zhi; Xiaohuan Liu; Huiwang Gao; Xiaohong Yao; Qi Yuan; Pingqing Fu; Weijun Li (Atmospheric Research, 2023)

Soil Nutrients Directly Drive Soil Microbial Biomass and Carbon Metabolism in the Sanjiangyuan Alpine Grassland - Chen Dongdong; Li Qi; Huo Lili; Xu Qian; Chen Xin; He Fuquan; Zhao Liang (Journal of Soil Science and Plant Nutrition, 2023)

Potential assessment of floating photovoltaic solar power in China and its environmental effect - Qianfeng Ji; Ruifeng Liang; Shiwei Yang; Qi Tang; Yuanming Wang; Kefeng Li; Zhongwei Zhang (Clean Technologies and Environmental Policy, 2023)

Performance of potentiometric oxygen sensors with LSCF electrode in lead–bismuth eutectic loop - Ruixian Liang; Huiping Zhu; Lingfeng Yang; Muran Qi; Xiaobo Li; Yifeng Wang; Zhenhua Sheng; Xu Tu; Gaoxiang Xu; Boqing Li; Hao Wu; Haicai Lyu; et al. (Annals of Nuclear Energy, 2023)

Joint effect of whole blood metals exposure with dyslipidemia in representative US adults in NHANES 2011–2020 - Jing-hong Liang; Ying-qi Pu; Mei-ling Liu; Li-xin Hu; Wen-wen Bao; Yu-shan Zhang; Aerziguli Kakaer; Yu Zhao; Yi-can Chen; Xue-ya Pu; Shao-yi Huang; Nan Jiang; et al. (Environmental Science and Pollution Research, 2023)

Potentially important regolith-hosted Sc deposits related to alkaline igneous complexes of the Permian Emeishan large igneous Province, SW China - Wen Winston Zhao; Mei-Fu Zhou; Zhengchao Wang; Yan Hei Martin Li; Liang Qi; Wei Terry Chen; Yu Shen (Journal of Asian Earth Sciences, 2023)

TiO2 nanoparticles affect spermatogenesis and adhesion junctions via the ROS-mediated mTOR signalling pathway in Eriocheir sinensis testes - Lan-Min Wang; Ke Jia; Zhen-Fang Li; Hong-Yu Qi; Ding-Xi Liu; Ya-Jing Liang; Shuang-Li Hao; Fu-Qing Tan; Wan-Xi Yang (Environmental Pollution, 2023)

NIR-AIEgens nanospheres featuring high-fidelity dynamic lipid droplet targeting, expediting ferroptosis to annihilating tumor in hypoxia - Ke Xue; Yongfei Zhao; Saidong Sun; Yuanhang Li; Jiankang Liang; Zhengjian Qi (Chemical Engineering Journal, 2023)

Carbonation dynamics of hydrated alite revealed by electron microscopy - Qi Zheng; Chengyao Liang; Jinyang Jiang; Shaofan Li (Chemical Engineering Journal, 2023)

A marine lipopeptides-producing Bacillus amyloliquefaciens HY2-1 with a broad-spectrum antifungal and antibacterial activity and its fermentation kinetics study - Lin-ru Huang; Xiao-ning Ling; Shuai-ying Peng; Ming-hui Tan; Lu-qi Yan; Ying-yin Liang; Gang-hui Li; Kun-tai Li (World Journal of Microbiology and Biotechnology, 2023)

Quantifying source effects based on rainwater δ18O from 10-year monitoring records in Southwest China - Yan-Xia Xue; Jian Zhang; Zhen Su; Yao Wu; Qi-sheng Liang; Ming-Qiang Liang; Xiang-Zhuo Liu; Chao-Jun Chen; Hai-Ying Qiu; Jun-Yun Li; Ting-Yong Li (Applied Geochemistry, 2023)

Big-sized trees and higher species diversity improve water holding capacities of forests in northeast China - Yanbo Yang; Lixin Jing; Qi Li; Chentao Liang; Quanxing Dong; Shuting Zhao; Yuwen Chen; Danqi She; Xu Zhang; Lei Wang; Guanchao Cheng; Xiting Zhang; et al. (Science of The Total Environment, 2023)

Numerical simulation of H2-intensive shaft furnace direct reduction process - Zhaoyang Li; Zheng Qi; Lechen Zhang; Meng Guo; Dong Liang; Qiang Dong (Journal of Cleaner Production, 2023)

Paleozoic remelting of carbonatite in Bayan Obo (China): Further insights into the formation of a giant REE deposit - Hai-Dong She; Hong-Rui Fan; M. Santosh; Xiao-Chun Li; Kui-Feng Yang; Qi-Wei Wang; Wei Wei; Yan-Jiang Liu; Shang Liu; Shuang-Liang Liu (Gondwana Research, 2023)

Extraction optimization and identification of four advanced glycation-end products inhibitors from lotus leaves and interaction mechanism analysis - Lu Zhang; Qi-ming Zhou; Liang Xu; Xing Xie; Pei-xin Wang; Zuo-hua Xie; Jin-lin Li; Zong-cai Tu (Food Chemistry, 2023)

Late Pleistocene zinc isotopic indices of paleoproductivity variations in the tropical West Pacific - Wenlong Pei; Jiayue Wang; Xinling Wang; Liang Du; Yipeng Wang; Yujin Fan; Rui Zhang; Tiegang Li; James Russell; Fan Zhang; Xiaoxiao Yu; Zhiyong Liu; et al. (CATENA, 2023)

Exogenous carbon turnover within the soil food web strengthens soil carbon sequestration through microbial necromass accumulation - Xinchang Kou; Elly Morriën; Yijia Tian; Xiaoke Zhang; Caiyan Lu; Hongtu Xie; Wenju Liang; Qi Li; Chao Liang (Global Change Biology, 2023)
Exogenous carbon turnover within soil food web is important in determining the trade‐offs between soil organic carbon (SOC) storage and carbon emission. However, it remains largely unknown how soil food web influences carbon sequestration through mediating the dual roles of microbes as decomposers and contributors, hindering our ability to develop policies for soil carbon management. Here, we conducted a 13 C‐labeled straw experiment to demonstrate how soil food web regulated the residing microbes to influence the soil carbon transformation and stabilization process after 11 years of no‐tillage. Our work demonstrated that soil fauna, as a “temporary storage container,” indirectly influenced the SOC transformation processes and mediated the SOC sequestration through feeding on soil microbes. Soil biota communities acted as both drivers of and contributors to SOC cycling, with 32.0% of exogenous carbon being stabilizing in the form of microbial necromass as “new” carbon. Additionally, the proportion of mineral‐associated organic carbon and particulate organic carbon showed that the “renewal effect” driven by the soil food web promoted the SOC to be more stable. Our study clearly illustrated that soil food web regulated the turnover of exogenous carbon inputs by and mediated soil carbon sequestration through microbial necromass accumulation.

Potential response of dark carbon fixation to global warming in estuarine and coastal waters - Lin Qi; Yanling Zheng; Lijun Hou; Bolin Liu; Jie Zhou; Zhirui An; Li Wu; Feiyang Chen; Zhuke Lin; Guoyu Yin; Hongpo Dong; Xiaofei Li; et al. (Global Change Biology, 2023)
Dark carbon fixation (DCF), through which chemoautotrophs convert inorganic carbon to organic carbon, is recognized as a vital process of global carbon biogeochemical cycle. However, little is known about the response of DCF processes in estuarine and coastal waters to global warming. Using radiocarbon labelling method, the effects of temperature on the activity of chemoautotrophs were investigated in benthic water of the Yangtze estuarine and coastal areas. A dome‐shaped thermal response pattern was observed for DCF rates (i.e., reduced rates at lower or higher temperatures), with the optimum temperature ( T opt ) varying from about 21.9 to 32.0°C. Offshore sites showed lower T opt values and were more vulnerable to global warming compared with nearshore sites. Based on temperature seasonality of the study area, it was estimated that warming would accelerate DCF rate in winter and spring but inhibit DCF activity in summer and fall. However, at an annual scale, warming showed an overall promoting effect on DCF rates. Metagenomic analysis revealed that the dominant chemoautotrophic carbon fixation pathways in the nearshore area were Calvin‐Benson‐Bassham (CBB) cycle, while the offshore sites were co‐dominated by CBB and 3‐hydroxypropionate/4‐hydroxybutyrate cycles, which may explain the differential temperature response of DCF along the estuarine and coastal gradients. Our findings highlight the importance of incorporating DCF thermal response into biogeochemical models to accurately estimate the carbon sink potential of estuarine and coastal ecosystems in the context of global warming.

Associations of long-term joint exposure to various ambient air pollutants with all-cause and cause-specific mortality: evidence from a large population-based cohort study - Zhi-Hao Li; Xiao-Meng Wang; Jia-Xuan Xiang; Ying Nan; Ying-Jun Chen; Pei-Dong Zhang; Dan Liu; Dong Shen; Xi-Ru Zhang; Wen-Fang Zhong; Pei-Liang Chen; Qing-Mei Huang; et al. (Environmental Science and Pollution Research, 2023)

Novel PbO@C composite material directly derived from spent lead-acid batteries by one-step spray pyrolysis process - Wenhao Yu; Mingyang Li; Sha Liang; Qi Xu; Peiyuan Zhang; Huijie Hou; Jingping Hu; Jiakuan Yang (Waste Management, 2023)

Building intercalation structure for high ionic conductivity via aliovalent substitution - Zongdong Sun; Jianing Liang; Kailang Liu; Xin Feng; Yu Wu; Yinghe Zhao; Qi Liang; Jinsong Wu; Huiqiao Li; Tianyou Zhai (Science Bulletin, 2023)

In-situ anaerobic treatment removes the passivation layer of sponge iron to restore the nitrogen and phosphorus removal performance of SBR - Kaiyao Hu; Wenxuan Li; Hao Mu; Shuang Ren; Hongjuan Zhu; Kexin Zeng; Bo Wang; Jinming Liang; Qi Zhang; Lili Yang; Wei Zhao; Juqiang Xiao (Process Safety and Environmental Protection, 2023)

Aconicumines A–D, an advanced class of norditerpenoid alkaloids with an unprecedented N,O-diacetal motif from Aconitum taipeicum Hand.-Mazz., exhibit anti-inflammatory properties in vitro - Dong-Bo Zhang; Yan-Ni Liang; Zheng Wang; Li-Ke Shi; Zhen Zhang; Zhi-Shu Tang; Lu-Qi Huang (Phytochemistry, 2023)

Interface engineering of Mn3O4/Co3O4 S-scheme heterojunctions to enhance the photothermal catalytic degradation of toluene - Jungang Zhao; Caiting Li; Qi Yu; Youcai Zhu; Xuan Liu; Shanhong Li; Caixia Liang; Ying Zhang; Le Huang; Kuang Yang; Ziang Zhang; Yunbo Zhai (Journal of Hazardous Materials, 2023)

Improved catalytic oxidation of propane over phosphate-modified Pd/Al2O3-TiO2 catalyst - Peiyuan Liang; Lina Wang; Qi Wang; Baogang Zhao; Yunhe Li; Yanming Ma; Yi Wei; Tianjun Sun (Journal of Environmental Chemical Engineering, 2023)

Effects of sucrose degradation product furfural on cyanidin-3-O-glucoside: Mechanism of action, stability, and identification of products in sugar solutions - Jiaxin Wang; Zhen Cheng; Ningxuan Gao; Ye Zhang; Mingshuang Wang; Guangyu Ren; Baoge Song; Qi Liang; Yiwen Bao; Hui Tan; Wei Chen; Bin Li; et al. (Food Research International, 2023)

Mechanism of polycyclic aromatic hydrocarbons degradation in the rhizosphere of Phragmites australis: Organic acid co-metabolism, iron-driven, and microbial response - Ni-chen Zhang; Dan A; Yuan-qing Chao; Hai-Yan Li; Charles Li; Qing-qi Lin; Ya-ying Li; Rong-liang Qiu (Environmental Pollution, 2023)

Pulsed counterclockwise rotation of the southwestern Sichuan Basin in response to the India-Asia convergence during 128-42 Ma - Qi Shen; Chun-Sheng Jin; Wen-Tian Liang; Chuan-Zhi Li; Hui-Hui Yang; Ya-Zhou Ran; Xuan He; Guan-Zuo Wu; Kai Jiang; Jian-Gang Li; Peng Han; Si-Hua Yuan (Earth and Planetary Science Letters, 2023)

90 C fast-charge Na-ion batteries for pseudocapacitive faceted TiO2 anodes based on robust interface chemistry - Hongshun Zhao; Jingjing Zhong; Yanli Qi; Kang Liang; Jianbin Li; Xiaobing Huang; Wenkai Chen; Yurong Ren (Chemical Engineering Journal, 2023)

Schisandrin B Improves the Hypothermic Preservation of Celsior Solution in Human Umbilical Cord Mesenchymal Stem Cells - Ying Zhang; Peng Wang; Mei-xian Jin; Ying-qi Zhou; Liang Ye; Xiao-juan Zhu; Hui-fang Li; Ming Zhou; Yang Li; Shao Li; Kang-yan Liang; Yi Wang; et al. (Tissue Engineering and Regenerative Medicine, 2023)

Differential Diagnosis of DCIS and Fibroadenoma Based on Ultrasound Images: a Difference-Based Self-Supervised Approach - Jin Yin; Jia-Jun Qiu; Jing-Yan Liu; Yi-Yue Li; Qi-Cheng Lao; Xiao-Rong Zhong; Mengling Feng; Hao Du; Shao-Liang Peng; Yu-Lan Peng (Interdisciplinary Sciences: Computational Life Sciences, 2023)

The Synergistic Activity and Interaction Mechanism of Linoleic Acid and a Bioactive Pentapeptide (Tyr-Val-Pro-His-Trp) from Walnut Meal in the Treatment of Alzheimer’s Disease - Zi-Chun Wang; Yu-Xi Ling; Ya-Xin Liang; Zi-Qi Li; Jie Dai; Di-Feng Ren (International Journal of Peptide Research and Therapeutics, 2023)

Heterosis and genetic diversity of intraspecific hybrids crosses between two selected lines of the Pacific oyster Crassostrea gigas - Yuanxin Liang; Chengxun Xu; Qi Li (Aquaculture, 2023)

Nitrogen removal by algal-bacterial consortium during mainstream wastewater treatment: Transformation mechanisms and potential N2O mitigation - Qi Li; Yifeng Xu; Chuanzhou Liang; Lai Peng; Yan Zhou (Water Research, 2023)

Aristolocholic acid I promotes renal tubular epithelial fibrosis by upregulating matrix metalloproteinase-9 expression via activating the C3a/C3aR axis of macrophages - Qi Zhang; Jing Ye; Zhaofeng Zhang; Yongkang Hu; Xian Wang; Wenjuan Jiang; Xinlong Guo; Langqun Chen; Siyu Cheng; Jian Li; Liang Zhang (Toxicology Letters, 2023)

Precise insertions of large DNA fragments for cell and gene therapy - Guanglei Li; Qi Zhang; Tingbo Liang; Xingxu Huang (Science Bulletin, 2023)

New insight into the geochemical mechanism and behavior of heavy metals in soil and dust fall of a typical copper smelter - Weijie Liu; Xinli Xing; Miao Li; Yue Yu; Tianpeng Hu; Yao Mao; Lili Liang; Yuan Zhang; Jiaquan Zhang; Shihua Qi (Environmental Research, 2023)

Ultralight, robust, and high Prussian blue-loading polyacrylonitrile aerogel: Preparation, characterization and efficient adsorption/removal of Cs+ - Xiao-Bo Yang; Wei Li; Ze-Zhong Lin; Jing-Qi Liu; Hong-Xin Jiang; Hao Jia; Wei-Liang Jin; Xin-Long Hou; Bing-Xuan Du; Li-Na Zhu; De-Ming Kong (Chemical Engineering Journal, 2023)

Local-scale soil nematode diversity in a subtropical forest depends on the phylogenetic and functional diversity of neighbor trees - Yingbin Li; Xiaofang Du; Xiaolin Su; Xu Han; Wenju Liang; Zhengwen Wang; Helge Bruelheide; T. Martijn Bezemer; Qi Li (Plant and Soil, 2023)

Bioavailability and regional transport of PM2.5 during heavy haze episode in typical coal city site of Fenwei Plain, China - Weijie Liu; Yue Yu; Miao Li; Haikuo Yu; Mingming Shi; Cheng Cheng; Tianpeng Hu; Yao Mao; Jiaquan Zhang; Lili Liang; Shihua Qi; Xinli Xing (Environmental Geochemistry and Health, 2023)

Elevated Interleukin-37 Associated with Dengue Viral Load in Patients with Dengue Fever - Jun-Ai Zhang; Jia-Jun Wang; Wen-Ting Zhang; Li Zhang; Bi-Ying Zheng; Gan-Bin Liu; Jing Liang; Yuan-Bin Lu; Xian-Jin Wu; Shu-Ying Yao; Guo-Ying Chen; Yun-Qi Xie; et al. (Current Microbiology, 2023)
Dengue remains a public health issue worldwide. Similar to chronic infectious diseases, stimulation of cytokine production is not enough to drive immune effector cells for effective virus clearance. One possible mechanism is the virus induces a large number of negative stimulatory cytokines inhibiting immune response. Interleukin 37 (IL-37) plays a crucial regulatory role in infection and immunity, inhibits innate and adaptive immunity as an anti-inflammatory cytokine by inhibiting proinflammatory mediators and pathways. To date, there are few studies reporting correlations between dengue fever (DF) and IL-37. In this study we found that the serum IL-37b and IL-37b-producing monocytes in patients were significantly increased in DF patients. A majority of the IL-37b produced by DF patients was produced by monocytes, not lymphocytes. Increased levels of IL-6, IL-10, and IFN-α were also found in DF patients. However, we failed to detect IL-1β, IL-17A and TNF-α in plasma, because of off-target. In our study, there was no relation between IL-6, IL-10, and IFN-α expressions and IL-37b in serum ( P > 0.05). The IL-37b-producing monocytes were negatively correlated with the level of IFN-α in serum and platelet count, and positively correlated with lymphocytes percentage ( P < 0.05, respectively). Additionally, serum DENV nonstructural protein 1 levels were positively correlated with monocytes percentages ( P < 0.05). Our data represents findings for IL-37b expression and its potential mechanisms in DF patients’ immune response.

Prodigiosin as an antibiofilm agent against multidrug-resistant Staphylococcus aureus - Jing Yan; Qi Yin; Hao Nie; Jinyou Liang; Xiang-Ru Liu; Yingli Li; Hong Xiao (Biofouling, 2023)

Apoptosis-related long non-coding RNA LINC5438 of Bombyx mori promotes the proliferation of BmNPV - Peng Chen; Min Cai; Yu-Jie Feng; Cong Li; Zhan-Qi Dong; Wen-Fu Xiao; Liang Tang; Yan Zhu; Ting Tian; Bo-Yuan Deng; Min-Hui Pan; Cheng Lu (Pesticide Biochemistry and Physiology, 2023)

Reliable spectroscopic identification of minerals associated with serpentinization: Relevance to Mars exploration - Wen-Ping Liu; Wei Yin; Bin-Long Ye; Tian-Lei Zhao; Qi-Zhi Yao; Yi-Liang Li; Sheng-Quan Fu; Gen-Tao Zhou (Icarus, 2023)

Rheological properties of wheat dough mediated by low-sodium salt - Xiaohua Wang; Ying Liang; Qi Wang; Xinlan Wang; Hanyan Li; Jinshui Wang (Food Hydrocolloids, 2023)

A critical review on graphene oxide membrane for industrial wastewater treatment - Ye-Chen An; Xiao-Xu Gao; Wen-Li Jiang; Jing-Long Han; Yuan Ye; Tian-Ming Chen; Rui-Yun Ren; Jia-Hui Zhang; Bin Liang; Zhi-Ling Li; Ai-Jie Wang; Nan-Qi Ren (Environmental Research, 2023)

Chronic exposure to environmentally relevant concentrations of carbamazepine interferes with anxiety response of adult female zebrafish through GABA /5-HT pathway and HPI axis - Cheng-Ting Xie; Mei-Ling Tan; Ying-Wen Li; Qi-Liang Chen; Yan-Jun Shen; Zhi-Hao Liu (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2023)

The infertile individual analysis based on whole-exome sequencing in chinese multi-ethnic groups - Qiongzhen Zhao; Yanqi Li; Qi Liang; Jie Zhao; Kai Kang; Meiling Hou; Xin Zhang; Renqian Du; Lingyin Kong; Bo Liang; Weidong Huang (Genes & Genomics, 2023)

Manifold clustering-based prediction for dynamic multiobjective optimization - Li Yan; Wenlong Qi; A.K. Qin; Shengxiang Yang; Dunwei Gong; Boyang Qu; Jing Liang (Swarm and Evolutionary Computation, 2023)

Seasonal variations of airborne phthalates and novel non-phthalate plasticizers in a test residence in cold regions: Effects of temperature, humidity, total suspended particulate matter, and sources - Chun-Yan Huo; Wen-Long Li; Li-Yan Liu; Yu Sun; Jia-Qi Guo; Liang Wang; Hayley Hung; Yi-Fan Li (Science of The Total Environment, 2023)

Ice tongue calving in Antarctica triggered by the Hunga Tonga volcanic tsunami, January 2022 - Qi Liang; Teng Li; Ian Howat; Wanxin Xiao; Fengming Hui; Zhuoqi Chen; Lei Zheng; Xiao Cheng (Science Bulletin, 2023)

Modulating the electron structure of Co-3d in Co3O4−x/WO2.72 for boosting peroxymonosulfate activation and degradation of sulfamerazine: Roles of high-valence W and rich oxygen vacancies - Xudong Yang; Jun Duan; Juanjuan Qi; Xiuze Li; Jing Gao; Yifei Liang; Si Li; Tao Duan; Wen Liu (Journal of Hazardous Materials, 2023)

Preparation, characterization and application of bacteriocin CAMT6 nanoliposomes using resveratrol as a novel stabilizer - Qibin Li; Linao Lv; Ying Liu; Zhijia Fang; Qi Deng; Weiqi Liang; Yueying Wu; Zhibao Chen (Food Chemistry, 2023)

Contribution of surface plasmonic resonance to enhanced photocatalytic antibacterial performance of graphene-based two-dimensional heterojunction - Zhengao Wang; Guangyu Liu; Wei Chen; Lu Zhang; Zheng Qi; Guanghui Bai; Youzhun Fan; Chengli Liu; Cairong Xiao; Wei Li; Yunbing Chang; Guoyan Liang; et al. (Chemical Engineering Journal, 2023)

Enhanced interfacial charge transfer and photothermal effect via in-situ construction of atom co-sharing Bi plasmonic/Bi4O5Br2 nanosheet heterojunction towards improved full-spectrum photocatalysis - Xiaoyi Dong; Liang Xu; Junhao Ma; Yongjin Li; Zhaoyi Yin; Daomei Chen; Qi Wang; Jin Han; Jianbei Qiu; Zhengwen Yang; Zhiguo Song (Chemical Engineering Journal, 2023)

Dorsal root ganglia P2X4 and P2X7 receptors contribute to diabetes-induced hyperalgesia and the downregulation of electroacupuncture on P2X4 and P2X7 - Qun-qi Hu; Xiao-fen He; Yi-qi Ma; Li-qian Ma; Si-ying Qu; Han-zhi Wang; Yu-rong Kang; Lu-hang Chen; Xiang Li; Bo-yu Liu; Xiao-mei Shao; Jun-fan Fang; et al. (Purinergic Signalling, 2023)

Inhibition of phosphorylated calcium/calmodulin-dependent protein kinase IIα relieves streptozotocin-induced diabetic neuropathic pain through regulation of P2X3 receptor in dorsal root ganglia - Xiao-fen He; Yu-rong Kang; Xue-yu Fei; Lu-hang Chen; Xiang Li; Yi-qi Ma; Qun-qi Hu; Si-ying Qu; Han-zhi Wang; Xiao-mei Shao; Bo-yi Liu; Yi-Liang; et al. (Purinergic Signalling, 2023)
Diabetic neuropathic pain (DNP) is frequent among patients with diabetes. We previously showed that P2X3 upregulation in dorsal root ganglia (DRG) plays a role in streptozotocin (STZ)-induced DNP but the underlying mechanism is unclear. Here, a rat model of DNP was established by a single injection of STZ (65 mg/kg). Fasting blood glucose was significantly elevated from the 1 st to 3 rd week. Paw withdrawal thresholds (PWTs) and paw withdrawal latencies (PWLs) in diabetic rats significantly reduced from the 2 nd to 3 rd week. Western blot analysis revealed that elevated p-CaMKIIα levels in the DRG of DNP rats were accompanied by pain-associated behaviors while CaMKIIα levels were unchanged. Immunofluorescence revealed significant increase in the proportion of p-CaMKIIα immune positive DRG neurons (stained with NeuN) in the 2 nd and 3 rd week and p-CaMKIIα was co-expressed with P2X3 in DNP rats. KN93, a CaMKII antagonist, significantly reduce mechanical hyperalgesia and thermal hyperalgesia and these effects varied dose-dependently, and suppressed p-CaMKIIα and P2X3 upregulation in the DRGs of DNP rats. These results revealed that the p-CaMKIIα upregulation in DRG is involved in DNP, which possibly mediated P2X3 upregulation, indicating CaMKIIα may be an effective pharmacological target for DNP management.

Sex difference on fibroblast growth factors (FGFs) expression in skin and wound of streptozotocin(STZ)-induced type 1 diabetic mice - Nuo-qi Wang; Wei-hua Jia; Lin Yin; Na Li; Mei-dai Liang; Jia-min Shang; Bi-yu Hou; Li Zhang; Gui-fen Qiang; Guan-hua Du; Xiu-ying Yang (Molecular Biology Reports, 2023)

Research on health risk assessment of heavy metals in soil based on multi-factor source apportionment: A case study in Guangdong Province, China - Jiahui Liang; Zhaoyue Liu; Yiqi Tian; Huading Shi; Yang Fei; Jingxian Qi; Li Mo (Science of The Total Environment, 2023)

Life cycle assessment of integrated bioelectrochemical-constructed wetland system: environmental sustainability and economic feasibility evaluation - Ying-Ke Fang; Hong-Cheng Wang; Pan-Hao Fang; Bin Liang; Kun Zheng; Qi Sun; Xi-Qi Li; Ran Zeng; Ai-Jie Wang (Resources, Conservation and Recycling, 2023)

Gonad development and recruitment pattern of the oysters Crassostrea ariakensis and Crassostrea sikamea in a subtropical bay in China - Wei Jiang; Wen-Jing Shi; Nan-Nan Li; Wen-Kao Zhang; Li-Zhi Chen; Qi Liu; Chun-Yu Ye; Rui-Liang Fan; Wei-Min Quan (Regional Studies in Marine Science, 2023)

A Late Jurassic magmatic flare-up triggered by break-off of the Bangong-Nujiang Meso-Tethyan slab: Insights from Jurassic arc magmatism in South Qiangtang, Central Tibet - Neng Gong; Hui Qi; Jun Li; Guo-Li Yuan; Gen-Hou Wang; Xiao Liang; Zhi-Bo Liu (Lithos, 2023)

Roles of the stolon and erect grass species in surface–subsurface flow generation and red soil loss - Zhimin Yang; Chunhui Li; Yaojun Liu; Jian Duan; Lichao Zhang; Zhongwu Li; Xiangyu Zhou; Qi Li; Yichun Ma; Liang Tian (Journal of Hydrology, 2023)

Corrigendum to: “Biochar derived from hydrolysis of sewage sludge influences soil properties and heavy metals distributed in the soil” - Qing Zhu; Yafeng Liang; Qi Zhang; Zhiyuan Zhang; Cuiping Wang; Sheng Zhai; Yanhua Li; Hongwen Sun (Journal of Hazardous Materials, 2023)

Ongoings in the apple watercore: First evidence from proteomic and metabolomic analysis - Mingyi Yang; Qianwei Lin; Zisheng Luo; Zhaojun Ban; Xihong Li; Russel J. Reiter; Shuang Zhang; Lei Wang; Ze Liang; Ming Qi; Li Li (Food Chemistry, 2023)

Effects of polystyrene nanoplastics on the physiological and biochemical characteristics of microalga Scenedesmus quadricauda - Ru-ru Li; Bin-liang Wang; Fang-ru Nan; Jun-ping Lv; Xu-dong Liu; Qi Liu; Jia Feng; Shu-lian Xie (Environmental Pollution, 2023)

A 2D mesoporous hydrazone covalent organic framework for selective detection and ultrafast recovery of Au(III) from electronic waste - Li Zhang; Jia-Qi Fan; Qiong-Qing Zheng; Sai-Jin Xiao; Cheng-Rong Zhang; Shun-Mo Yi; Xin Liu; Wei Jiang; Quan-Gen Tan; Ru-Ping Liang; Jian-Ding Qiu (Chemical Engineering Journal, 2023)

A lipid droplet-specific near-infrared automatic oxygen-supplied AIEgen for photodynamic therapy and metastasis inhibition of hypoxic tumors - Xing Wang; Yuqi Tang; Jiankang Liang; Yongfei Zhao; Li Yang; Zhengjian Qi (Chemical Engineering Journal, 2023)

Sipunculus nudus genome provides insights into evolution of spiralian phyla and development - Yi Qi; Liang Chen; Binhua Wu; Xiaoning Tang; Xiao Zhu; Ru Li; Kefeng Wu; Hui Luo (Frontiers in Marine Science, 2023)
Introduction Sipunculus nudus is the most known species in the genus Sipunculus , distributed in tropical and subtropical coastal waters. Methods PacBio sequencing and Illumina sequencing were combined for whole-genome sequencing of S. nudus . LC-MS/MS analysis was performed for the metabolomics of S. nudus . Results Herein, we report a 1.75 Gb complete genome assembly with a contig N50 size of 450 kb of the S. nudus based on a strategy combining third-generation long-read sequencing and Illumina sequencing. A total of 80391 protein-coding genes are annotated in this genome. Furthermore, gene family evolution analysis shows that S. nudus belonged to Mollusca or was close to Mollusca , but distinct with Annelida . Transcriptome analysis indicates the involvement of complex developmental events in larve. KEGG pathway analysis of differentially expressed genes showed that these DEGs were mainly enriched in the pathway of amino acid metabolism, lipid metabolism and transport and catabolism. LC-MS/MS analysis shows that S. nudus was rich in a variety of nutritional and functional components, such as carnitine, free amino acids, unsaturated fatty acids, inosine and methionine sulfoxide. Combined transcriptome with LC-MS/MS analysis, the results showed that gene expression and metabolic level involved in the inosine, arginine and proline biosynthesis of S. nudus during different growth stages were significantly changed. Discussion Our genome assembly provides an important genome resource and new insight into the relationships of Sipuncula to other spiralian phyla. Meanwhile, transcriptome and LC-MS/MS analysis reveal the systematic gene expression profiles and metabolite components of S. nudus during different growth stages, which provide new insight into the exploration and development of bioactive molecules of S. nudus .

Atmospheric particulate matter impairs cognition by modulating synaptic function via the nose-to-brain route - Chunmei Liang; Yuling Jiang; Tianzhen Zhang; Yao Ji; Yu Zhang; Yuanhong Sun; Shengnan Li; Yi Qi; Yan Wang; Yujie Cai; Tianwen Lai; Lili Cui (Science of The Total Environment, 2023)

Characteristics of biotrickling filter system for hydrogen sulfide removal with seasonal temperature variations: A strategy for low temperature conditions - Tipei Jia; Liang Zhang; Xiyao Li; Qi Zhao; Yongzhen Peng; Jun Sui; Chuanxin Wang (Science of The Total Environment, 2023)

Biochar derived from hydrolysis of sewage sludge influences soil properties and heavy metals distributed in the soil - Qing Zhu; Yafeng Liang; Qi Zhang; Zhiyuan Zhang; Cuiping Wang; Sheng Zhai; Yanhua Li; Hongwen Sun (Journal of Hazardous Materials, 2023)

Detection of microplastics in domestic and fetal pigs’ lung tissue in natural environment: A preliminary study - Han Li; Zuosen Yang; Feng Jiang; Liang Li; Yansheng Li; Minmin Zhang; Zhenzhen Qi; Ruixue Ma; Yuanyuan Zhang; Jing Fang; Xi Chen; Yihang Geng; et al. (Environmental Research, 2023)

A voltage control strategy to improve the cycling stability of organic electrode materials: The case of para-dinitrobenzene - Minle Li; Qi Wang; Junxiao Wang; Liang Huang; Jun Chu; Xiaotang Gan; Zhiping Song (Chemical Engineering Journal, 2023)

Facile fabrication of hierarchically porous melamine foam@COF composite for sample treatment of non-targeted food safety analysis and oil/water separation - Wei Li; Wei-Liang Jin; Hong-Xin Jiang; Rui Wang; Hao Jia; Jing-Qi Liu; An-Na Tang; Li-Na Zhu; De-Ming Kong (Chemical Engineering Journal, 2023)

Effect of isostructural phase transition on cycling stability of ZrCo-based alloys for hydrogen isotopes storage - Jiacheng Qi; Zhaoqing Liang; Xuezhang Xiao; Zhendong Yao; Panpan Zhou; Ruhong Li; Ling Lv; Xinyi Zhang; Huaqin Kou; Xu Huang; Wenhua Luo; Changan Chen; et al. (Chemical Engineering Journal, 2023)

Sequencing the CuOx active species for CO preferential oxidation at low-temperature over CeO2-CuO composite catalysts - Qi Wang; Liping Li; Taotao Huang; Junfang Ding; Yantong Lu; Bin Liang; Haozhe Liu; Guangshe Li (Chemical Engineering Journal, 2023)

Excellent energy storage and mechanical performance in hetero-structure BaTiO3-based relaxors - Liang Chen; Feng Li; Botao Gao; Chang Zhou; Jie Wu; Shiqing Deng; Hui Liu; He Qi; Jun Chen (Chemical Engineering Journal, 2023)

Deciphering exogenous electric field promoting catalysis from the perspectives of electric energy and electron transfer: A review - Ziang Zhang; Caiting Li; Xueyu Du; Youcai Zhu; Le Huang; Kuang Yang; Jungang Zhao; Caixia Liang; Qi Yu; Shanghong Li; Xuan Liu; Yunbo Zhai (Chemical Engineering Journal, 2023)

Overexpressed Cyclin D1 and CDK4 proteins are responsible for the resistance to CDK4/6 inhibitor in breast cancer that can be reversed by PI3K/mTOR inhibitors - Zijie Cai; Jingru Wang; Yudong Li; Qianfeng Shi; Liang Jin; Shunying Li; Mengdi Zhu; Qi Wang; Lok Lam Wong; Wang Yang; Hongna Lai; Chang Gong; et al. (Science China Life Sciences, 2023)

Identification of two migratory colon ILC2 populations differentially expressing IL-17A and IL-5/IL-13 - Hongzhi Liu; Liang Li; Yanyun Hao; Jialu Li; Zhaoyuan Liu; Jingjing Qi; Jingjing Zhang; Ningbo Wu; Dandan Wu; Caixia Gao; Lei Chen; Lei Shen; et al. (Science China Life Sciences, 2023)

Receptor and Ionic Mechanism of Histamine on Mouse Dorsolateral Striatal Neurons - Jian-Ya Peng; Kang-Li Shen; Xiu-Juan Fan; Zeng-Xin Qi; Hui-Wei Huang; Jian-Lan Jiang; Jian-Hua Lu; Xiao-Qin Wang; Xiao-Xia Fang; Wang-Rui Yuan; Qiao-Xuan Deng; Shu Chen; et al. (Molecular Neurobiology, 2023)

Sound speed profiles in high spatiotemporal resolution using multigrid three-dimensional variational method: a coastal experiment off northern Shandong Peninsula - Guangchao Hou; Jingsheng Zhai; Qi Shao; Yanling Zhao; Wei Li; Guijun Han; Kangzhuang Liang (Journal of Oceanology and Limnology, 2023)

Viperin deficiency promotes dendritic cell activation and function via NF-kappaB activation during Mycobacterium tuberculosis infection - Xinying Zhou; Hui Xu; Qianna Li; Qi Wang; Honglin Liu; Yingqi Huang; Yao Liang; Linmiao Lie; Zhenyu Han; Yaoxin Chen; Yulan Huang; Wenle Zhou; et al. (Inflammation Research, 2023)
Objectives and design Dendritic cells (DCs) are one of the key immune cells in bridging innate and adaptive immune response against Mycobacterium tuberculosis (Mtb) infection. Interferons (IFNs) play important roles in regulating DC activation and function. Virus-inhibitory protein, endoplasmic reticulum-associated, interferon-inducible (Viperin) is one of the important IFN-stimulated genes (ISGs), and elicits host defense against infection. Methods We investigated the effects and mechanisms of Viperin on DC activation and function using Viperin deficient bone marrow-derived dendritic cells (BMDCs) during Mtb infection. Results Viperin deficiency enhanced phagocytic activity and increased clearance of Mtb in DCs, produced higher abundance of NO, cytokine including interleukin-12 (IL-12), Tumor necrosis factor-α (TNF- α ), IL-1 β , IL-6 and chemokine including CXCL1, CXCL2 and CXCL10, elevated MHC I, MHC II and co-stimulatory molecules expression, and enhanced CD4 + and CD8 + T cell responses. Mechanistically, Viperin deficiency promoted DC activation and function through NF-κB p65 activation. NF-κB p65 inhibitor prevented cytokine and chemokine production, and co-stimulatory molecules expression promoted by Viperin deficiency. Conclusions These results suggest that Mtb induced Viperin expression could impair the activation of host defense function of DCs and DC-T cell cross talk during Mtb infection. This research may provide a potential target for future HDT in TB therapy.

Determining the position of a fish passage facility entrance based on endemic fish swimming abilities and flow field - Yunong Qin; Qi Wei; Qianfeng Ji; Kefeng Li; Ruifeng Liang; Yuanming Wang (Environmental Science and Pollution Research, 2023)

Spatiotemporal variations and relationships of absorbing aerosol-radiation-gross primary productivity over China - Liang Li; Minxia Liu; Yuhan Qi; Guojuan Zhang; Ruixin Yu (Environmental Monitoring and Assessment, 2023)

Evaluation of agricultural water and soil resource matching characteristics considering increased precipitation-derived “green water”: a case study in the Yellow River Basin, China - Yun Gao; Ping Li; Hongyu Hou; Zhijie Liang; Yan Zhang; Xuebin Qi (Mitigation and Adaptation Strategies for Global Change, 2023)

Advanced analytical model for orbital aerodynamic prediction in LEO - Tengfei Liang; Kaiyu Nie; Qi Li; Jun Zhang (Advances in Space Research, 2023)

Investigation into a homogenous step-like rock slope response under wide-frequency seismic loads using a large-scale shaking table - Jianxian He; Zhifa Zhan; Shengwen Qi; Chunlei Li; Bowen Zheng; Guoxiang Yang; Songfeng Guo; Xiaolin Huang; Yu Zou; Ning Liang (Natural Hazards, 2022)

Mitochondrial DNA mutation affects the pluripotency of embryonic stem cells with metabolism modulation - Juntao Qi; Qi Long; Yang Yuan; Yanshuang Zhou; Jian Zhang; Zifeng Ruan; Liang Yang; Yi Wu; Ge Xiang; Wei Li; Hao Wu; Shiwei Du; et al. (Genome Instability & Disease, 2022)

A stable method for Agrobacterium-mediated transformation of Mentha piperita and Mentha canadensis using internodal explants - Xu Yu; Zequn Chen; Shumin Li; Xiwu Qi; Hailing Fang; Yang Bai; Li Li; Dongmei Liu; Qun Liu; Weilin Li; Chengyuan Liang (In Vitro Cellular & Developmental Biology - Plant, 2022)

Identification of the Hub Genes and the Signaling Pathways in Human iPSC-Cardiomyocytes Infected by SARS-CoV-2 - Li-Min Xie; Yin-Fei Huang; Ye-Ling Liu; Jia-Qi Liang; Wei Deng; Geng-Ling Lin; Huan-Min Luo; Xu-Guang Guo (Biochemical Genetics, 2022)

Removal of Cd from contaminated farmland soil by washing with residues of traditional Chinese herbal medicine extracts - Yi Wang; Yuan Li; Shuai Yang; Qi-hao Wang; Shao-cheng Si; Han-yi Mei; Guo-ming Liu; Xiang-liang Pan; Yong-ming Luo (Environmental Science and Pollution Research, 2022)

Amino Acid Composition, Antioxidant, α-Glucosidase and α-Amylase Inhibitory Activities of the Enzymic Polypeptide from Acer truncatum Seed Meal - Liang Wei; Hui Li; Xinxin Yu; Huiying Yang; Duowen Pu; Minghua Zhu; Qi Lu; Yihong Bao; Yuangang Zu (International Journal of Peptide Research and Therapeutics, 2022)

Two new sesquiterpenoid lactone derivatives from Lindera aggregata - Song-Song Wen; Yan Wang; Jia-Ping Xu; Qi Liu; Lei Zhang; Jing Zheng; Lin Li; Na Zhang; Xin Liu; Yu-Wen Xu; Zhen-Liang Sun (Natural Product Research, 2022)

Proteomic analysis and identification reveal the anti-inflammatory mechanism of clofazimine on lipopolysaccharide-induced acute lung injury in mice - Bo Yang; Zhan Gao; Qi-Shuang Li; Xiang-Ye Zhang; Lan Song; Yi-Ni Wang; Xin-Yue Wang; Lin-Lin Ji; Hong-Liang Xu; Hui Xie; Fu-Kai Feng; Xiao-Ping Li; et al. (Inflammation Research, 2022)

Cost-effective microwave-assisted hydrothermal rapid synthesis of analcime-activated carbon composite from coal gangue used for Pb2+ adsorption - Qi Li; Liang Lv; Xudong Zhao; Yong Wang; Yongzhen Wang (Environmental Science and Pollution Research, 2022)

New taxonomic framework for Arthrodermataceae: a comprehensive analysis based on their phylogenetic reconstruction, divergence time estimation, phylogenetic split network, and phylogeography - Zhi-Yuan Zhang; Yu-Lian Ren; Xin Li; Wan-Hao Chen; Jian-Dong Liang; Yan-Feng Han; Zong-Qi Liang (Antonie van Leeuwenhoek, 2022)

Changes of production and consumption structures in coastal regions lead to mercury emission control in China - Qiumeng Zhong; Hui Li; Sai Liang; Jetashree; Xiaohui Wu; Jianchuan Qi; Shuxiao Wang (Journal of Industrial Ecology, 2022)
China is important in the global mercury (Hg) cycle and is experiencing substantial economic structure transitions. There are pronounced differences in economic development, industrial structure, and consumption patterns across regions in China. However, the impacts of regional economic structure transitions (i.e., production and final demand structures) on Hg emissions in China remain unknown. Here, we reveal the transboundary impacts of changes in regional economic structures on provincial Hg emissions in China. We found that the transitions of production and final demand structures in coastal regions led to Hg emission reductions in China during 2007–2017. In particular, production structure changes in East Coast contributed to 36 metric tons of national Hg emission reduction, where 28 metric tons occurred in other regions (especially Hebei). Its final demand structure transition contributed to 19 metric tons of national emission reduction, where 15 metric tons occurred in other regions (especially Henan). Unfortunately, production structure changes in Northwest and final demand structure changes in Southwest contributed to Hg emission increments in China during 2007–2017. For instance, changes in the final demand structure of Southwest caused 34 metric tons of emission increments, mainly from provinces within the region. Thus, spatially explicit measures for China's Hg emission control can focus on the optimizations of production structure in Northwest and final demand structure in Southwest, as well as the promotion of interregional joint actions between East Coast and North China (especially Hebei and Henan). The findings of this study can inform region‐specific policy decisions and interregional joint efforts to control Hg emissions around the world.

3D food printing: Applications of plant-based materials in extrusion-based food printing - Mingshuang Wang; Dongnan Li; Zhihuan Zang; Xiyun Sun; Hui Tan; Xu Si; Jinlong Tian; Wei Teng; Jiaxin Wang; Qi Liang; Yiwen Bao; Bin Li; et al. (Critical Reviews in Food Science and Nutrition, 2022)

Two-stage hybrid network for segmentation of COVID-19 pneumonia lesions in CT images: a multicenter study - Yaxin Shang; Zechen Wei; Hui Hui; Xiaohu Li; Liang Li; Yongqiang Yu; Ligong Lu; Li Li; Hongjun Li; Qi Yang; Meiyun Wang; Meixiao Zhan; et al. (Medical & Biological Engineering & Computing, 2022)

Sparse principal component analysis based on genome network for correcting cell type heterogeneity in epigenome-wide association studies - Rui Miao; Qi Dang; Jie Cai; Hai-Hui Huang; Sheng-Li Xie; Yong Liang (Medical & Biological Engineering & Computing, 2022)

An application of the A-4DEnVar to coupled parameter optimization - Yantian Gong; Kangzhuang Liang; Xinrong Wu; Qi Shao; Wei Li; Siyuan Liu; Guijun Han; Hanyu Liu (Acta Oceanologica Sinica, 2022)

A new anti-tumor cytotoxic triterpene from Ganoderma lucidum - Liping Cao; Hongliu Jin; Qi Liang; Haiyi Yang; Shuguang Li; Zhicheng Liu; Zhongwen Yuan (Natural Product Research, 2022)

Comparative transcriptome analysis revealed candidate genes involved in fruiting body development and sporulation in Ganoderma lucidum - Dongmei Liu; Xueyan Sun; Wentong Diao; Xiwu Qi; Yang Bai; Xu Yu; Li Li; Hailing Fang; Zequn Chen; Qun Liu; Chengyuan Liang (Archives of Microbiology, 2022)

Comparative metabolome analysis unravels a close association between dormancy release and metabolic alteration induced by low temperature in lily bulbs - Yafan Li; Qi Xin; Yingjie Zhang; Meixia Liang; Gang Zhao; Daqi Jiang; Xiaohua Liu; Hongxia Zhang (Plant Cell Reports, 2022)

Porewater-Derived Blue Carbon Outwelling and Greenhouse Gas Emissions in a Subtropical Multi-Species Saltmarsh - Peiyuan Zhu; Xiaogang Chen; Yan Zhang; Qianyu Zhang; Xuan Wu; Huawen Zhao; Liang Qi; Xuexin Shao; Ling Li (Frontiers in Marine Science, 2022)
Saltmarshes can sequester atmospheric CO 2 in sediments, but limited studies have quantified porewater-derived carbon exports and identified related carbon sources. Here, we estimated porewater exchange, carbon outwelling, and greenhouse gas emissions in a subtropical multi-species saltmarsh. The radon-based porewater exchange rate was estimated to be 5.60 ± 2.78 cm d -1 . As the most dominant (~90%) carbon species, dissolved inorganic carbon (DIC) fluxes through porewater exchange and outwelling were 447 ± 227 and 1200 ± 61 mmol m -2 d -1 , respectively, which were 1.2 and 3.2 times that of carbon burial. As most DIC can remain in the ocean for a long time, porewater-derived DIC outwelling represents another important carbon sink, in addition to carbon burial. CO 2 and CH 4 emissions from creek water were 54.6 ± 0.5 and 0.19 ± 0.01 mmol m -2 d -1 , respectively, which could offset 16% of carbon burial. The δ 13 C and C/N ratios suggest that saltmarsh organic carbon mainly originates from the C3 plant Scirpus mariqueter rather than the C4 plant Spartina alterniflora . Overall, we suggest that porewater-derived DIC outwelling is an important long-term carbon sink in multi-species saltmarshes, providing a scientific basis for the protection and restoration of saltmarshes in the context of global climate change.

A new NLR gene for resistance to Tomato spotted wilt virus in tomato (Solanum lycopersicum) - Shiming Qi; Yuanbo Shen; Xinyu Wang; Shijie Zhang; Yushun Li; Md. Monirul Islam; Jin Wang; Pan Zhao; Xiangqiang Zhan; Fei Zhang; Yan Liang (Theoretical and Applied Genetics, 2022)

Effects of dihydroartemisinin, a metabolite of artemisinin, on colon cancer chemoprevention and adaptive immune regulation - Chong-Zhi Wang; Chunping Wan; Yun Luo; Chun-Feng Zhang; Qi-Hui Zhang; Lina Chen; Zhi Liu; Daniel H. Wang; Mallory Lager; Cang-Hai Li; Ting-Liang Jiang; Lifei Hou; et al. (Molecular Biology Reports, 2022)

Cavin-1 promotes M2 macrophages/microglia polarization via SOCS3 - Wei Huang; Yiyi Hong; Wenjing He; Li Jiang; Wen Deng; Biyan Peng; Fen Tang; Chaolan Shen; Qianqian Lan; Hui Huang; Haibin Zhong; Jian Lv; et al. (Inflammation Research, 2022)

Genome-wide assessment of genetic diversity and population structure of Platostoma palustre in southern China and implications for conservation and breeding strategies - Qi Li; Wei Xia; Qian Li; Xuezhi Liang; Jianguang Xie; Shilei Geng (Genetic Resources and Crop Evolution, 2022)

A New Scheme for Capturing Global Conditional Nonlinear Optimal Perturbation - Siyuan Liu; Qi Shao; Wei Li; Guijun Han; Kangzhuang Liang; Yantian Gong; Ru Wang; Hanyu Liu; Song Hu (Journal of Marine Science and Engineering, 2022)
Conditional nonlinear optimal perturbation (CNOP) represents the initial perturbation that satisfies a certain physical constraint condition, and leads to a maximum prediction error at the moment of prediction. The CNOP method is a useful tool in studying atmosphere and ocean predictability problems. Generally, the optimization algorithm based on the gradient of the cost function to compute CNOP requires an initial guess. The traditional scheme randomly chooses the initial guess of CNOP within the constraint range and therefore this scheme is called RIG-CNOP. However, the RIG-CNOP scheme reduces the probability of capturing the global CNOP in many cases, such as the prediction model is strongly nonlinear or long-term prediction is performed, or multiple extreme values existed in the cost function. Considering the limitations of the RIG-CNOP scheme, we propose a new initial guess selection scheme. In this scheme, we first pre-analyze a series of random initial guesses, and then, an optimal initial guess is selected. The above process replaces the initial guess selection scheme in the traditional scheme, which is called PAIG-CNOP. Numerical experiments are conducted utilizing the Lorenz-63 model. Also, to compare the performance of the PAIG-CNOP method with the RIG-CNOP method in capturing global CNOP, the CNOP and the maximum cost function value (MCFV) obtained by the filtering method (FM) are used as benchmarks (this value is called FMMCFV in brief). The experimental results show that even the prediction model is strongly nonlinear or the prediction time is long, or the cost function has multiple extreme values, the PAIG-CNOP method can capture the global CNOP with a high probability. The results show that the PAIG-CNOP method has a higher probability of capturing the global CNOP than the RIG-CNOP method. In addition, we use an ensemble-based technique in the computation of gradients, thus avoiding the use of adjoint techniques in the maximization process. Due to the attractive features of the new method, the PAIG-CNOP method is an efficient and useful method for solving CNOP, it can be more easily applied to obtain the global CNOP of operational prediction models.

Short-form OPA1 is a molecular chaperone in mitochondrial intermembrane space - Deyang Yao; Yukun Li; Sheng Zeng; Zhifan Li; Zahir Shah; Bigui Song; Jinglei Liu; Yi Wu; Liang Yang; Qi Long; Wenqian Wang; Zhijuan Hu; et al. (Science China Life Sciences, 2022)

Two new threonine-containing metabolites from fungus Curvularia inaequalis strain HS-FG-257 - Shao-Yong Zhang; Jian-Song Li; Hui Zhang; Huan Qi; Rui-Jun Wang; Chou-Fei Wu; Li-Qin Zhang; An-Liang Chen; Ji-Dong Wang; Zhi-Kui Hao (Natural Product Research, 2022)

Effect of feed restriction on the intestinal microbial community structure of growing ducks - Jun-peng Li; Qi-fan Wu; Sheng-chao Ma; Jian-mei Wang; Bin Wei; Yang Xi; Chun-chun Han; Liang Li; Hua He; He-he Liu (Archives of Microbiology, 2022)

Sabulicella rubraurantiaca gen. nov., sp. nov., a new member of the family Acetobacteraceae, isolated from desert soil - Zhi-Liang Lin; Shuai Li; Qi-Chuang Wei; Wen-Hui Lian; Chun-Yan Lu; Lu Xu; Li-Nan Huang; Lei Dong; Wen-Jun Li (Archives of Microbiology, 2022)

Goodyschle A, a new butenolide with significant BchE inhibitory activity from Goodyera schlechtendaliana - Le-Yao Dai; Qi-Meng Yin; Jia-Kai Qiu; Zhen-Yang Zhang; Gang Li; Meng-Ni Huang; Liang Liu (Natural Product Research, 2021)

External evaluation of published population pharmacokinetic models of polymyxin B - Ya-qian Li; Kai-feng Chen; Jun-jie Ding; Hong-yi Tan; Nan Yang; Ya-qi Lin; Cui-fang Wu; Yue-liang Xie; Guo-ping Yang; Jing-Jing Liu; Qi Pei (European Journal of Clinical Pharmacology, 2021)

Detoxification difference of cadmium between the application of selenate and selenite in native cadmium-contaminated soil - Mingxing Qi; Yang Liu; Yanan Li; Min Wang; Nana Liu; Pornpimol Kleawsampanjai; Fei Zhou; Hui Zhai; Mengke Wang; Quang Toan Dinh; Rui Ren; Dongli Liang (Environmental Science and Pollution Research, 2021)

Mineralogical characteristics and sedimentary envrionment significance of water-insoluble minerals in potash deposits of Vientiane Basin of Laos - Tang Qi-liang; Zhang Xi-ying; Miao Wei-liang; Ma Hai-zhou; Li Yong-shou; Li Wen-xia; Yuan Xiao-long (Carbonates and Evaporites, 2021)

Exposure to 2,4-dichlorophenol, 2,4,6-trichlorophenol, pentachlorophenol and risk of thyroid cancer: a case-control study in China - Wan-Jun Yang; Hua-Bing Wu; Chi Zhang; Qi Zhong; Ming-Jun Hu; Jia-Liu He; Guo-Ao Li; Zhen-Yu Zhu; Jin-Liang Zhu; Huan-Huan Zhao; Han-Shuang Zhang; Fen Huang (Environmental Science and Pollution Research, 2021)

Changes in Brain Functional Network Connectivity in Adult Moyamoya Diseases - Gaoxing Zheng; Yu Lei; Yuzhu Li; Wei Zhang; Jiabin Su; Xiaoying Qi; Liang Chen; Xin Zhang; Yuxiang Gu; Yuguo Yu; Ying Mao (Cognitive Neurodynamics, 2021)

Seismic response characteristics and deformation evolution of the bedding rock slope using a large-scale shaking table - Jianxian He; Shengwen Qi; Zhifa Zhan; Songfeng Guo; Chunlei Li; Bowen Zheng; Xiaolin Huang; Yu Zou; Guoxiang Yang; Ning Liang (Landslides, 2021)

Strong in vitro and in vivo cytotoxic effects of two platinum(II) complexes with cryptolepine derivatives - Li-Qin Qin; Zu-Zhuang Wei; Lin Yang; Qi-Pin Qin; Jia-Jing Zeng; Ming-Xiong Tan; Hong Liang (Medicinal Chemistry Research, 2021)

Seasonal variation of nitrogen biogeochemical processes constrained by nitrate dual isotopes in cascade reservoirs, Southwestern China - Sai-Nan Chen; Fu-Jun Yue; Xiao-Long Liu; Jun Zhong; Yuan-Bi Yi; Wan-Fa Wang; Yulin Qi; Hua-Yun Xiao; Si-Liang Li (Environmental Science and Pollution Research, 2021)

Mowing did not mitigate the negative effects of nitrogen deposition on soil nematode community in a temperate steppe - Yingbin Li; Siwei Liang; Xiaofang Du; Xinchang Kou; Xiaotao Lv; Qi Li (Soil Ecology Letters, 2021)

Phylogenetic diversity and bioactivity of culturable deep-sea-derived fungi from Okinawa Trough - Xiaoyong Zhang; Yiyang Li; Zonghe Yu; Xiao Liang; Shuhua Qi (Journal of Oceanology and Limnology, 2021)

New biphenanthrenes with butyrylcholinesterase inhibitory activitiy from Cremastra appendiculata - Liang Liu; Qi-Meng Yin; Qian Gao; Jun Li; Yong Jiang; Peng-Fei Tu (Natural Product Research, 2021)

A single nucleotide polymorphism variant located in the cis ‐regulatory region of the ABCG2 gene is associated with mallard egg colour - Hehe Liu; Jian Hu; Zhanbao Guo; Wenlei Fan; Yaxi Xu; Suyun Liang; Dapeng Liu; Yunsheng Zhang; Ming Xie; Jing Tang; Wei Huang; Qi Zhang; et al. (Molecular Ecology, 2021)
Avian egg coloration is shaped by natural selection, but its genetic basis remains unclear. Here, we used genome‐wide association analysis and identity by descent to finely map green egg colour to a 179‐kb region of Chr4 based on the resequencing of 352 ducks ( Anas platyrhynchos ) from a segregating population resulting from the mating of Pekin ducks (white‐shelled eggs) and mallards (green‐shelled eggs). We further narrowed the candidate region to a 30‐kb interval by comparing genome divergence in seven indigenous duck populations. Among the genes located in the finely mapped region, only one transcript of the ABCG2 gene (XM_013093252.2) exhibited higher uterine expression in green‐shelled individuals than in white‐shelled individuals, as supported by transcriptome data from four populations. ABCG2 has been reported to encode a protein that functions as a membrane transporter for biliverdin. Sanger sequencing of the whole 30‐kb candidate region (Chr4: 47.41–47.44 Mb) and a plasmid reporter assay helped to identify a single nucleotide polymorphism (Chr4: 47,418,074 G>A) located in a conserved predicted promoter region whose variation may alter ABCG2 transcription activity. We provide a useful molecular marker for duck breeding and contribute data to the research on ecological evolution based on egg colour patterns among birds.

Slight Increases in Salinity Improve Muscle Quality of Grass Carp (Ctenopharyngodon idellus) - Xi Zhang; Zhiyuan Shen; Tianpeng Qi; Rujuan Xi; Xiao Liang; Li Li; Rong Tang; Dapeng Li (Fishes, 2021)
Fish muscle quality is an important parameter in the aquaculture industry. In this study, we analyzed and compared the muscle quality of grass carp (Ctenopharyngodon idellus) cultured at salinities of 0‰, 3‰, and 6‰ (GC0, GC3, GC6). There was no significant difference in crude protein and crude fat content of muscle between GC0 and GC3. Crude fat was significantly lower in GC6 compared to the other groups. GC3 and GC6 had higher hydroxyproline content, which suggested that these groups had higher collagen content. GC3 and GC6 had higher contents of free amino acids and umami amino acids than GC0, but there was no significant difference in sweet or sour amino-acid content among groups. GC3 and GC6 had better texture properties, including hardness, gumminess, chewiness, resilience, and springiness, than GC0. GC3 had the highest water-holding capacity among the groups. As the salinity increased, the diameter of muscle fibers decreased and the sarcolemma showed a thickening trend. These results suggest that a slight increase in salinity (i.e., 3‰) can effectively improve the muscle quality of grass carp.

Connexin 36 Mediates Orofacial Pain Hypersensitivity Through GluK2 and TRPA1 - Qian Li; Tian-Le Ma; You-Qi Qiu; Wen-Qiang Cui; Teng Chen; Wen-Wen Zhang; Jing Wang; Qi-Liang Mao-Ying; Wen-Li Mi; Yan-Qing Wang; Yu-Xia Chu (Neuroscience Bulletin, 2020)

Variations of Forage Yield and Nutrients with Altitude Gradients and Their Influencing Factors in Alpine Meadow of Sanjiangyuan, China - Chen Dongdong; Li Qi; Liu Zhe; He Fuquan; Chen Xin; Xu Shixiao; Zhao Xinquan; Zhao Liang (Journal of Soil Science and Plant Nutrition, 2020)

Characterization and genome analysis of Klebsiella phage P509, with lytic activity against clinical carbapenem-resistant Klebsiella pneumoniae of the KL64 capsular type - Min Li; Yuyi Xiao; Pei Li; Zitong Wang; Weiling Qi; Zitai Qi; Liang Chen; Hong Du; Wei Zhang (Archives of Virology, 2020)

2020 taxonomic update for phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Daniela Alioto; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Simon J. Anthony; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Tomáš Bartonička; et al. (Archives of Virology, 2020)

Sphingosylphosphorylcholine alleviates hypoxia-caused apoptosis in cardiac myofibroblasts via CaM/p38/STAT3 pathway - Ying Li; Qi Qi; Wan-cheng Yang; Tian-liang Zhang; Chen-chen Lu; Yu-juan Yao; Wei-hua Kong; Jing Zhao (Apoptosis, 2020)

Analysis of genetic architecture and favorable allele usage of agronomic traits in a large collection of Chinese rice accessions - Xiuxiu Li; Zhuo Chen; Guomin Zhang; Hongwei Lu; Peng Qin; Ming Qi; Ying Yu; Bingke Jiao; Xianfeng Zhao; Qiang Gao; Hao Wang; Yunyu Wu; et al. (Science China Life Sciences, 2020)

Fasudil attenuates glial cell-mediated neuroinflammation via ERK1/2 and AKT signaling pathways after optic nerve crush - Wei Huang; Qianqian Lan; Li Jiang; Wenya Yan; Fen Tang; Chaolan Shen; Hui Huang; Haibin Zhong; Jian Lv; Siming Zeng; Min Li; Zhongxiang Mo; et al. (Molecular Biology Reports, 2020)

Comparing GWAS and Brain Structure-Specific Gene Expression Profiles Identifies Psychiatric Disorder-Related Brain Structures at Different Developmental Stages - Xin Qi; Cuiyan Wu; Yanan Du; Shiqiang Cheng; Yan Wen; Mei Ma; Chujun Liang; Li Liu; Bolun Cheng; Lu Zhang; Ping Li; Feng Zhang (Neuroscience Bulletin, 2020)

Heroin Abuse and/or HIV Infection Dysregulate Plasma Exosomal miRNAs - Xu Wang; Li Sun; Yu Zhou; Qi-Jian Su; Jie-Liang Li; Li Ye; Man-Qing Liu; Wang Zhou; Wen-Zhe Ho (Journal of Neuroimmune Pharmacology, 2020)

Pseudomonas Saliphila sp. nov., a Bacterium Isolated from Oil-Well Production Water in Qinghai Oilfield of China - Xiao-Juan Zhang; Hong-Can Liu; Yu-Guang Zhou; Xiao-Lei Wu; Yong Nie; Qi-Rui Li; Mei-Zhu Wang; Liang Zhao; Man Cai; Ying-Qian Kang (Current Microbiology, 2020)

Characterization of viromes within mosquito species in China - Jiang Du; Fan Li; Yelin Han; Shihong Fu; Bo Liu; Nan Shao; Haoxiang Su; Weijia Zhang; Dandan Zheng; Wenwen Lei; Jie Dong; Lilian Sun; et al. (Science China Life Sciences, 2020)

Correction to: The Effects of 50 nm Unmodified Nano-ZnO on Lipid Metabolism and Semen Quality in Male Mice - Tao Kong; Shu-Hui Zhang; Cai Zhang; Ji-Liang Zhang; Fan Yang; Guo-Yong Wang; Zi-Jun Yang; Dong-Ying Bai; Yun-Yun Shi; Tian-Qi Liu; Hai-Long Li (Biological Trace Element Research, 2020)

The Effects of 50 nm Unmodified Nano-ZnO on Lipid Metabolism and Semen Quality in Male Mice - Tao Kong; Shu-Hui Zhang; Cai Zhang; Ji-Liang Zhang; Fan Yang; Guo-Yong Wang; Zi-Jun Yang; Dong-Ying Bai; Yun-Yun Shi; Tian-Qi Liu; Hai-Long Li (Biological Trace Element Research, 2020)

Evaluating the Genetic Correlations Between Left-Handedness and Mental Disorder Using Linkage Disequilibrium Score Regression and Transcriptome-Wide Association Study - Bolun Cheng; Chujun Liang; Ping Li; Li Liu; Shiqiang Cheng; Mei Ma; Lu Zhang; Xin Qi; Yan Wen; Feng Zhang (Biochemical Genetics, 2020)

Study on visual control system of acoustic in situ measurement technology for survey of seafloor sediment - Bin Lv; Guo-liang Qi; Guan-bao Li; Guang-ming Kan; Jing-qiang Wang; Jie Liu (Marine Georesources & Geotechnology, 2020)

De novo transcriptomic analysis of light-induced flavonoid pathway, transcription factors in the flower buds of Lonicera japonica - Hailing Fang; Xiwu Qi; Yiming Li; Xu Yu; Dongbei Xu; Chengyuan Liang; Weilin Li; Xin Liu (Trees, 2020)

A novel Ursane-type triterpene saponin from Ajuga multiflora - Yunzhi Li; Mingli Liang; Lu Ma; Qi Chen; Xian Huang (Natural Product Research, 2020)

A Water-Soluble Fluorescent Probe for the Selective Sensing of Ag+ and its Application in Imaging of Living Cells and Nematodes - Xueqin Jiang; Youzhe Yang; Hao Li; Xiaoyi Qi; Xiaogang Zhou; Mingming Deng; Muhan Lü; Jianming Wu; Sicheng Liang (Journal of Fluorescence, 2020)

LncRNA SNHG3 promotes cell proliferation and invasion through the miR-384/hepatoma-derived growth factor axis in breast cancer - Qiuhong Ma; Xiangqin Qi; Xiaona Lin; Liang Li; Libo Chen; Wei Hu (Human Cell, 2020)

Predicting the higher heating value of syngas pyrolyzed from sewage sludge using an artificial neural network - Hongsen Li; Qi Xu; Keke Xiao; Jiakuan Yang; Sha Liang; Jingping Hu; Huijie Hou; Bingchuan Liu (Environmental Science and Pollution Research, 2020)

Nonlinear responses of soil nematode community composition to increasing aridity - Dan Xiong; CunZheng Wei; E. R. Jasper Wubs; G. F. Veen; Wenju Liang; Xiaobo Wang; Qi Li; Wim H. Van der Putten; Xingguo Han (Global Ecology and Biogeography, 2020)
Aim Increasing aridity under global change is predicted to have a profound impact on the structure and functioning of terrestrial ecosystems, yet we have a poor understanding of how belowground communities respond. In order to understand the longer term responses of different trophic levels in the soil food web to increasing aridity, we investigated the abundance, richness and community similarity of the soil nematode community along a 3,200 km aridity gradient. Location A transect across semi‐arid and arid grasslands in Northern China, where the aridity ranges from .43 to .97. Time period July and August 2012. Major taxa studied Soil‐borne Nematoda. Methods We used generalized additive (mixed) models to analyse the abundance, richness and community similarity patterns of soil nematodes. We used structural equation modelling (SEM) to disentangle the direct and indirect environmental drivers (aridity, soil and plant variables) of the nematode community. Results The abundance, richness and similarity of nematode communities declined nonlinearly with increasing aridity. The most pronounced decline in nematode richness and community similarity occurred in arid conditions (aridity > .80). However, the shape of the response to aridity differed among nematode feeding groups. In arid conditions, the abundance and richness of bacterial feeders were less sensitive to changes in aridity than for fungal feeders. The SEM analysis revealed that nematode community responses to aridity were not mediated via changes in plant and soil variables, but instead were affected directly by aridity. Main conclusions Our results showed that in mesic grasslands, increasing aridity primarily caused a decline in nematode abundance, whereas increasing aridity in xeric grasslands led to a loss of nematode diversity. The nonlinear responses of nematodes to aridity could also result in nonlinear shifts in ecosystem functioning, because soil nematodes operate at various trophic levels in the soil food web, thereby influencing the performance of plants, soil biodiversity and biogeochemical cycling.

Transferrin Receptor Targeted Cellular Delivery of Doxorubicin Via a Reduction-Responsive Peptide-Drug Conjugate - Songtao Li; Hongling Zhao; Xiaoxia Mao; Yanfang Fan; Xiujun Liang; Ruxing Wang; Lijun Xiao; Jianping Wang; Qi Liu; Guiqin Zhao (Pharmaceutical Research, 2019)

Carbon Monoxide Attenuates High Salt-Induced Hypertension While Reducing Pro-inflammatory Cytokines and Oxidative Stress in the Paraventricular Nucleus - Dong-Dong Zhang; Yan-Feng Liang; Jie Qi; Kai B. Kang; Xiao-Jing Yu; Hong-Li Gao; Kai-Li Liu; Yan-Mei Chen; Xiao-Lian Shi; Guo-Rui Xin; Li-Yan Fu; Yu-Ming Kang; et al. (Cardiovascular Toxicology, 2019)

Targeted disruption of tyrosinase causes melanin reduction in Carassius auratus cuvieri and its hybrid progeny - Qingfeng Liu; Yanhua Qi; Qiuli Liang; Jia Song; Junmei Liu; Wuhui Li; Yuqin Shu; Min Tao; Chun Zhang; Qinbo Qin; Jing Wang; Shaojun Liu (Science China Life Sciences, 2019)

The complete chloroplast genome of Taiwania cryptomerioides (Cupressales: Cupressaceae), an endangered relict conifer species endemic to East Asia - Ling-Li Wang; Yong-Liang Shi; Qi-Lin Zhang; Yan-Ru Guo; Hong-Mei Teng (Conservation Genetics Resources, 2019)

A Spatial Ecology Study of Keshan Disease and Hair Selenium - Xiao Zhang; Tong Wang; Shie Li; Chao Ye; Jie Hou; Qi Li; Hong Liang; Huihui Zhou; Zhongying Guo; Xiaomin Han; Zhe Wang; Huan Wu; et al. (Biological Trace Element Research, 2019)

Phyllobacterium phragmitis sp. nov., an endophytic bacterium isolated from Phragmites australis rhizome in Kumtag Desert - Li-xiong Liang; Qi-wu Sun; Nan Hui; Xiao-xia Zhang; Lu-bin Li; Lei Liu (Antonie van Leeuwenhoek, 2019)

Approach to the Geopolitical Influences of Great Powers in Southeast Asia: Case Studies of China and the US - Qi Qin; Shengkui Cheng; Fei Li; Shuwen Zhang; Liang Wu; Dan Zhang (Chinese Geographical Science, 2019)

Complete genome sequence of a novel mitovirus from the wheat stripe rust fungus Puccinia striiformis - Li Zheng; Jing Zhao; Xiaofei Liang; Hua Zhuang; Tuo Qi; Zhensheng Kang (Archives of Virology, 2019)

Butenolide, a Marine-Derived Broad-Spectrum Antibiofilm Agent Against Both Gram-Positive and Gram-Negative Pathogenic Bacteria - Qi Yin; Jinyou Liang; Weipeng Zhang; Lv Zhang; Zhang-Li Hu; Yu Zhang; Ying Xu (Marine Biotechnology, 2019)

Angiogenesis in pancreatic cancer: current research status and clinical implications - Shuo Li; Hua-Xiang Xu; Chun-Tao Wu; Wen-Quan Wang; Wei Jin; He-Li Gao; Hao Li; Shi-Rong Zhang; Jin-Zhi Xu; Zi-Hao Qi; Quan-Xing Ni; Xian-Jun Yu; et al. (Angiogenesis, 2019)

Heterologous overexpression of Lithospermum erythrorhizon LeERF-1 gene increases drought and pathogen resistance in Arabidopsis - Rong-Jun Fang; Ai-Qian Li; Ru-Nan Tian; Wen-Ju Zhang; Ai-Lan Zou; Feng-Yao Wu; Yong-Hui Liao; Xiao-Ming Wang; Yan-Jun Pang; Rong-Wu Yang; Gui-Hua Lu; Jin-Liang Qi; et al. (Acta Physiologiae Plantarum, 2019)

Threshold sediment flux for the formation of river deltas in Hainan Island, southern China - Gaocong Li; Liang Zhou; Yali Qi; Shu Gao (Journal of Geographical Sciences, 2019)

Quantifying the ecological stability of artificial aquatic ecosystems: a case study of an artificial lake in Chengdu, China - Fang-Fang Chen; Gong-Ping Su; Hai-Yan Mou; Xuan Liang; Yi Chen; Tian-Qi Ao; Wen-Qing Chen; Yun-Zhen Li (Aquatic Sciences, 2019)

Contourlet-based hippocampal magnetic resonance imaging texture features for multivariant classification and prediction of Alzheimer’s disease - Ni Gao; Li-Xin Tao; Jian Huang; Feng Zhang; Xia Li; Finbarr O’Sullivan; Si-Peng Chen; Si-Jia Tian; Gehendra Mahara; Yan-Xia Luo; Qi Gao; Xiang-Tong Liu; et al. (Metabolic Brain Disease, 2018)

The jasmonate-responsive transcription factor CbWRKY24 regulates terpenoid biosynthetic genes to promote saponin biosynthesis in Conyza blinii H. Lév. - Wen-Jun Sun; Jun-Yi Zhan; Tian-Run Zheng; Rong Sun; Tao Wang; Zi-Zhong Tang; Tong-Liang Bu; Cheng-Lei Li; Qi Wu; Hui Chen (Journal of Genetics, 2018)

Soil micro-food web interactions and rhizosphere priming effect - Xinchang Kou; Tongqing Su; Ningning Ma; Qi Li; Peng Wang; Zhengfang Wu; Wenju Liang; Weixin Cheng (Plant and Soil, 2018)

Frond transformation system mediated by Agrobacterium tumefaciens for Lemna minor - Gui-Li Yang; Yang Fang; Ya-Liang Xu; Li Tan; Qi Li; Yang Liu; Fan Lai; Yan-Ling Jin; An-Ping Du; Kai-Ze He; Xin-Rong Ma; Hai Zhao (Plant Molecular Biology, 2018)

An Automatic Method for Generating an Unbiased Intensity Normalizing Factor in Positron Emission Tomography Image Analysis After Stroke - Binbin Nie; Shengxiang Liang; Xiaofeng Jiang; Shaofeng Duan; Qi Huang; Tianhao Zhang; Panlong Li; Hua Liu; Baoci Shan (Neuroscience Bulletin, 2018)

The chimeric genes in the hybrid lineage of Carassius auratus cuvieri (♀)×Carassius auratus red var. (♂) - Qingfeng Liu; Yanhua Qi; Qiuli Liang; Xiujuan Xu; Fangzhou Hu; Jing Wang; Jun Xiao; Shi Wang; Wuhui Li; Min Tao; Qinbo Qin; Rurong Zhao; et al. (Science China Life Sciences, 2018)

Thimet oligopeptidase and prolyl endopeptidase of spotted scat Scatophagus argus: characterization, tissue distribution, expression at different ovarian stages and down-regulation by estradiol - Si-ping Deng; Dong-neng Jiang; Jian-ye Liu; Zhi-qi Liang; Hua-pu Chen; Tian-li Wu; Chun-hua Zhu; Guang-li Li (Fisheries Science, 2018)

Amplitude calculation of the end-Permian sea level drop in Northeastern Sichuan Basin, China - Rui Zhao; Jiahui Zhao; Yang Li; Yu Liang; Yasheng Wu; Enguang Qi (Carbonates and Evaporites, 2018)

Long-term fertilization management affects the C utilization from crop residues by the soil micro-food web - Shuyan Cui; Siwei Liang; Xiaoke Zhang; Yingbin Li; Wenju Liang; Liangjie Sun; Jingkuan Wang; T. Martijn Bezemer; Qi Li (Plant and Soil, 2018)

Erratum to: A cross-sectional study of irritable bowel syndrome in nurses in China: prevalence and associated psychological and lifestyle factors - Liang Liu; Qi-fan Xiao; Yan-li Zhang; Shu-kun Yao (Journal of Zhejiang University-SCIENCE B, 2018)

Removal efficiency and enzymatic mechanism of dibutyl phthalate (DBP) by constructed wetlands - Xin Qi; Tiancui Li; Feihua Wang; Yanran Dai; Wei Liang (Environmental Science and Pollution Research, 2018)

Nucleocapsid protein from porcine epidemic diarrhea virus isolates can antagonize interferon-λ production by blocking the nuclear factor-κB nuclear translocation - Ying Shan; Zi-qi Liu; Guo-wei Li; Cong Chen; Hao Luo; Ya-jie Liu; Xun-hui Zhuo; Xing-fen Shi; Wei-huan Fang; Xiao-liang Li (Journal of Zhejiang University-SCIENCE B, 2018)

Effects of Cr2O3 nanoparticles on the chlorophyll fluorescence and chloroplast ultrastructure of soybean (Glycine max) - Jinxing Li; Yuchao Song; Keren Wu; Qi Tao; Yongchao Liang; Tingqiang Li (Environmental Science and Pollution Research, 2018)

Diethylstilbestrol arrested spermatogenesis and somatic growth in the juveniles of yellow catfish (Pelteobagrus fulvidraco), a fish with sexual dimorphic growth - Zhi–Hao Liu; Qi–Liang Chen; Qiang Chen; Fang Li; Ying–Wen Li (Fish Physiology and Biochemistry, 2018)

Peripheral Leptin Signaling Mediates Formalin-Induced Nociception - Zhi-Jing Hu; Wei Han; Chang-Qing Cao; Qi-Liang Mao-Ying; Wen-Li Mi; Yan-Qing Wang (Neuroscience Bulletin, 2018)

Successful Treatment by Surgery of a Primary Cutaneous Mucormycosis Caused by Mucor irregularis - Guan-zhao Liang; Wen-qi Xu; Xiao-li Zheng; Huan Mei; Gui-xia Lv; Yong-nian Shen; Dong-mei Li; Wei-da Liu (Mycopathologia, 2018)

Use of freeze-dried bone allografts in osteoporotic patients undergoing median sternotomy - Mei Liang; Jianzhou Liu; Qi Miao; Guotao Ma; Xingrong Liu; Xiaofeng Li; Chaoji Zhang (Cell and Tissue Banking, 2018)

Epidemiology and clinical characteristics of human coronaviruses OC43, 229E, NL63, and HKU1: a study of hospitalized children with acute respiratory tract infection in Guangzhou, China - Zhi-Qi Zeng; De-Hui Chen; Wei-Ping Tan; Shu-Yan Qiu; Duo Xu; Huan-Xi Liang; Mei-Xin Chen; Xiao Li; Zheng-Shi Lin; Wen-Kuan Liu; Rong Zhou (European Journal of Clinical Microbiology & Infectious Diseases, 2018)

Effects of Dietary Administration of Shewanella xiamenensis A-1, Aeromonas veronii A-7, and Bacillus subtilis, Single or Combined, on the Grass Carp (Ctenopharyngodon idella) Intestinal Microbiota - Kai Hao; Zhuo-Qi Wu; Dong-Liang Li; Xiao-Bo Yu; Gao-Xue Wang; Fei Ling (Probiotics and Antimicrobial Proteins, 2017)

Cloning and characterization of Agp1, the gene encoding the small subunit of ADP-glucose pyrophosphorylase from wheat and its relatives - Xiao-Wei Zhang; Qing Wang; Ling-Ling Zhang; Xiao-Juan Zhong; Qian-Tao Jiang; Jian Ma; Peng-Fei Qi; Wei Li; Guo-Yue Chen; Xiu-Jin Lan; Mei Deng; Zhen-Xiang Lu; et al. (Biologia, 2017)

Microsatellite records for volume 9, issue 3 - Aiguo Yang; Biao Wu; Chao Shen; Guangming Zhang; Hanmiao Liu; Hongying Guo; Jiaman Li; Jinliang Liu; Liqing Zhou; Longbing Rao; Man Yang; Mengdi Li; et al. (Conservation Genetics Resources, 2017)

Gene Polymorphisms for Both Auto-antigen and Immune-Modulating Proteins Are Associated with the Susceptibility of Autoimmune Myasthenia Gravis - Hai-Feng Li; Yu Hong; Xu Zhang; Yanchen Xie; Geir Olve Skeie; Hong-Jun Hao; Nils Erik Gilhus; Bing Liang; Yao-Xian Yue; Xian-Jun Zhang; Xiang Gao; Qi Wang; et al. (Molecular Neurobiology, 2017)

Change in temperature extremes and its correlation with mean temperature in mainland China from 1960 to 2015 - Shibo Fang; Yue Qi; Weiguo Yu; Hanyue Liang; Guojun Han; Qingxiang Li; Shuanghe Shen; Guangsheng Zhou; Guangxun Shi (International Journal of Climatology, 2017)
Changes in temperature extremes can be linked to mean temperature changes and variability. This study aims to quantify observed trends in mean and extreme temperature values and to analyse the relationship between mean and extreme temperatures in mainland China, based on daily data from 1960 to 2015. This is the first analysis undertaken of the relationship between mean and extreme temperatures in mainland China. Based on the 95th and 99th percentiles of daily T max and the 5th and 1st percentiles of daily T min , warm days ( TX95p ), hot days ( TX99p ), cold nights ( TN05p ), and very cold nights ( TN01p ) were defined. The results showed the following: (1) large increasing tendencies of TX95p and TX99p nearly all occurred in locations where mean temperature had substantially increased, and large decreasing tendencies of TN05p were more probably at locations of warming in mainland China; (2) the rise of mean temperature significantly increased the frequency of TX95p and TX99p , and decreased the frequency of TN05p , which indicates a simple shift of the entire distribution towards a warmer climate and greater potential risk of heat waves in the future. The likelihood of occurrence of TX95p and TX99p increased by about 3 and 1 day, respectively, and the occurrence of TN05p was reduced by about 4 days with a mean temperature increase of 1 °C, but the occurrence of TN01p was hardly affected, indicating increased variability of T min temperatures; and (3) the mean and extreme temperatures increased with the urbanization rate in China, and advanced phenologies and unaffected frequency of very cold nights ( TN01p ) could pose more potential risk of frost and freeze injury to crops in China in the future.

Erratum to: Transposon insertion resulted in the silencing of Wx-B1n in Chinese wheat landraces - Ling‑Ling Zhang; Hu Chen; Mi Luo; Xiao‑Wei Zhang; Mei Deng; Jian Ma; Peng‑Fei Qi; Ji‑Rui Wang; Guo‑Yue Chen; Ya‑Xi Liu; Zhi‑En Pu; Wei Li; et al. (Theoretical and Applied Genetics, 2017)

Transposon insertion resulted in the silencing of Wx-B1n in Chinese wheat landraces - Ling-Ling Zhang; Hu Chen; Mi Luo; Xiao-Wei Zhang; Mei Deng; Jian Ma; Peng-Fei Qi; Ji-Rui Wang; Guo-Yue Chen; Ya-Xi Liu; Zhi-En Pu; Wei Li; et al. (Theoretical and Applied Genetics, 2017)

A novel synthetic derivative of squamosamide FLZ inhibits the high mobility group box 1 protein-mediated neuroinflammatory responses in murine BV2 microglial cells - De-Chuan Li; Xiu-Qi Bao; Xiao-Liang Wang; Hua Sun; Dan Zhang (Naunyn-Schmiedeberg's Archives of Pharmacology, 2017)

Lower functional connectivity of default mode network in cognitively normal young adults with mutation of APP, presenilins and APOE ε4 - Yun Yan Su; Xiao Dong Zhang; U. Joseph Schoepf; Akos Varga-Szemes; Andrew Stubenrauch; Xue Liang; Li Juan Zheng; Gang Zheng; Xiang Kong; Qiang Xu; Shou Ju Wang; Rong Feng Qi; et al. (Brain Imaging and Behavior, 2017)

Porcine circovirus type 2 capsid protein induces unfolded protein response with subsequent activation of apoptosis - Ying-shan Zhou; Yuan-xing Gu; Bao-zhu Qi; Yi-kai Zhang; Xiao-liang Li; Wei-huan Fang (Journal of Zhejiang University-SCIENCE B, 2017)

Enhanced Biotransformation of Triclocarban by Ochrobactrum sp. TCC-1 Under Anoxic Nitrate Respiration Conditions - Hui Yun; Bin Liang; Deyong Kong; Zhiling Li; Guoshu Qi; Aijie Wang (Current Microbiology, 2017)

Identification of protein tyrosine phosphatase SHP-2 as a new target of perfluoroalkyl acids in HepG2 cells - Yu Yang; Qi-Yan Lv; Liang-Hong Guo; Bin Wan; Xiao-Min Ren; Ya-Li Shi; Ya-Qi Cai (Archives of Toxicology, 2017)

New isocoumarin and stilbenoid derivatives from the tubers of Sparganium stoloniferum (Buch.-Ham.) - Da-Wei Wu; Qiao-Li Liang; Xiao-Long Zhang; Zheng Jiang; Xiu-He Fan; Wei Yue; Qi-Nan Wu (Natural Product Research, 2017)

Production of human type II collagen using an efficient baculovirus-silkworm multigene expression system - Qi Qi; Lunguang Yao; Zhisheng Liang; Donghua Yan; Zhuo Li; Yadong Huang; Jingchen Sun (Molecular Genetics and Genomics, 2016)

Temperature sensitivity thresholds to warming and cooling in phenophases of alpine plants - Fandong Meng; Yang Zhou; Shiping Wang; Jichuang Duan; Zhenhua Zhang; Haishan Niu; Lili Jiang; Shujuan Cui; Xin’e Li; Caiyun Luo; Lrirong Zhang; Qi Wang; et al. (Climatic Change, 2016)

BMP2 induces chondrogenic differentiation, osteogenic differentiation and endochondral ossification in stem cells - Nian Zhou; Qi Li; Xin Lin; Ning Hu; Jun-Yi Liao; Liang-Bo Lin; Chen Zhao; Zhen-Ming Hu; Xi Liang; Wei Xu; Hong Chen; Wei Huang (Cell and Tissue Research, 2016)

Patterns and drivers of soil microbial communities in Tibetan alpine and global terrestrial ecosystems - Yong‐Liang Chen; Jin‐Zhi Ding; Yun‐Feng Peng; Fei Li; Gui‐Biao Yang; Li Liu; Shu‐Qi Qin; Kai Fang; Yuan‐He Yang (Journal of Biogeography, 2016)
Aim Soil microorganisms play key roles in regulating many important ecosystem processes. However, our understanding of the patterns and drivers of soil microbial communities remains limited. This study aims to test the hypothesis that edaphic factors are more important in explaining variations in soil microbial communities than climatic and biotic factors, as soils directly provide substrates and environment for soil microbial communities. Location Tibetan alpine grasslands and global terrestrial biomes. Methods On the basis of phospholipid fatty acid ( PLFA ) analysis, we investigated large‐scale patterns and drivers of soil microbial communities using data obtained from 196 sites within two major grassland types (alpine steppe and alpine meadow) on the Tibetan Plateau. We also explored global patterns of soil microbial communities by analysing published data from around the world. Results Soil microbial PLFA s in Tibetan alpine grasslands were positively associated with mean annual temperature and mean annual precipitation ( MAP ), contradicting patterns previously observed across global biomes. A combined stepwise regression and variation partitioning analysis revealed that soil microbial community variations in Tibetan alpine grasslands were mainly explained by edaphic factors, such as soil organic carbon, C : N ratio, pH and soil texture, then by biotic factors, such as aboveground biomass and plant species richness, and further by climatic factors, such as MAP . The global analysis confirmed that edaphic factors accounted for a greater portion of the variation in soil microbial communities than did climatic and biotic variables. Main conclusions These results provide strong support for the hypothesis that edaphic factors are the dominant drivers of spatial variations in soil microbial communities across regional and global scales.

The heterogeneity of islet autoantibodies and the progression of islet failure in type 1 diabetic patients - Jin Liu; Lingling Bian; Li Ji; Yang Chen; Heng Chen; Yong Gu; Bingqin Ma; Wei Gu; Xinyu Xu; Yun Shi; Jian Wang; Dalong Zhu; et al. (Science China Life Sciences, 2016)

Overexpression of sugarcane gene SoSnRK2.1 confers drought tolerance in transgenic tobacco - Thi-Thu Phan; Bo Sun; Jun-Qi Niu; Qin-Liang Tan; Jian Li; Li-Tao Yang; Yang-Rui Li (Plant Cell Reports, 2016)

Protective effects of parecoxib on rat primary astrocytes from oxidative stress induced by hydrogen peroxide - Yun-zhi Ling; Xiao-hong Li; Li Yu; Ye Zhang; Qi-sheng Liang; Xiao-di Yang; Hong-tao Wang (Journal of Zhejiang University-SCIENCE B, 2016)

Salicylic acid-induced cytosolic acidification increases the accumulation of phenolic acids in Salvia miltiorrhiza cells - Xiuhong Li; Hongbo Guo; Yuexin Qi; Hailong Liu; Xiaoru Zhang; Pengda Ma; Zongsuo Liang; Juane Dong (Plant Cell, Tissue and Organ Culture (PCTOC), 2016)

Characterization of the waxy gene in diploid Triticum L. and Aegilops L. species and its geographic distribution - Wei Li; Bang-Bo Fu; Zhe Li; Ya-Xi Liu; Zhi-En Pu; Peng-Fei Qi; Qian-Tao Jiang; Guo-Yue Chen; Ji-Rui Wang; Yu-Ming Wei; You-Liang Zheng (Genetic Resources and Crop Evolution, 2016)

A novel process for obtaining pinosylvin using combinatorial bioengineering in Escherichia coli - Jing-long Liang; Li-qiong Guo; Jun-fang Lin; Ze-qi He; Fa-ji Cai; Jun-fei Chen (World Journal of Microbiology and Biotechnology, 2016)

Structure and expression of phosphoglucan phosphatase genes of Like Sex Four1 and Like Sex Four2 in barley - Jian Ma; Shang Gao; Qian-Tao Jiang; Qiang Yang; Min Sun; Ji-Rui Wang; Peng-Fei Qi; Ya-Xi Liu; Wei Li; Zhi-En Pu; Xiu-Jin Lan; Yu-Ming Wei; et al. (Genetica, 2016)

Adaptive evolution of interleukin-3 (IL3), a gene associated with brain volume variation in general human populations - Ming Li; Liang Huang; Kaiqin Li; Yongxia Huo; Chunhui Chen; Jinkai Wang; Jiewei Liu; Zhenwu Luo; Chuansheng Chen; Qi Dong; Yong-gang Yao; Bing Su; et al. (Human Genetics, 2016)

PD-1/PD-L1 signal pathway participates in HCV F protein-induced T cell dysfunction in chronic HCV infection - Wen Xiao; Long Feng Jiang; Xiao Zhao Deng; Dan Yan Zhu; Jia Ping Pei; Mao Lei Xu; Bing Jun Li; Chang Jun Wang; Jing Hai Zhang; Qi Zhang; Zhen Xian Zhou; Wei Liang Ding; et al. (Immunologic Research, 2016)

Study of antibody repertoires to the CD4 binding site of gp120 of a Chinese HIV-1-infected elite neutralizer, using 454 sequencing and single-cell sorting - Dan Li; Zheng Wang; Li Ren; Jing Zhang; Guangda Feng; Kunxue Hong; Yanling Hao; Zhi Qi; Hua Liang; Yiming Shao (Archives of Virology, 2016)

Erratum to: Microsatellite records for volume 7, issue 4 - Rose Komugisha Basiita; J. Henrich Bruggemann; Nianhui Cai; Conchi Cáliz-Campal; Chen Chen; Jiawei Chen; L. Cizek; Pedro J. Cordero; Deborah A. Dawson; Yandong Ding; L. Drag; Anan Duan; et al. (Conservation Genetics Resources, 2016)

Re–Os and U–Pb geochronology of the Laochang Pb–Zn–Ag and concealed porphyry Mo mineralization along the Changning–Menglian suture, SW China: implications for ore genesis and porphyry Cu–Mo exploration - Xiao-Dong Deng; Jian-Wei Li; Xin-Fu Zhao; Hong-Qiang Wang; Liang Qi (Mineralium Deposita, 2016)

RETRACTED ARTICLE: Prognostic Significance of Osteopontin and Carbonic Anhydrase 9 in Human Brain Tumors: A Meta-Analysis - Liang-Yu Chen; Li-Bo Liu; Xin-Xing Li; Qi Yu; Bo Yu; Yang Hong; Jian Zheng; Yi-Xue Xue; Yun-Hui Liu (Molecular Neurobiology, 2015)

Total glycosides of Yupingfeng protects against bleomycin-induced pulmonary fibrosis in rats associated with reduced high mobility group box 1 activation and epithelial–mesenchymal transition - Wenhui Cui; Liucheng Li; Delin Li; Xiaoting Mo; Wencheng Zhou; Zhihui Zhang; Liang Xu; Ping Zhao; Lianwen Qi; Ping Li; Jian Gao (Inflammation Research, 2015)

Feasibility of diagnosing unstable plaque in patients with acute coronary syndrome using iMap-IVUS - Jian Liu; Zhao Wang; Wei-min Wang; Qi Li; Yu-liang Ma; Chuan-fen Liu; Ming-yu Lu; Hong Zhao (Journal of Zhejiang University-SCIENCE B, 2015)

Evaluation of temporal variations in soil moisture based on the microwave polarization difference index using in situ data over agricultural areas in China - Xiao-Jing Han; Si-Bo Duan; Ronglin Tang; Hai-Qi Liu; Zhao-Liang Li (International Journal of Remote Sensing, 2015)

Retraction Note to: Analyzing time-series microarray data reveals key genes in spinal cord injury - Xun Xia; Bo Qu; Yuan Ma; Li-bin Yang; Hai-dong Huang; Jing-ming Cheng; Tao Yang; Bin Kong; En-yu Liu; Kai Zhao; Wei-qi He; Xue-min Xing; et al. (Molecular Biology Reports, 2015)

The impact of hemodialysis on cognitive dysfunction in patients with end-stage renal disease: a resting-state functional MRI study - Hui Juan Chen; Rongfeng Qi; Xiang Kong; Jiqiu Wen; Xue Liang; Zhe Zhang; Xue Li; Guang Ming Lu; Long Jiang Zhang (Metabolic Brain Disease, 2015)

Effects of pre-harvest chemical application on rice desiccation and seed quality - Yong-qi He; Jin-ping Cheng; Liang-feng Liu; Xiao-dan Li; Bin Yang; Hong-sheng Zhang; Zhou-fei Wang (Journal of Zhejiang University-SCIENCE B, 2015)

Antioxidative responses of Pseudomonas fluorescens YZ2 to simultaneous exposure of Zn and Cefradine - Yan-Bin Xu; Jia-Xin Xu; Jin-Liang Chen; Lu Huang; Shao-Qi Zhou; Yan Zhou; Li-Hua Wen (Ecotoxicology, 2015)

Responses of carbon transfer, partitioning, and residence time to land use in the plant–soil system of an alpine meadow on the Qinghai-Tibetan Plateau - Liang Zhao; Dongdong Chen; Na Zhao; Qi Li; Qian Cheng; Caiyun Luo; Shixiao Xu; Shiping Wang; Xinquan Zhao (Biology and Fertility of Soils, 2015)

Decreased PSD95 expression in medial prefrontal cortex (mPFC) was associated with cognitive impairment induced by sevoflurane anesthesia - Yun-zhi Ling; Wei Ma; Li Yu; Ye Zhang; Qi-sheng Liang (Journal of Zhejiang University-SCIENCE B, 2015)

Characterization of genes encoding Starch Branching Enzyme I from Triticum monococcum and its diploid wheat relatives - Xiu-Ying Wang; Chang-Shui Wang; Jian Ma; Ji-Rui Wang; Ya-Xi Liu; Peng-Fei Qi; Wei Li; Zhi-En Pu; Xiu-Jin Lan; Yu-Ming Wei; You-Liang Zheng; Qian-Tao Jiang (Biologia, 2015)

Donor Age and Cell Passage Affect Osteogenic Ability of Rat Bone Marrow Mesenchymal Stem Cells - Chao Li; Guojun Wei; Qun Gu; Gang Wen; Baochang Qi; Liang Xu; Shuqin Tao (Cell Biochemistry and Biophysics, 2015)

Complete genome sequence of a new recombinant echovirus 25 strain isolated from a neonatal patient with hand, foot, and mouth disease complicated by encephalitis in Beijing, China - Hongjie Li; Yixing Meng; Lin Pang; Jinqiu Liang; Hongping Lu; Qi Wang; Pu Liang; Jinfeng Cao; Shun-ai Liu; Jun Cheng (Virus Genes, 2015)

Polymorphic microsatellite loci in the Chinese skink, Plestiodon chinensis (squamata: scincidae) - Tian-qi Fan; Tian-long Fu; Yan-xia Zhang; Hong-liang Lu; Chao-nan Zhu; Shan Sun; Hong Li (Conservation Genetics Resources, 2015)

Establishment and maintenance of a standardized glioma tissue bank: Huashan experience - Abudumijiti Aibaidula; Jun-feng Lu; Jin-song Wu; He-jian Zou; Hong Chen; Yu-qian Wang; Zhi-yong Qin; Yu Yao; Ye Gong; Xiao-ming Che; Ping Zhong; Shi-qi Li; et al. (Cell and Tissue Banking, 2015)

GmPGIP3 enhanced resistance to both take-all and common root rot diseases in transgenic wheat - Aiyun Wang; Xuening Wei; Wei Rong; Liang Dang; Li-Pu Du; Lin Qi; Hui-Jun Xu; Yanjun Shao; Zengyan Zhang (Functional & Integrative Genomics, 2015)

Root cell wall polysaccharides are involved in cadmium hyperaccumulation in Sedum alfredii - Tingqiang Li; Qi Tao; Md Jahidul Islam Shohag; Xiaoe Yang; Donald L. Sparks; Yongchao Liang (Plant and Soil, 2015)

Using rabies virus vaccine strain SRV9 as viral vector to express exogenous gene - Hualei Wang; Hongli Jin; Na Feng; Xuexing Zheng; Ling Li; Yinglin Qi; Meng Liang; Yongkun Zhao; Tiecheng Wang; Yuwei Gao; Changchun Tu; Ningyi Jin; et al. (Virus Genes, 2015)

Polycyclic aromatic hydrocarbons in Chinese surface soil: occurrence and distribution - Wan-Li Ma; Li-Yan Liu; Chong-Guo Tian; Hong Qi; Hong-Liang Jia; Wei-Wei Song; Yi-Fan Li (Environmental Science and Pollution Research, 2015)

Ground-dwelling arthropod community response to native grassland conversion in a temperate desert of northwestern China - Qi Feng; Feng-Rui Li; Ji-Liang Liu; Te-Sheng Sun; Li-Juan Chen (Journal of Insect Conservation, 2015)

Genome-wide discovery of novel and conserved microRNAs in white shrimp (Litopenaeus vannamei) - Qian-Yun Xi; Yuan-Yan Xiong; Yuan-Mei Wang; Xiao Cheng; Qi-En Qi; Gang Shu; Song-Bo Wang; Li-Na Wang; Ping Gao; Xiao-Tong Zhu; Qing-Yan Jiang; Yong-Liang Zhang; et al. (Molecular Biology Reports, 2015)

Therapeutic detoxification of quercetin against carbon tetrachloride-induced acute liver injury in mice and its mechanism - Jia-qi Zhang; Liang Shi; Xi-ning Xu; Si-chong Huang; Bin Lu; Li-li Ji; Zheng-tao Wang (Journal of Zhejiang University-SCIENCE B, 2014)

Bone morphogenetic protein-4 induces upregulation of Cav3.1 Ca2+ channels in HL-1 atrial myocytes - Chao-Wei Hu; Qi Li; Ying Zhang; Yu-Hong Li; Hong-Chao Jiang; Ming-Yu Liu; Shan-Liang Li; Wei Han; De-Li Dong (Pflügers Archiv - European Journal of Physiology, 2014)

RETRACTED ARTICLE: Analyzing time-series microarray data reveals key genes in spinal cord injury - Xun Xia; Bo Qu; Yuan Ma; Li-bin Yang; Hai-dong Huang; Jing-ming Cheng; Tao Yang; Bin Kong; En-yu Liu; Kai Zhao; Wei-qi He; Xue-min Xing; et al. (Molecular Biology Reports, 2014)

Synthesis, biological evaluation, and molecular docking studies of pyrazolyl-acylhydrazone derivatives as novel anticancer agents - Man Xing; Ting-Ting Zhao; Yu-Jia Ren; Na-Na Peng; Xian-Hui Yang; Xi Li; Hui Zhang; Gao-Qi Liu; Li-Rong Zhang; Hai-Liang Zhu (Medicinal Chemistry Research, 2014)

A cross-sectional study of irritable bowel syndrome in nurses in China: prevalence and associated psychological and lifestyle factors - Liang Liu; Qi-fan Xiao; Yan-li Zhang; Shu-kun Yao (Journal of Zhejiang University-SCIENCE B, 2014)

Intergeneric hybrids between Chrysanthemum morifolium ‘Nannongxiaoli’ and Artemisia vulgaris ‘Variegata’ show enhanced resistance against both aphids and Alternaria leaf spot - Wen-ying Zhu; Fei Zhang; Su-mei Chen; Li-li Xu; Liang Wang; Hai-bin Wang; Xiang-yu Qi; Hui-yun Li; Fadi Chen (Euphytica, 2014)

Meta-analysis of the association between common interleukin-1 polymorphisms and dental implant failure - Jian Liao; Chao Li; Yong Wang; MinHua Ten; Xu Sun; Ai Tian; Qi Zhang; Xing Liang (Molecular Biology Reports, 2014)

Identification of BACH2 as a susceptibility gene for Graves’ disease in the Chinese Han population based on a three-stage genome-wide association study - Wei Liu; Hai-Ning Wang; Zhao-Hui Gu; Shao-Ying Yang; Xiao-Ping Ye; Chun-Ming Pan; Shuang-Xia Zhao; Li-Qiong Xue; Hui-Jun Xie; Sha-Sha Yu; Cui-Cui Guo; Wen-Hua Du; et al. (Human Genetics, 2014)

Elevated CO2 concentration increase the mobility of Cd and Zn in the rhizosphere of hyperaccumulator Sedum alfredii - Tingqiang Li; Qi Tao; Chengfeng Liang; Xiaoe Yang (Environmental Science and Pollution Research, 2014)

Geochronology and geochemistry of the Late Triassic Longtan pluton in South China: termination of the crustal melting and Indosinian orogenesis - Liang Qiu; Dan-Ping Yan; Mei-Fu Zhou; Nicholas T. Arndt; Shuang-Li Tang; Liang Qi (International Journal of Earth Sciences, 2014)

Interactive effects of elevated ozone and UV-B radiation on soil nematode diversity - Xuelian Bao; Qi Li; Jianfeng Hua; Tianhong Zhao; Wenju Liang (Ecotoxicology, 2014)

Nitrogen deposition weakens plant–microbe interactions in grassland ecosystems - Cunzheng Wei; Qiang Yu; Edith Bai; Xiaotao Lü; Qi Li; Jianyang Xia; Paul Kardol; Wenju Liang; Zhengwen Wang; Xingguo Han (Global Change Biology, 2013)
Soil carbon (C) and nitrogen (N) stoichiometry is a main driver of ecosystem functioning. Global N enrichment has greatly changed soil C : N ratios, but how altered resource stoichiometry influences the complexity of direct and indirect interactions among plants, soils, and microbial communities has rarely been explored. Here, we investigated the responses of the plant‐soil‐microbe system to multi‐level N additions and the role of dissolved organic carbon ( DOC ) and inorganic N stoichiometry in regulating microbial biomass in semiarid grassland in northern China. We documented a significant positive correlation between DOC and inorganic N across the N addition gradient, which contradicts the negative nonlinear correlation between nitrate accrual and DOC availability commonly observed in natural ecosystems. Using hierarchical structural equation modeling, we found that soil acidification resulting from N addition, rather than changes in the plant community, was most closely related to shifts in soil microbial community composition and decline of microbial respiration. These findings indicate a down‐regulating effect of high N availability on plant–microbe interactions. That is, with the limiting factor for microbial biomass shifting from resource stoichiometry to soil acidity, N enrichment weakens the bottom‐up control of soil microorganisms by plant‐derived C sources. These results highlight the importance of integratively studying the plant‐soil‐microbe system in improving our understanding of ecosystem functioning under conditions of global N enrichment.

Effects of the Conversion of Native Vegetation to Farmlands on Soil Microarthropod Biodiversity and Ecosystem Functioning in a Desert Oasis - Feng-Rui Li; Qi Feng; Ji-Liang Liu; Te-Sheng Sun; Wei Ren; Zhen-Huan Guan (Ecosystems, 2013)

A new generic processing scheme for large baseline spaceborne bistatic SAR data imaging - Feng He; Baoguo Li; Qi Chen; Anxi Yu; Zhihua He; Diannong Liang (International Journal of Remote Sensing, 2013)

Abundance and diversity of archaeal accA gene in hot springs in Yunnan Province, China - Zhao-Qi Song; Li Wang; Feng-Ping Wang; Hong-Chen Jiang; Jin-Quan Chen; En-Min Zhou; Feng Liang; Xiang Xiao; Wen-Jun Li (Extremophiles, 2013)

High levels of divergent HIV-1 quasispecies in patients with neurological opportunistic infections in China - Yulin Zhang; Feili Wei; Qi Liang; Wei Ding; Luxin Qiao; Fengli Song; Lifeng Liu; Sufang Yang; Ronghua Jin; Jianhua Gu; Ning Li; Dexi Chen (Journal of NeuroVirology, 2013)

Genome-wide identification of cancer-related polyadenylated and non-polyadenylated RNAs in human breast and lung cell lines - GuoGuang Zhao; Fei Jiao; Qi Liao; HaiTao Luo; Hui Li; Liang Sun; DeChao Bu; KunTao Yu; Yi Zhao; RunSheng Chen (Science China Life Sciences, 2013)

Genetic characterization of avian-origin H3N2 canine influenza viruses isolated from Guangdong during 2006–2012 - Heng Wang; Kun Jia; Wenbao Qi; Minze Zhang; Long Sun; Huanbin Liang; Guohao Du; Likai Tan; Zhenwen Shao; Jiahui Ye; Lingshuang Sun; Zhenpeng Cao; et al. (Virus Genes, 2013)

Preliminary applications of a land surface temperature retrieval method to IASI and AIRS data - Xiaoying Ouyang; Guoting Kang; Funian Zeng; Enyun Qi; Zhao-Liang Li (International Journal of Remote Sensing, 2013)

Dietary exposure to aluminium of urban residents from cities in South China - Qi Jiang; Jing Wang; Min Li; Xuxia Liang; Guangwei Dai; Zhikun Hu; Jian Wen; Qiong Huang; Yonghui Zhang (Food Additives & Contaminants: Part A, 2013)

Shrubs and species identity effects on the distribution and diversity of ground-dwelling arthropods in a Gobi desert - Feng-Rui Li; Ji-Liang Liu; Chang-An Liu; Qi-Jun Liu; Rui-Xue Niu (Journal of Insect Conservation, 2013)

Prevalence of type-specific human papillomavirus and pap results in Chinese women: a multi-center, population-based cross-sectional study - En-Qi Wu; Bin Liu; Jian-Feng Cui; Wen Chen; Jian-Bing Wang; Liang Lu; Mayineur Niyazi; Chao Zhao; Sheng-Da Ren; Chang-Qing Li; Xiang-Zhen Gong; Jennifer S. Smith; et al. (Cancer Causes & Control, 2013)

Lyssavirus surveillance in bats of southern China’s Guangxi Province - Zhuan-Ling Lu; Wen Wang; Wei-Li Yin; Hai-Bo Tang; Yan Pan; Xiang Liang; Qi Liu; Yi Xiong; Nobuyuki Minamoto; Ting Rong Luo (Virus Genes, 2013)

Bacterial and archaeal diversities in Y unnan and T ibetan hot springs, C hina - Zhao‐Qi Song; Feng‐Ping Wang; Xiao‐Yang Zhi; Jin‐Quan Chen; En‐Min Zhou; Feng Liang; Xiang Xiao; Shu‐Kun Tang; Hong‐Chen Jiang; Chuanlun L. Zhang; Hailiang Dong; Wen‐Jun Li (Environmental Microbiology, 2013)
Summary Thousands of hot springs are located in the north‐eastern part of the Y unnan– T ibet geothermal zone, which is one of the most active geothermal areas in the world. However, a comprehensive and detailed understanding of microbial diversity in these hot springs is still lacking. In this study, bacterial and archaeal diversities were investigated in 16 hot springs ( pH 3.2–8.6; temperature 47–96° C ) in Y unnan P rovince and T ibet, C hina by using a barcoded 16 S rRNA gene‐pyrosequencing approach. A quificae , P roteobacteria , F irmicutes , D einococcus‐ T hermus and B acteroidetes comprised the large portion of the bacterial communities in acidic hot springs. Non‐acidic hot springs harboured more and variable bacterial phyla than acidic springs. D esulfurococcales and unclassified C renarchaeota were the dominated groups in archaeal populations from most of the non‐acidic hot springs; whereas, the archaeal community structure in acidic hot springs was simpler and characterized by S ulfolobales and T hermoplasmata . The phylogenetic analyses showed that A quificae and C renarchaeota were predominant in the investigated springs and possessed many phylogenetic lineages that have never been detected in other hot springs in the world. Thus findings from this study significantly improve our understanding of microbial diversity in terrestrial hot springs.

Pancreatic cystic neoplasms: a review of preoperative diagnosis and management - Xue-li Bai; Qi Zhang; Noman Masood; Waqas Masood; Yun Zhang; Ting-bo Liang (Journal of Zhejiang University-SCIENCE B, 2013)

Toxic Effects of Acetochlor on Mortality, Reproduction and Growth of Caenorhabditis elegans and Pristionchus pacificus - Jingnan Zhang; Wenju Liang; Xia Wu; Siwei Jiang; Qi Li (Bulletin of Environmental Contamination and Toxicology, 2013)

Late Paleoproterozoic sedimentary rock-hosted stratiform copper deposits in South China: their possible link to the supercontinent cycle - Xin-Fu Zhao; Mei-Fu Zhou; Jian-Wei Li; Liang Qi (Mineralium Deposita, 2013)

Bm65 is Essential for the Propagation of Bombyx mori Nucleopolyhedrovirus - Qi Tang; Guohui Li; Qin Yao; Liang Chen; Fan Feng; Yi Yuan; Keping Chen (Current Microbiology, 2013)

Impact of a dust storm on characteristics of particle matter (PM) in Guangzhou, China - Qi Fan; Chong Shen; Xuemei Wang; Yuan Li; Wei Huang; Guixiong Liang; Shaoyi Wang; Zhuoer Huang (Asia-Pacific Journal of Atmospheric Sciences, 2013)

Simple and rapid detection of swine hepatitis E virus by reverse transcription loop-mediated isothermal amplification - Liang-Quan Zhang; Fu-Rong Zhao; Zhi-Gang Liu; Wei-Li Kong; Heng Wang; Yun Ouyang; Huan-Bin Liang; Chao-Yi Zhang; Hai-Tao Qi; Chang-Li Huang; Si-Hu Guo; Gui-Hong Zhang (Archives of Virology, 2012)

Cloning and Characterization of the Wx Gene Encoding a Granule-Bound Starch Synthase in Lotus (Nelumbo nucifera Gaertn) - Ye Lu; Liangjun Li; Yong Zhou; Qingsong Gao; Guohua Liang; Xuehao Chen; Xiaohua Qi (Plant Molecular Biology Reporter, 2012)

Influences of shrub vegetation on distribution and diversity of a ground beetle community in a Gobi desert ecosystem - Ji-Liang Liu; Feng-Rui Li; Chang-An Liu; Qi-Jun Liu (Biodiversity and Conservation, 2012)

An updated meta-analysis of the p53 codon 72 polymorphism and gastric cancer risk - Kui-Jie Liu; Hai-Zhi Qi; Hong-Liang Yao; San-Lin Lei; Zhen-Dong Lei; Tie-Gang Li; Hua Zhao (Molecular Biology Reports, 2012)

Possible novel roles of poly(rC)-binding protein 1 in SH-SY5Y neurocytes: an analysis using a dynamic Bayesian network - Li-Rong Huo; Jian-Tao Liang; Jun-Hua Zou; Lan-Ying Wang; Qi Li; Xiao-Min Wang (Neuroscience Bulletin, 2012)

Consistent isomiR expression patterns and 3′ addition events in miRNA gene clusters and families implicate functional and evolutionary relationships - Li Guo; Hailing Li; Tingming Liang; Jiafeng Lu; Qi Yang; Qinyu Ge; Zuhong Lu (Molecular Biology Reports, 2012)

Biofilm formation and microbial community analysis of the simulated river bioreactor for contaminated source water remediation - Xiang-Yang Xu; Li-Juan Feng; Liang Zhu; Jing Xu; Wei Ding; Han-Ying Qi (Environmental Science and Pollution Research, 2012)

Inhibition of matrine against gastric cancer cell line MNK45 growth and its anti-tumor mechanism - Cong Luo; Hai Jun Zhong; Li Ming Zhu; Xian Guo Wu; Jie Er Ying; Xiao Hong Wang; Wang Xia LÜ; Qi Xu; Yong Liang Zhu; Jian Huang (Molecular Biology Reports, 2012)

MiRNA-140 is a negative feedback regulator of MMP-13 in IL-1β-stimulated human articular chondrocyte C28/I2 cells - Zu-jian Liang; Hong Zhuang; Guo-xia Wang; Zhao Li; Huan-tian Zhang; Tian-qi Yu; Bai-dang Zhang (Inflammation Research, 2012)

Ectopic expression of a LEA protein gene TsLEA1 from Thellungiella salsuginea confers salt-tolerance in yeast and Arabidopsis - Yiyue Zhang; Yin Li; Jianbin Lai; Huawei Zhang; Yuanyuan Liu; Liming Liang; Qi Xie (Molecular Biology Reports, 2012)

Fertilization increases paddy soil organic carbon density - Shao-xian Wang; Xin-qiang Liang; Qi-xiang Luo; Fang Fan; Ying-xu Chen; Zu-zhang Li; Huo-xi Sun; Tian-fang Dai; Jun-nan Wan; Xiao-jun Li (Journal of Zhejiang University-SCIENCE B, 2012)

Larval settlement and metamorphosis of the mussel Mytilus coruscus in response to natural biofilms - Chong Wang; Wei-Yang Bao; Zhong-Qi Gu; Yi-Feng Li; Xiao Liang; Yun Ling; Sheng-Li Cai; He-Ding Shen; Jin-Long Yang (Biofouling, 2012)

Development of a simple and efficient transformation system for the basidiomycetous medicinal fungus Ganoderma lucidum - Liang Shi; Xing Fang; Mengjiao Li; Dashuai Mu; Ang Ren; Qi Tan; Mingwen Zhao (World Journal of Microbiology and Biotechnology, 2012)

Suboptimal Selenium Supply—A Continuing Problem in Keshan Disease Areas in Heilongjiang Province - Jie Hou; Tong Wang; Mingfa Liu; Shaochen Li; Jie Chen; Chunxu Liu; Hui Zhang; Yiru Wang; Zengchao Liu; Na Liang; Yuezhu Wan; Qi Li; et al. (Biological Trace Element Research, 2011)

Plasma Paraoxonase-1, Oxidized Low-Density Lipoprotein and Lipid Peroxidation Levels in Gout Patients - Xing-Liang Jiang; Min Li; Jing-Guo Zhou; Qi-Bin Yang; Li-Jun Du; Juan Du (Cell Biochemistry and Biophysics, 2011)

Global transcriptional profiles of Mycobacterium tuberculosis treated with plumbagin - Haiqing Ye; Zengshan Liu; Aizhen Guo; Junchao Liang; Na Guo; Fanli Zeng; Liqiang Liu; Lei Li; Jing Jin; Xiuping Wu; Yang Li; Mingyuan Liu; et al. (World Journal of Microbiology and Biotechnology, 2011)

Physiology and cell biology of acupuncture observed in calcium signaling activated by acoustic shear wave - Geng Li; Jie-Ming Liang; Pei-Wen Li; Xiaoqiang Yao; Peter Zhong Pei; Wei Li; Qi-Hua He; Xifei Yang; Queenie C. C. Chan; Paul Y. S. Cheung; Qi Yuan Ma; Siu Kam Lam; et al. (Pflügers Archiv - European Journal of Physiology, 2011)

Microsatellite Analysis of Homozygosity Progression of Heterozygous Genotypes Segregating in the Rice Subspecies Cross Pei’ai64s/Nipponbare - Yong-shu Liang; Qi-jun Zhang; Shi-quan Wang; Li-yong Cao; Zhi-qiang Gao; Ping Li; Shi-hua Cheng (Biochemical Genetics, 2011)

Study of Lead Level During Pregnancy by Application of Synchrotron Radiation Micro XRF - Yongpeng Tong; Huibin Sun; Qi Luo; Jinxing Feng; Xiaohong Liu; Feng Liang; Fen Yan; Ke Yang; Xiaohan Yu; Yulan Li; Jianmin Chen (Biological Trace Element Research, 2011)

Leaching behavior of nitrogen in a long-term experiment on rice under different N management systems - Liang-guo Luo; Sumio Itoh; Qing-wen Zhang; Shi-qi Yang; Qing-zhong Zhang; Zheng-li Yang (Environmental Monitoring and Assessment, 2011)

Characterization of Exserohilum rostratum, a new causal agent of banana leaf spot disease in China - Shan-Hai Lin; Si-Liang Huang; Qi-Qin Li; Chun-Jin Hu; Gang Fu; Li-Ping Qin; Yue-Feng Ma; Ling Xie; Zhen-Lu Cen; Wei-Hong Yan (Australasian Plant Pathology, 2011)

Microarray Analysis of the Chelerythrine-Induced Transcriptome of Mycobacterium tuberculosis - Junchao Liang; Fanli Zeng; Aizhen Guo; Liqiang Liu; Na Guo; Lei Li; Jing Jin; Xiuping Wu; Mingyuan Liu; Dan Zhao; Yang Li; Qi Jin; et al. (Current Microbiology, 2011)

Genetic Diversity and Identity of Chinese Loquat Cultivars/Accessions (Eriobotrya japonica) Using Apple SSR Markers - Qiao He; Xiong Wei Li; Guo Lu Liang; Kun Ji; Qi Gao Guo; Wei Min Yuan; Gen Zhi Zhou; Kun Song Chen; W. Eric van de Weg; Zhong Shan Gao (Plant Molecular Biology Reporter, 2011)

Prognostic value of serum soluble Fas in patients with locally advanced unresectable rectal cancer receiving concurrent chemoradiotherapy - Qi-lian Liang; Zhou-yu Li; Guo-qiang Chen; Zhen-nan Lai; Bi-rong Wang; Jie Huang (Journal of Zhejiang University-SCIENCE B, 2010)

Development of a large-scale isolation chamber system for the safe and humane care of medium-sized laboratory animals harboring infectious diseases - Xin Pan; Jian-cheng Qi; Ming Long; Hao Liang; Xiao Chen; Han Li; Guang-bo Li; Hao Zheng (Journal of Zhejiang University-SCIENCE B, 2010)

Utility of nematode Acrobeloides nanus for assessing subacute toxicity of heavy metals - Wei Hao; Qi Li; Jingnan Zhang; Yong Jiang; Wenju Liang (Environmental Monitoring and Assessment, 2010)

Applying DNA C-values to evaluate invasiveness of angiosperms: validity and limitation - Guo-Qi Chen; Shui-Liang Guo; Li-Ping Yin (Biological Invasions, 2010)

Frequent occurrence of unreduced gametes in Triticum turgidum–Aegilops tauschii hybrids - Lian-Quan Zhang; Deng-Cai Liu; You-Liang Zheng; Ze-Hong Yan; Shou-Fen Dai; Yun-Fang Li; Qi Jiang; Ya-Qing Ye; Yang Yen (Euphytica, 2010)

Identification and characterization of a novel capsid protein encoded by Singapore grouper iridovirus ORF038L - Qing Jiao Wan; Jie Gong; Xiao Hong Huang; You Hua Huang; Sheng Zhou; Zheng Liang Ou-Yang; Jian Hao Cao; Li Li Ye; Qi Wei Qin (Archives of Virology, 2010)

DcR3 and survivin are highly expressed in colorectal carcinoma and closely correlated to its clinicopathologic parameters - Qi-lian Liang; Bi-rong Wang; Guo-hong Li (Journal of Zhejiang University-SCIENCE B, 2009)

The Polymorphism of DNA Repair Gene ERCC2/XPD Arg156Arg and Susceptibility to Breast Cancer in a Chinese Population - Jiaoyang Yin; Duohong Liang; Ulla Vogel; Yaping Chang; Zhengrong Liu; Li Yue; Xiaoling Sun; Rong Qi; Tiehua Song (Biochemical Genetics, 2009)

Genome-wide association scan for stature in Chinese: evidence for ethnic specific loci - Shu-Feng Lei; Tie-Lin Yang; Li-Jun Tan; Xiang-Ding Chen; Yan Guo; Yan-Fang Guo; Liang Zhang; Xiao-Gang Liu; Han Yan; Feng Pan; Zhi-Xin Zhang; Yu-Mei Peng; et al. (Human Genetics, 2009)

Molecular Identification of cDNA, Immunolocalization, and Expression of a Putative Odorant-Binding Protein from an Asian Honey Bee, Apis cerana cerana - Hong-Liang Li; Ya-Li Zhang; Qi-Kang Gao; Jia-An Cheng; Bing-Gan Lou (Journal of Chemical Ecology, 2008)

Controls on variations of platinum-group element concentrations in the sulfide ores of the Jinchuan Ni-Cu deposit, western China - Shangguo Su; Chusi Li; Mei-Fu Zhou; Edward M. Ripley; Liang Qi (Mineralium Deposita, 2008)

Membrane Tension Modulates the Effects of Apical Cholesterol on the Renal Epithelial Sodium Channel - Shi-Peng Wei; Xue-Qi Li; Chu-Fang Chou; You-You Liang; Ji-Bin Peng; David G. Warnock; He-Ping Ma (The Journal of Membrane Biology, 2007)

Notch activation promotes cell proliferation and the formation of neural stem cell-like colonies in human glioma cells - Xue-Ping Zhang; Gang Zheng; Lian Zou; Hui-Ling Liu; Li-Hong Hou; Peng Zhou; Dan-Dan Yin; Qi-Jun Zheng; Liang Liang; Su-Zhen Zhang; Lei Feng; Li-Bo Yao; et al. (Molecular and Cellular Biochemistry, 2007)

Wavefield continuation datuming using a near surface model - Xingfu Cui; Hongbing Li; Ying Hu; Hong Liang; Li Qi (Applied Geophysics, 2007)

Recovery of novel bacterial diversity from mangrove sediment - Jun-Bin Liang; Yue-Qin Chen; Chong-Yu Lan; Nora F. Y. Tam; Qi-Jie Zan; Li-Nan Huang (Marine Biology, 2007)

Application of cDNA array for studying the gene expression profile of mature appressoria of Magnaporthe grisea - Qing-chao Jin; Hai-tao Dong; You-liang Peng; Bao-shan Chen; Jing Shao; Ye Deng; Cheng-en Dai; Yong-qi Fang; Yi-chun Lou; You-zhi Li; De-bao Li (Journal of Zhejiang University-SCIENCE B, 2007)

Forskolin up-regulates metastasis-related phenotypes and molecules via protein kinase B, but not PI-3K, in H7721 human hepato-carcinoma cell line - Shi-liang Wu; Jun Ma; Hui-ling Qi; Ying Zhang; Xia-ying Zhang; Hui-li Chen (Molecular and Cellular Biochemistry, 2003)